Rational Design of Naringenin-Functionalized ZnO Nanoparticles for Wound Healing Applications with Cytocompatibility Assessment in L929 Fibroblast Cells - Ayusha O. Dondulkar; Mandar M. Muley; Raj Kiran; Siva Hemalatha; Prakash R. Itankar; Nikhil Y. Yenorkar; Raksha A. Purohit; Sadhana Soni; Arun Upadhyay; Beauty Behera; Natasha S. Akojwar; Satyendra K. Prasad (Journal of Pharmaceutical Innovation, 2027)

Replacing maize grain with self-fermented agro-waste in total mixed ration improves fatty acid profile, oxidative stability and meat quality traits in goats - Rajat Bagdas; Gauri Jairath; Varun; Suman Bishnoi; Yashavanth Basavapatna Subbanna; Gorakh Mal; Ashim K. Biswas; Triveni Dutt; Arup Ratan Sen; Randhir Singh Bhatt; Lalit Kumar Soni; Birbal Singh; et al. (Meat Science, 2026)

Multiscale structural and functional characterisation of phenolic-reduced rapeseed protein isolates: Effects of phenolic removal and drying methods - Akhilesh Modi; Twinkle Soni; Amit Arora; Sushil Dhital (Food Hydrocolloids, 2026)

Modelling uncertainty in WRF-based extreme rainfall simulations over India: A review toward integrated atmosphere-chemistry-hydrology frameworks - Saurabh Maurya; Pramod Soni (Atmospheric Research, 2026)

GABARAPL2 and Alix mediate reciprocal regulation of autophagy and exosome pathways to facilitate cellular homeostasis - Naveen Soni; Megha Chaudhary; Bhawana Bissa (Molecular Biology Reports, 2026)

Multiscale predictive cellular modeling: integrating hypothesis grammars, digital twins, and multi-omics for In silico oncology and precision theranostics - S. T. Gopukumar; Dyumn Dwivedi; Mohamed Rahamathulla; Mohammed Muqtader Ahmed; Tanveen Kaur Soni; Praveen Ganesh Natarajan; S. Ramkanth; Arpita Mitra; Uddalak Das (Functional & Integrative Genomics, 2026)

Comparative phenotypic analysis of primary aortic VSMCs versus TGF - β/PDGF - BB differentiated MSCs in rat - Pulkit Soni; Diksha Rani; Manish Kumar; Vaibhav Kushwaha; Anurag Thapliyal; Satyavir Yadav; Shashank Kumar Maurya; Sanjay Kumar Dey (Tissue and Cell, 2026)

Modulation of experimental colitis by Enterococcus faecalis, Enterococcus faecium, and Bacillus subtilis: insights from infectious and chemical models - Ajinath Kale; Aayush Kamiya; Dipika Limje; Manoranjan Sharma; Riteshri Soni; Meghrajsinh Jadeja; Onkar Date; Hiren Patel; Jinal Patel; Ashvin Patel; Purvi Vyas; Kasinath Viswanathan; et al. (Archives of Microbiology, 2026)

Protective effects of curcumin on short and long-term particulate matter (PM10/2.5) induced lung damage severity via modulation of neutrophil extracellular traps (NETs) formation in mouse model - Diksha Sharma; Vandana Soni; Shalini Singh; Prashant Kumar Chauhan; Abhay Kumar Singh; Rashmi Singh (Tissue and Cell, 2026)

Transportation pathways of black carbon aerosols and radiative impacts over India - Vivek Kumar; M. Sateesh; Panuganti CS. Devara; Anikender Kumar; Chinmay Kumar Jena; Vijay Kumar Soni (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Solvent-dependent extraction of phenolic compounds from Curcuma caesia Roxb. Rhizomes: HPTLC profiling, antioxidant activity and correlation analysis - Vinita Tamrakar; S.K. Ghosh; Shweta Tamrakar; Jyoti Pandey; Rakesh Soni (Next Research, 2026)

Designing a bimetallic Fe,Co-MOF supported Sn-doped BiFeO3/CdS dual Z-scheme heterojunction for boosted visible light gatifloxacin degradation: Coupling experimental performance with DFT insights - Monika Malhotra; Vatika Soni; Rohit Kumar; Pardeep Singh; Konstantin P. Katin; Savaş Kaya; Mehmet Erdem; Tansir Ahamad; Van-Can Nguyen; Van-Huy Nguyen; Pankaj Raizada (Journal of Environmental Chemical Engineering, 2026)

Evaluating the performance of the Global Forecast System (GFS) during a tropical cyclone over India using Radiosonde observations: A case study - M. Ashok Williams; Anshul Chauhan; S.T. Akhil Raj; M.I. Ansari; Gajendra Kumar; Vijay Kumar Soni (Atmospheric Research, 2026)

From Coast to Canopy: Polybrominated Diphenyl Ethers (PBDEs) in Selected Coastal Ecosystems of Western India, and Their Bioaccumulation in Mangrove Species - Chetankumar Nandanwar; Ayush Vikram Singh; Rakhi Nikhade; Yogiraj Joginath Basheshankar; Manju Soni; Pravin Krishnarao Naoghare (International Journal of Environmental Research, 2026)

Smartphone-assisted detection of Bi3+ ions using a calix[4]arene-based fluorescent sensor from cosmetics and water samples - Krushna A. Baraiya; Heni N. Soni; Jinal V. Zala; Saim A. Khatri; Sunil H. Chaki; Divyesh Y. Chaudhari; Sahaj A. Gandhi; Pinkesh G. Sutariya (Analytica Chimica Acta, 2026)

Phosphorus capture from subsurface drainage water using iron-activated alumina (Alcan): Column adsorption, regeneration, and agronomic reuse evaluation - Soni Kumari; Younsuk Dong (Journal of Environmental Sciences, 2026)

Synergistic effect of dual-biowax on biodegradable PLA nanofibers for high-performance and antifouling oil–water separation: Mechanistic insights from molecular docking and dynamics simulations - Neha Soni; Monica Jaiswal; Mousam Choudhury; Husn Ara Chauhan; Tushar Kumeria; Ranu Nayak (Chemical Engineering Journal, 2026)

Bio-Synthesized Silver Nanoparticles from Neolamarckia Cadamba: Characterization and Analysis - Vivek P. Bhange; Ruta D. Khonde; Manju A. Soni; Vivek M. Nanoti (Water, Air, & Soil Pollution, 2026)

In vitro seed germination, propagation, and biochemical profiling of Meconopsis aculeata royle: an endangered medicinal and ornamental herb of the high-altitude Himalayas - Kamlesh Verma; Mahinder Partap; Priyanka Parmar; Vidyashankar Srivatsan; Rahul Bodh; Vikas Soni; Bhavya Bhargava (In Vitro Cellular & Developmental Biology - Plant, 2026)

Dibenzofuran Based Donor-Pi-Acceptor Molecules: Effect of Azo and Aminomethylene Linkages on Photophysical and NLO Properties - Jay Patel; Amitbhai Ahir; Rina Soni; Divyesh Patel (Journal of Fluorescence, 2026)

Comparative metabolite profiling and SNP analysis of Psoralea corylifolia callus following chemical mutagenesis - Mayuri G. Tatte; Manju A. Soni; Vivek P. Bhange (Journal of Plant Biochemistry and Biotechnology, 2026)

Integrated in silico and in vivo approaches reveal naltrexone as a synergistic modulator of TLR4 and μ-opioid receptors restoring redox homeostasis via Nrf2/Keap-1/HO-1 and HIF-1α/VEGF pathways in COPD - Soni; Atul Srivastava; Pratikkumar Gaglani; Vandana Yadav; Vinita Pandey; Subhashini (Molecular and Cellular Biochemistry, 2026)

Phytotoxic effects of personal care products in agro-ecosystems: plant uptake dynamics and cellular perturbations - Dipti Agarwal; Upma Bhatt; Vineet Soni (Environmental Science and Pollution Research, 2026)

Ofloxacin impairs photosynthetic efficiency, oxidative homeostasis, and growth in Azolla pinnata - Hari Dev Chaudhary; Aditi Mishra; Upma Bhatt; Vineet Soni (Environmental Science and Pollution Research, 2026)

Participatory adaptive groundwater management using geometric fuzzy identification of recharge strategies under environmental uncertainty - Soni Kumari; Srinivas Rallapalli; Ajit Pratap Singh; Mohammed Bhuiyan; Kevin Zhang (Groundwater for Sustainable Development, 2026)

La2Co0.9W0.1Mn1O6-δ coupled with VN: A synergistic heterojunction for supercapacitor electrode - Prakshi Soni; Shobhita Singal; Raj Kishore Sharma (Chemical Engineering Journal, 2026)

A Comprehensive Review on the Multifaceted Applications, Ecological Impact and Bioactivity of Harnessing Eichhornia Crassipes - Karan Ashokbhai Rathod; Mital Rajbhai Soni; Nishant Ranjan (Water Conservation Science and Engineering, 2026)

Spatiotemporal effects of blue-green infrastructure on land surface temperature across local geo-urban zones in Bhopal - Aishwarya Dwivedi; Rajat Soni (Theoretical and Applied Climatology, 2026)

Long-Term Trends and Variability in Global and Diffuse Solar Radiation Over India - Somnath Mahato; Pushpa Saroja; Vijai Kumar; Anjit Anjan; Vijai Kumar Soni; D. S. Pai (Pure and Applied Geophysics, 2026)

Effects of Nationwide COVID-19 Lockdown on Fossil Fuel and Biomass Burning Emissions in India - Anikender Kumar; Vivek Kumar; Chinmay Kumar Jena; Sanjay Bist; Vijay Kumar Soni (Aerosol Science and Engineering, 2026)

Chlorophyll a Fluorescence Based Physiological Screening of Stress Responses and Recovery Under Liriomyza trifolii Infestation in Solanum lycopersicum - Komal Sharma; Dipti Agarwal; Upma Bhatt; Vineet Soni (Journal of Crop Health, 2026)

Microsatellite markers-based diversity assessment in urdbean genotypes (Vigna mungo L Hepper) - Ayushi Soni; Stuti Sharma; Shikha Upadhyay; R. S. Sharma; R. Shiv Ramakrishnan (Plant Physiology Reports, 2026)

Evolutionary analysis and genome organization of a genetically divergent isolate of Tomato leaf curl Joydebpur virus associated with a betasatellite infecting Capsicum annuum in Central India - Akshita Soni; Shobhit Maheshwari; Sunil Kumar Snehi (Indian Phytopathology, 2026)

Silicon nanoparticles in agriculture: applications, mechanisms and future prospects for crop improvement - Vikram Singh; Pooja Jangir; Praveen Soni (Journal of Plant Biochemistry and Biotechnology, 2026)

Late embryogenesis protein (LEA): not so late for plants under stress - Aastha Sharma; Tapan Kumar Mondal; Soni Chowrasia (The Nucleus, 2026)

Fencing off critical source areas reduces faecal contamination and reshapes microbial communities in agricultural headwater catchments - Adrian L. Cookson; Rose M. Collis; Aswathi Soni; Fleur Srey; Richard W. Muirhead (Science of The Total Environment, 2026)

Antimicrobial, antioxidant, anti-inflammatory, and antacid activities of selected Indian medicinal plants with potential applications against fungi and multidrug-resistant bacteria - Adtiya Raj; Gagandeep Singh; Hemant Soni; Smriti Tandon; Virendra Singh; Sanjeev Kumar Lale; Hemant Rawat; Cheemalapati Venkata Narasimhaji; Sanjaya Kumar YR; Narayanam Srikanth; Rabinarayan Acharya (Next Research, 2026)

Thermosensitive TRP channels as dietary modulators of adipose thermogenesis: Implications for energy homeostasis and obesity - Yashdeep Mukheja; Roshan Lal; Neha Soni; Jasleen Kaur; Pragyanshu Khare; Kanthi Kiran Kondepudi; Kanwaljit Chopra; Mahendra Bishnoi (Journal of Thermal Biology, 2026)

In silico and in vitro insights into stigmasterol targeting Keap1/Nrf2, Bcl-2/Bax and IKKβ/IκBα protein–protein interactions in Arsenic-induced toxicity - Manoj Soni; Vivek Kumar; Yangala Sudheer Babu; Pawan Kumar; Mulaka Maruthi; Pooja Yadav; Ajit Kumar; Vijay Kumar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Prediction of Aerosol Optical Depth Using a Support Vector Machine Model in the Coal Mining Regions of Assam - Nishant Kumar; Kirti Soni; Kulwinder Singh Parmar; Pranalee Thorat; Dipankar Saha; Arvind Kumar Jha; Anikender Kumar; Vijay Kumar Soni (Journal of the Indian Society of Remote Sensing, 2026)

Intercomparison and Validation of SODAR and ERA5 Measured Atmospheric Boundary Layer Height Over Delhi - Nishant Kumar; Anjali S. Nair; Avni Tiwari; Kirti Soni; V. K. Soni; Anikender Kumar; Arvind Jha; Dharmendra Gupta (Journal of the Indian Society of Remote Sensing, 2026)

Neuroinflammation mediated repurposing of clemastine for Alzheimer’s disease through network pharmacology, molecular dynamics, and experimental validation studies - Simran Soni; Sinjini Sarkar; Pratigya Tripathi; Satyamvada Maurya; Ginpreet Kaur; Shafiul Haque (Inflammopharmacology, 2026)

Quantification and characterization of soil organic carbon with different environmental gradients for the high altitude wetlands of Indian Himalaya - Narayan P. Anugraha; D. Ganguly; A. Paneer Selvam; Kakolee Banerjee; M. Harikrishna Prasad; Lakpa Tamang; Sushmita Chettri; Anupriya Soni; Rajesh Joshi; Ajay Kumar Gupta; Prakash Chhetri; Ramachandran Purvaja (Environmental Geochemistry and Health, 2026)

In silico and in vitro antibacterial investigation of Origanum majorana L. leaves extract against gram-positive and gram-negative bacteria - Rajan Rolta; Deeksha Salaria; Megha Soni; Gajendra Choudhary; Uma Ranjan Lal; Ajay Prakash; Arunanshu Behera; Vikas Gautam; Lileswar Kaman; Bikash Medhi (In Silico Pharmacology, 2026)

Bio-inspired stearic acid functionalized polylactic acid nanofibers with nanodome architecture for enhanced oil–water separation - Neha Soni; Sheril Delma Vas; Tushar Kumeria; Ranu Nayak (Environmental Science and Pollution Research, 2026)

The potential of bioengineered exosomes in regenerative medicine: a next generation therapy - Shiwani Kumari; Anjali Agnihotri; Arpit Sharma; Shweta Dongre; Ashwani Tiwari; Naveen Soni; Bhawana Bissa (Human Cell, 2026)

Root exudate-driven rhizosphere engineering: Integrating microbial community design and nanotechnology for sustainable agriculture - Jyoti Yadav; Pushpa Gehlot; Deepali Chittora; Bhanu Raj Meena; Priya Soni; Tripta Jain (Rhizosphere, 2026)

Pharmacological and comparative evaluation of green coffee bean extract (Coffee arabica) and phytoconstituents for the attenuating airway inflammation via NF-κB inhibitory signaling pathway in ovalbumin-induced Balb/c - Mamta Saini; Saurabh Gupta; Sushma Devi; Ahsas Goyal; Girish Chandra Sharma; Kavitha; Kavita Goyal; Md Sadique Hussain; Thakur Gurjeet Singh; Diksha Sharma; Pooja Mittal; Hardik Soni; et al. (PharmaNutrition, 2026)

Facet-engineered MIL-88A1(Fe-MOF)/MoO3 Z-scheme heterojunction for enabling efficient peroxymonosulfate-driven photo-degradation of ciprofloxacin: Synergetic performance, DFT calculations and mechanism insights - Monika Malhotra; Vatika Soni; Pardeep Singh; Duc Anh Dinh; Konstantin P. Katin; Savaş Kaya; Tansir Ahamad; Van-Huy Nguyen; Pankaj Raizada (Journal of Water Process Engineering, 2026)

Interface-engineered UiO-66-NH2-based S-scheme heterojunction for enhanced solar to chemical conversion - Anshika Bhardwaj; Monika Malhotra; Vatika Soni; Pardeep Singh; Van-Huy Nguyen; Aftab Aslam Parwaz Khan; Khoa Dang Dang; Savaş Kaya; Pankaj Raizada (Journal of Environmental Chemical Engineering, 2026)

Avian diversity and responses to altitude and human disturbance in Askot Wildlife Sanctuary, Western Himalaya - Soni Bisht; Gopal Singh Rawat (Journal for Nature Conservation, 2026)

Prediction of biochar yield from the pyrolysis of sewage sludge: supervised machine learning models assisted approach for better accuracy - Nitin Kumar Soni; Prabhansu; Purnanand V. Bhale (Biomass and Bioenergy, 2026)

Statistical optimisation of steam pretreatment and enzymatic hydrolysis for enhanced sugar recovery and bioethanol production from composite food waste - Bishakha Thakur; Raman Soni; Deepak Kumar Rahi; Sanjeev Kumar Soni (Bioresource Technology Reports, 2026)

Advances in microbial biofilm-driven bioremediation: Mechanistic breakthroughs, technological innovations, and future perspectives - Nikki Agrawal; Nalini Soni; Vineet Kumar; Leena Preeti Lakra; Meesala Sudhakar; D.S.V.G.K. Kaladhar (Bioresource Technology Reports, 2026)

An endophytic fungus Serendipita indica enhances drought tolerance of pearl millet - Pooja Jangir; Praveen Soni (Plant and Soil, 2026)

Beyond energy production: targeting mitochondrial biogenesis in aging and cancer with phytochemical intervention - Adelene Gan-Yin-Xuen; Soni Thakur; Mohd Adnan; Sreenivasan Sasidharan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Electrostatic-tailored Leciplex system of ketoconazole for boosted ocular pharmacology and cytotoxicity assessment - Shubham Biyani; Mansi Dholakia; Tejal Soni (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Cerebroprotective potential of ceftriaxone against cadmium chloride-induced cerebral inflammatory changes and oxidative insult - Mansi Chaudhary; Prabhat Singh; Surbhi Gupta; Vishal Kumar Biswkarma; Priyadarshini Soni; Lubhan Singh (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Evaluating Nitrogen Solubility from Fertilizers in Sandy Loam Soil Using Core-Ring Soil Extraction Method and Electrical Conductivity Sensors - Caden Wade; Soni Kumari; Younsuk Dong (Journal of Soil Science and Plant Nutrition, 2026)
Understanding fertilizer solubility and nutrient release dynamics is essential for improving nitrogen (N) use efficiency in coarse-textured soils prone to leaching. This study aimed to quantify and compare the dissolution kinetics of urea, diammonium phosphate (DAP) and pelleted poultry manure using a novel core-ring extraction method under controlled moisture condition in sandy loam soil. Fertilizers were incubated for 0.5 to 168 hours, and core (application zone) and surrounding ring soils were separately extracted to quantify N release and mobility. Nutrient mobility was further validated using TEROS 12 electrical conductivity (EC) sensors in layered soil columns. Results indicated that urea had the highest core N release index of 1.8, followed by DAP at 1.1 and poultry manure at 0.3, with statistically significant differences (p < 0.05). Temporal solubility patterns showed rapid urea- N surge in the core from 42.8 to 219.1 mg L -1 within 2 h, followed by outward migration reflected in ring N increasing to 44 mg L -1 by 168 h. DAP released N more gradually from 50.8 to 111.6 mg L -1 by 168 h with minimum lateral diffusion. Poultry manure displayed the slowest release from 20 to 34.1 mg L -1 at 4 h. EC monitoring corroborated with these results, where urea generated a strong EC accumulation in the topsoil (EC response ratio of 2.15 at 48 h), DAP produced localized EC enrichment and poultry manure induced negligible EC change. The integrated core-ring and EC monitoring approach provided a mechanistic understanding of fertilizer solubility pathways and nutrient movement under field moisture conditions.

Engineering Abiotic Stress Tolerance in Plants Using CRISPR Cas: From Molecular Targets to Physiological Resilience - Komal Sharma; Upma Bhatt; Vineet Soni (Journal of Soil Science and Plant Nutrition, 2026)

Seismicity patterns and seismogenic framework for Northeast India: implications for regional hazard assessment - Komal Soni; Daya Shanker (Journal of Seismology, 2026)

Artificial Intelligence-Assisted Detection of Abiotic Stress in Agricultural Crops: Sensors, Computational Models, and Outlook - Komal Sharma; Upma Bhatt; Vineet Soni (Journal of Crop Health, 2026)

Survey on common scab of potato caused by Streptomyces spp. in North Gujarat, India - J. K. Patel; R. S. Jaiman; N. V. Soni; D. M. Zapadiya (Indian Phytopathology, 2026)

Cyanobacteria-coated seeds for improved productivity and seed storability in direct-seeded and transplanted rice - Shreya Kumari; Aditi Tayade; Deepti Varsha; Yashbir Singh Shivay; Sudipta Basu; Sandeep Kumar Lal; Arun Kumar; Preeti Soni; Radha Prasanna (Cereal Research Communications, 2026)

Neuroprotective Efficacy of Silymarin against Oxidative Stress, Inflammation, and Structural Changes Mediated by Arsenic-induced Toxicity in Rats - Annu Verma; Manoj Soni; Vijay Kumar (Indian Journal of Clinical Biochemistry, 2026)

Coenzyme Q: the lipophilic shield against ferroptosis - Sharanya Bhattacharya; Meric Dag; Soni Deshwal (BIOspektrum, 2026)
Coenzyme Q is a lipid first isolated from mitochondrial membranes in 1957. Despite seven decades of extensive study into its role in the electron transport chain, we are still uncovering the mechanisms that govern its transport from mitochondria, intracellular distribution, and functions beyond respiration. Here, we give a brief overview on recent findings on CoQ biology, focusing on its distribution and its role in ferroptotic cell death.

Beyond osmoprotection: the expanding roles of proline in plant signalling and development - Anjali Bhardwaj; Upma Bhatt; Sunita Parihar; Vineet Soni (Biologia Futura, 2026)

Impact of traditional agroforestry systems on biomass and carbon stock for climate change mitigation in the North-Western Indian Himalayas - Kapoor; Bhupender Gupta; Kiran Soni; Ankush Moran; S. Balaji Naik; Sourav Ranjan Mohapatra (Agroforestry Systems, 2026)

Sleep abnormalities in patients with idiopathic intracranial hypertension: a cross-sectional study - Vaishali Sharma; Sucharita Ray; Pramod Avti; Swapnajeet Sahoo; Aastha Takkar; Shiv Lal Soni; Kamalesh Chakravarty (Acta Neurologica Belgica, 2026)

An evolutionary diverse STAT-like protein plays a role in stress response in rice as indicated by bioinformatics analysis - Alka Bishnoi; Hasthi Ram; Praveen Soni (Vegetos, 2026)

Inactivation kinetics for plasmonic photothermal based eradication of ESKAPE and Candida albicans pathogens - Sarabjot Kaur; Parminder Kaur; Rajneesh Dadwal; Hemraj Nandanwar; Sanjeev Soni (Journal of Photochemistry and Photobiology B: Biology, 2026)

Evaluations of PM2.5 forecast during Winter 2020 over India using WRF-SILAM model - Chinmay Jena; Vijay Kumar Soni; Anikender Kumar; Sanjay Bist; Kanika Taneja; Arpit Tiwari; Ananda Kumar Das; D.R. Pattanaik; Sachin D. Ghude; Andreas Uppstu; Rostislav Kouznetsov; Antti Hyvarinen; et al. (Atmospheric Environment, 2026)

Decoding the impact of PAHs on primary and secondary brown carbon light absorption at a semi-urban site in Eastern India - Prerna Thapliyal; Ashish Soni; Apoorvi Sharma; Pratibha Vishwakarma; Tarun Gupta (Atmospheric Pollution Research, 2026)

Comparative Profiling of Discharged Sludge from Two Sewage Treatment Plants: Linking Physico-Chemical Properties and Organic Compounds to Microbial Community Structure - Zakir Ullah Fazli; Kuldeep Soni; Anil Kumar; Ram Chandra (Water, Air, & Soil Pollution, 2026)

Seasonal forecasts of marine heat waves using Monsoon Mission Climate ForecaSt system - Ashish Alone; Ankur Srivastava; Suryachandra A. Rao; Maheswar Pradhan; Geetanjali S.; Aarti Soni; Sudheer Joseph (Theoretical and Applied Climatology, 2026)

Seasonal dynamics and transition patterns of land use land cover in Sher River Basin, Madhya Pradesh (India) - Krishna Kumar Tiwari; Rajan Dev Gupta; Pramod Soni (Environmental Monitoring and Assessment, 2026)

Uncovering candidate protein(s) in murine vaginal lavage fluid linked to sperm-agglutinating Escherichia coli-induced infertility menace: a discovery phase analysis - Ishwerpreet Kaur Jawanda; Thomson Soni; Sunidhi Bhatt; Subhankar Chatterjee; Seema Kumari; Vijay Prabha (Archives of Microbiology, 2026)

Evolutionary and Structural Insights into Proline Metabolism Genes Associated with Salt Resilience in Mango - Laxmi Rastogi; Anju Bajpai; Sumit K. Soni; M. Muthukumar (Biochemical Genetics, 2026)

The combined application of entomopathogenic nematodes and insecticides: A strategy for the management of Holotrichia serrata (Coleoptera: Scarabaeidae) in sugarcane - Aarthi Nekkanti; Jagadeesh Patil; Sonia Soni; Raghubir Kumar Patidar; Priyank Hanuman Mhatre; Manjunatha T. Gowda; Vijaykumar R; B.S. Gotyal; S.N. Sushil (Crop Protection, 2026)

GIS-Based Multi-criteria Flood Risk Assessment Using AHP in the Arpa River Basin, Chhattisgarh - Rahul Kumar Patel; Prasoon Soni; Pushpraj Singh (Journal of the Indian Society of Remote Sensing, 2026)

Deciphering Long-Term Variation of Aerosol Characteristics and Their Climatic Implication over the World’s Wettest Place: Mawsynram - Mamta Devi; Sumit Kumar Mishra; Kartika Pandey; Supreet Kaur; Anikender Kumar; Vijay Kumar Soni; Amarendra Singh; Atul Kumar Srivastva (Journal of the Indian Society of Remote Sensing, 2026)

Two-dimensional transition metal chalcogenides for water and wastewater remediation: a review - S. Singh; R. Soni; P. E. Lokhande; D. Kumar; S. Ghotekar; S. Praveenkumar; K. Singh; N. M. Mubarak; Suhas; R. R. Karri; M. H. Dehghani (International Journal of Environmental Science and Technology, 2026)

Photophysiological dysfunction and growth suppression in freshwater macrophyte Azolla pinnata induced by the emerging anthropogenic UV filter Benzophenone-3 - Dipti Agarwal; Upma Bhatt; Vineet Soni (Ecotoxicology, 2026)

Morphological and photosynthetic responses of Azolla pinnata to bisphenol A - Hari Dev Chaudhary; Upma Bhatt; Vineet Soni (Ecotoxicology, 2026)

Study of Aerosols Optical Depth and Ångström Exponent Over IGP: A Case Study - Pushpendra Singh Soni; Vikram Singh; Alok Sagar Gautam; Amar Deep; Rolly Singh; Alka Gautam; Sneha Gautam; Surendra Pratap Singh (Aerosol Science and Engineering, 2026)

Genome-wide SNP mapping and selective sweep analysis in Indian equine breeds - Anuradha Bhardwaj; Jayakumar Sivalingam; Yash Pal; Varij Nayan; Mamta Chauhan; Sonali Soni; Saroj Panghal; Shiv Kumar Giri; Mohan Malayaperumal; Sarika Jaiswal; Mir Asif Iquebal; Vijay Kumar; et al. (The Nucleus, 2026)

Effect of silage-based diets on growth performance, nutrient digestibility and carcass traits in Avishaan lambs - R.S. Bhatt; Srobana Sarkar; Arvind Soni; Lalit Kumar; M.C. Meena; Arun Kumar (Small Ruminant Research, 2026)

Integrative omics-based biotechnological strategies for deciphering plant stress responses - Maahi Choure; Piyush Kant Rai; Kamlesh Kumar Soni; P.S. Bisen; V. Vivekanand; Vishal Sharma; Aradhana Mishra; Piyush Pandey; Kamlesh Choure (Plant Gene, 2026)

Rainfall extremes variability, teleconnections with atmospheric circulation anomalies in the Indian summer monsoon - Anmol Yadav; G.P. Singh; Pradeep Kumar Rai; Vijay Kumar Soni; Akhilesh Mishra; Sonu Kumar (Dynamics of Atmospheres and Oceans, 2026)

Comparative assessment of WRF-simulated raindrop size distribution using disdrometer observations in Varanasi - Saurabh Maurya; Pramod Soni (Theoretical and Applied Climatology, 2026)

Investigating the interplanetary causes of severe geomagnetic storms during solar cycle 23 using SYM-H and OMNI data - Saket Kumar; Swapnil Garg; Palak Singh Takur; Shrish Lata Soni; O. P. Tripathi (Rendiconti Lincei. Scienze Fisiche e Naturali, 2026)

Crop Suitability Analysis for Cereal Production in Bilaspur, Chhattisgarh, Using the Analytical Hierarchy Process and GIS Techniques - Rahul Kumar Patel; Prasoon Soni; Pushpraj Singh (Journal of the Indian Society of Remote Sensing, 2026)

Weed Management in Fodder Maize Using Herbicides Under Diverse Agro-Climates of India - R. K. Agrawal; Jeetendra Kumar Soni; S. K. Jha; R. V. Kale; Rajesh Kumar; Birendra Kumar; Usha C. Thomas; Subhash Chand; A. K. Roy; A. K. Jha; V. K. Yadav (International Journal of Plant Production, 2026)

Multiple myeloma in adolescents and young adults(AYA): global epidemiological trends, risk factors, and future projections (1990–2040) - Rupayan Kundu; Ankush Mukhopadhyay; Nivedita Sarkar; Niladri Kal; Tuhin Subhra Pal; Kriti Soni; Sudipto Mukherjee (Cancer Causes & Control, 2026)
Introduction Multiple myeloma (MM) is a hematological malignancy with increasing incidence among adolescents and young adults (AYAs) aged 15 to 39 years. This trend presents unique challenges related to long-term treatment effects, fertility, and late-onset complications. Risk factors include obesity, diabetes, environmental exposures, and genetic predispositions, with a higher incidence observed in males and individuals of African-American descent. This study aims to analyze global trends in MM incidence and mortality among AYAs from 1990 to 2021 and project future trends through 2040. Methods Using data from the Global Burden of Disease (GBD) 2021 study, we analyzed the age-specificincidence rate (IR), and death rate (DR) per 100,000 patient-years of AYA MM. Statistical modeling, including two sample t-test were done to estimate the standard deviations among each group, which is plugged into the denominator to compute the statistic. Auto-Regressive Integrated Moving Average (ARIMA) and Exponential Smoothing State Space (ETS) models were applied for projections. Results In 2021, the global AYA MM incidence was 2536 cases (IR 0.09/100,000 patient-years), and deaths totaled 1579 (DR 0.05/100,000 patient-years). From 1990 to 2021, IR and DR increased (annual percentage change (APC) of 0.84 for IR and 0.60 for DR). Males exhibited higher rates and faster increases. High-middle SDI regions had the highest IR and DR, with Mauritius recording the highest national rates. High BMI contributed to 6.52% of MM-related deaths in 2021. Projections indicate rising IR and DR globally through 2040. Conclusion The increasing burden of AYA MM necessitates early detection, targeted treatments, and preventive measures addressing obesity and other modifiable risk factors. Reducing regional disparities through improved healthcare access is essential to mitigate the growing impact of MM.

Comparative analysis of meteorological and air quality variables in urban and semi-urban environments: a case study of Varanasi and Azamgarh - Saurabh Maurya; Pramod Soni; Ashwin Chitravanshi; Prabhankur Prabhankur; Asif Ansari; Abdur Rahman Quaff (Air Quality, Atmosphere & Health, 2026)

Bridging Gaps in Fungal Keratitis Management: Novel Diagnostics, Drug Delivery Systems, and Gene Therapies - Riya Shivgotra; Bindu Soni; Hossamaldeen Bakrey; Parminder Kaur; Subheet Kumar Jain (AAPS PharmSciTech, 2026)

Advancing Sorghum-Based Bioethanol for the Energy Transition Program in Indonesia: Economic and Environmental Aspects - Soni Solistia Wirawan; Agus Sugiyono; Ni Putu Dian Nitamiwati; Palupi Tri Widiyanti; Romelan Romelan; Yayan Heryana; Ana Nurhasanah; Ibrahim Ahmad Ibadurrohman; Fadhlullah Ramadhani; Mokhtar Mokhtar; Andrias Rahman Wimada; Maharani Dewi Solikhah (BioEnergy Research, 2026)

PMVE/MA-based microneedle patches for rapid transdermal delivery of vitamin B12: fabrication and evaluation - Sankalp Saurabh; Dinesh Kumar; Sanjeev Soni (Drug Delivery and Translational Research, 2026)

In silico evaluation of natural opioid ligands interaction and their therapeutic prospects in neuroinflammation - Pratikkumar Gaglani; Shalini Sharma; Atul Srivastava; Vinita Pandey; Vandana Yadav; Soni; Subhashini (In Silico Pharmacology, 2026)

Design Validation of a Developed Six-Stage Cascade Impactor Sampler - Baban Kumar; Prashant Patel; Shankar G. Aggarwal; Khem Singh; Daya Soni; Vijay N. Ojha (Aerosol Science and Engineering, 2026)

Consumer Perception Assessment of Leather Developed Using Discarded Fish Skins - Shubham Soni; Arpita Sharma; K. A. Martin Xavier (Agricultural Research, 2026)

Water quality characteristics and controlling factors of springs in Sirmaur district, North-Western Himalayas, India: a multivariate assessment - Amita Sharma; Satish Kumar Bhardwaj; Neelam Sidhu; Kiran Soni; Pooja Sharma (Environmental Monitoring and Assessment, 2026)

Ecosystem-based assessment of tropical Lobster Sea cage farming impact: A novel BACI-framework for sustainable mariculture expansion along the Northeast coast of Arabian Sea - Mayur Shivdas Tade; Suresh Kumar Mojjada; Abdul Azeez Pokkathappada; Prachi Siddharth Bagde; T.S. Ramshad; Mayank Soni; Aarsha Subramanian; Swathi Lekshmi Perumal Sundaram; Boby Ignatius; Suresh Vettath Raghavan; Achamveetil Gopalakrishnan; Damodaran Nair Divu (Aquaculture, 2026)

Silver nanoparticles and graphene oxide synergistically improves the postharvest life of Narcissus tazetta L., a wild ornamental flower - Himanshi Gupta; Payal Kapoor; Vikas Soni; Bhavya Bhargava (Postharvest Biology and Technology, 2026)

Microbial metabolites–-a sustainable solution for agricultural challenges: A review - Rajat SINGH; Priyanka SONI; Rajul JAIN; Akash CHAUHAN; Rahul KUMAR; Divya GUNSOLA; Sourav CHATTARAJ; Sergio DE LOS SANTOS-VILLALOBOS; Debasis MITRA; Ashish GAUR (Pedosphere, 2026)

Harnessing the synergy of ozone and architecturally engineered carbon materials for environmental remediation - Vatika Soni; Pardeep Singh; Quyet Van Le; Van-Huy Nguyen; Savaş Kaya; Chaudhery Mustansar Hussain; Pankaj Raizada (Journal of Environmental Chemical Engineering, 2026)

Spatio - temporal changes in vegetation dynamics under climate variability and water structures in the Arpa river Basin, Central India - Rahul Kumar Patel; Prasoon Soni; Pushpraj Singh (Theoretical and Applied Climatology, 2026)

Evaluating the therapeutic potential of picrosides in breast cancer cell lines: a systematic scoping review - Deepika Soni; Sasidharan Sivakumar; Saurabh Verma (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Heterologous Expression of OsMADS16 Transcription Factor of Rice Confers Salinity Stress Tolerance in Arabidopsis thaliana - Jyoti Nishad; Soni Chowrasia; Swati Mishra; Alok Kumar Panda; Nirmala Chongtham; Tapan Kumar Mondal (Journal of Plant Growth Regulation, 2026)

Flood-induced in vitro shoot regeneration in Vigna aconitifolia and Lens culinaris using thidiazuron: a novel stress-driven approach - Renu Soni; Gayatri Tripathi (In Vitro Cellular & Developmental Biology - Plant, 2026)

First report of 'Candidatus Phytoplasma citri'-related strain (16srII-C subgroup) associated with little leaf and witches’-broom disease of sunn hemp (Crotalaria juncea) in India - Shobhit Maheshwari; Akshita Soni; Ram Prasad Kushvaha; Sunil Kumar Snehi (Australasian Plant Pathology, 2026)

Infestation intensity drives the mutualism-parasitism shift in Oecophylla smaragdina and Cassia fistula L. - Vineet Soni; Yashwant Sompura; Upma Bhatt (Arthropod-Plant Interactions, 2026)

Dynamic economic emission dispatch in wind-solar plug-in electric vehicles: Equilibrium optimization with arrival-departure constraints and cost estimation precision - Jatin Soni; Kuntal Bhattacharjee (Environment, Development and Sustainability, 2026)

Multifaceted toxicity assessment of di-octyl phthalate on morphology, antioxidant biomarkers, and chlorophyll a fluorescence kinetics of Spirodela polyrhiza - Vineet Soni; Hari Dev Chaudhary; Upma Bhatt (Environmental Sustainability, 2026)

Capsule enclosed coordinate attention based dual batch depthwise convolutional knowledge distillation model for drug-drug interaction prediction - Soni Sharmila Kadimi; S. Thanga Revathi; Pokkuluri Kiran Sree (Molecular Diversity, 2026)

The long-term variability of meteorological parameters at Maitri, East Antarctica station of India - Sunny Chug; V K Soni (Journal of Earth System Science, 2026)

Psycho-socio-economic factors and risk of cardiorenal multimorbidity in middle to older-aged adults: prospective findings from the Canadian longitudinal study on aging - Setor K. Kunutsor; Reyhaneh Rikhtehgaran; Anita Soni (GeroScience, 2026)
Psycho-socio-economic factors (PSEFs) such as income and homeownership may influence the prevalence of cardiorenal multimorbidity (CRM), yet their prospective associations with CRM risk remain unclear. This study aimed to estimate CRM incidence and examine its relationships with multiple PSEFs in a nationally representative Canadian cohort. We analyzed data from 16,557 participants (mean age: 60.4 years; 48.9% men) in the Canadian Longitudinal Study on Aging (CLSA) who were free of CRM at baseline (2010–2015). Incident CRM was defined as the co-occurrence of at least one cardiovascular disease and kidney disease at second follow-up (2018–2021). Survey-weighted multivariable logistic regression estimated odds ratios (ORs) and 95% confidence intervals (CIs) for PSEFs and CRM risk. Over 3–11 years follow-up, 194 participants (1.2%) developed CRM, corresponding to 8.80 per 1,000 individuals (95% CI: 6.77–11.40). CRM incidence increased with age, was higher in men than women (10.63 vs. 7.35 per 1,000), urban than rural residents (9.69 vs. 3.72 per 1,000), and immigrants than non-immigrants (10.87 vs. 8.49 per 1,000). Greater tangible social support reduced CRM risk (OR = 0.65; 95% CI: 0.43–0.97), while depression (OR = 1.68; 95% CI: 1.07–2.65) and PTSD (OR = 3.14; 95% CI: 1.74–5.67) increased risk. In middle- to older-aged Canadian adults, higher social support appears protective, whereas depression and PTSD increase CRM risk. Although incidence was low, CRM burden rose with age and was higher among men, urban residents and immigrants. These findings highlight the importance of psychosocial well-being and social connectedness in preventing CRM and reducing multimorbidity burden in aging populations.

Mitochondrial epigenetic remodeling and integrated stress response induced by microcystin-LR: Experimental evidence and preliminary PP2A structural targeting - Nikita Soni; Apoorva Chouksey; Vikas Gurjar; Kashish Gupta; Rupesh Kumar Srivastava; Ram Kumar Nema; Rajnarayan Tiwari; Pradyumna Kumar Mishra (Toxicon, 2026)

Advances in remote sensing and GIS applications in watershed hydrology: a systematic review - Rahul Kumar Patel; Prasoon Soni; Pushpraj Singh (Journal of Hydrology, 2026)

Magnetically recoverable catalysts and base recycling for sustainable hydrothermal liquefaction of woodchips - Samson O. Akpotu; Swathi Mukundan; Hira Lal Soni; Jonathan L. Wagner (Biomass and Bioenergy, 2026)

Utilization of Genetically Engineered RuBisCO Enzyme for Capturing Carbon Dioxide to Address Environmental Challenges-An Overview - Priya Gupta; Rajkumar Prabhakaran; Nalini Soni; Sangeeta Devendra Kumar Singh; Chinnaperumal Kamaraj; Silambarasan Tamil Selvan; Neethu Asokan; Sudheer D. V. N. Pamidimarri; Balasubramanian Velramar (Water, Air, & Soil Pollution, 2026)

A New Vision for Ocular Disease: Stem Cell Strategies in Regenerative Ophthalmology - Sadhnakumari Chourasiya; Pratixa Patel; G. Santhana Kumar; Arun Soni (Stem Cell Reviews and Reports, 2026)

Quantitative ethnomedicinal survey of indigenous communities in Chhattisgarh, India - Satish Dubey; Ankita Pani; Nagendra Singh Chauhan; Kamal Shah; Akanksha Singh; Shilpa Vinodia; Prasoon Soni; Mery Aradhna Bara; Archana Markam; Satrupa Gond; Ashwini Kumar Dixit (Genetic Resources and Crop Evolution, 2026)

Phytochemical-mediated modulation of cancer-associated proteins: an integrated in-silico and in-vitro study - Manoj Soni; Yangala Sudheer Babu; Mettle Brahma; Vijay Kumar; Mulaka Maruthi; Aastha Sharma; Shikha Nara; Kiran Sura; Mehak Dangi (Natural Product Research, 2025)

Atmospheric pressure waves and seismic signatures of the Hunga Tonga-Hunga Haʻapai eruption in Antarctica - Vivek Kumar; Rahul Kumar; B. Padma Rao; Anand K. Singh; Shailendra Saini; Vijay K. Soni (Polar Science, 2025)

Advances in photoactive g-C3N5 derived Z-and S-scheme heterojunctions for energy and environmental catalysis - Vatika Soni; Tarannum Tarannum; Pardeep Singh; Quyet Van Le; Van-Huy Nguyen; Aftab Aslam Parwaz Khan; Chaudhery Mustansar Hussain; Pankaj Raizada (Journal of Environmental Chemical Engineering, 2025)

Prebiotic potential of selected plants, fruits, vegetables and herbs – An in-vitro study - Prateeksha Bhagwat; Hemant Soni; Gagandeep Singh; Smriti Tandon; Vijay Kumar; Sanjeev Kumar Lale; Cheemalapati Venkata Narasimhaji; Shiddamallayya Mathapati; Narayanam Srikanth; Rabinarayan Acharya (Food and Humanity, 2025)

Genomic insights into plant-microbe interactions - Pushpa Gehlot; Jyoti Yadav; Poonam Meena; Priya Soni; Tripta Jain (Ecological Genetics and Genomics, 2025)

Ultrasound-assisted extraction of bioactive compounds from Litchi chinesis kernel: optimization, bioactivity and antimicrobial study - Jyoti Soni; Parmjit S. Panesar; Avinash Thakur (Bioresource Technology Reports, 2025)

Long term (2003–2023) analysis of Black Carbon aerosols and its impact on cloud characteristics over a highly polluted Delhi mega city of India - Lakshmi; Rashmi Deshwal; Vijay Kumar Soni; Adarsh Kumar (Atmospheric Environment, 2025)

Comparative efficacy of the recently identified entomopathogenic nematode, Steinernema indicum, with other native nematodes against the black cutworm, Agrotis ipsilon (Hufnagel) (Lepidoptera: Noctuidae), in potato crops - Aarthi Nekkanti; Jagadeesh Patil; Sonia Soni; Priyank Hanuman Mhatre; Manjunatha T. Gowda; B.S. Gotyal; S.N. Sushil (Biocatalysis and Agricultural Biotechnology, 2025)

Manuscript Number: WATE-D-25–01270 Veterinary Medicines: An Emerging Threat to Soil, Water, and Plants - Yashwant Sompura; Upma Bhatt; Sunita Parihar; Vineet Soni (Water, Air, & Soil Pollution, 2025)

Restoration of urban degraded soil in the dry tropics: role of multipurpose shrub plants - Amrita Kumari; Priyanka Soni; Fahami Zaya; Rahul Kumar; Riya Gupta; Nandita Ghoshal (Tropical Ecology, 2025)

Assessment of Genetic Variability of Date Palm (Phoenix dactylifera L.) Grown Under Arid Ecosystem of Gujarat, India - Kapil Mohan Sharma; Piyush Verma; Nishit V. Soni; Kapil K. Tiwari; D. A. Baidiyavadra; Mani N. Chaudhari; Bhargav B. Golakiya; P. C. Joshi (Sugar Tech, 2025)

Design, Synthesis and In Vivo Assessment of the Neuroprotective Activity of a Novel Hybrid Conjugate of L-DOPA and Curcumin - Manoj K. Shrivash; K. Amrutha; Sarika Singh; Unnati Soni; Krishna Misra (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2025)

CRISPR/Cas9-Mediated Genome Editing for Abiotic Stress Tolerance in Crops: Current Advances and Future Prospects - Ajithkumar V.; Soni K. B.; Swapna Alex; Anuradha T.; Rehna Augustine; Manju R. V. (Plant Molecular Biology Reporter, 2025)

Role of Mesenchymal Markers in Colorectal Cancer Metastasis - Supriya Soni; Archana Tiwari; Dipanjana Ghosh (Molecular Biology Reports, 2025)

Correction: Sepsis-related immune signature C3 in endometrial carcinoma: implications for prognosis, tumor progression through bioinformatics and experimental validation - Kulsoom; Wajahat Ali; Saleem Ahmad; Irfan Ali Khan; Tanveen Kaur Soni; Asia Masood; Muhammad Omer Iqbal; Valisher Sapayev Odilbek uglu; Mukhayya Xusinovna Djumaniyazova; Anas Sameed Cholavaram; Mubaraq Arisekola Abdulrahmon (Molecular Biology Reports, 2025)

Sepsis-related immune signature C3 in endometrial carcinoma: implications for prognosis, tumor progression through bioinformatics and experimental validation - Kulsoom; Wajahat Ali; Saleem Ahmad; Irfan Ali Khan; Tanveen Kaur Soni; Asia Masood; Muhammad Omer Iqbal; Valisher Sapayev Odilbek uglu; Mukhayya Xusinovna Djumaniyazova; Anas Sameed Cholavaram; Mubaraq Arisekola Abdulrahmon (Molecular Biology Reports, 2025)

The role of plant-derived extracellular vesicles in ameliorating chronic diseases - Ashwani Tiwari; Naveen Soni; Shweta Dongre; Megha Chaudhary; Bhawana Bissa (Molecular Biology Reports, 2025)

Enhanced post-thaw functional characteristics of cryopreserved caprine dermal fibroblasts through adhesion to extracellular matrix proteins - Juhi Pathak; Shiva Pratap Singh; Manisha Pathak; Anjana Goel; Yogesh Kumar Soni; Manoj Kumar Singh (Molecular Biology Reports, 2025)

Characterization of Extracellular Polymeric Substances from Biofilm-Forming Marine Bacteria from the Arabian Sea, India - Madhav Kumar; Riya Soni; Rajiv S. Maniyar; Pooja Saran; Doongar R. Chaudhary (Indian Journal of Microbiology, 2025)

Naturally occurring mutations exist at the functionally important motifs of piperine synthase genes among Piper species - Devika Babu; Srinivasan Asha; K. B. Soni; Swapna Alex; E. V. Soniya; K. N. Anith (Genetic Resources and Crop Evolution, 2025)

Correction to: Synergic effect of biofillers reinforcements and polylactic acid on the mechanical performance of biocomposites for structural applications - Ashish Soni; Murugan Vellaisamy; Dhinakaran Veeman (Clean Technologies and Environmental Policy, 2025)

Optimizing indirect organogenesis and chlorophyll a fluorescence analysis to ensure high survival rate of Capparis decidua under ex vitro conditions - Vineet Soni; Renu Sharma; Upma Bhatt; Yashwant Sompura (In Vitro Cellular & Developmental Biology - Plant, 2025)

Impact of Preharvest Bagging on Fruit Physiology and Quality of Mango (Mangifera indica L.) Under Subtropical Conditions - Dinesh Kumar; K. Kishore; K. K. Srivastava; A. Singh; M. Mishra; P. K. Shukla; T. Damodaran; Sumit K. Soni (Applied Fruit Science, 2025)

Surgical Process Modeling of Workflow and Performance in Image-Guided Bronchoscopy - Tatiana A. Rypinski; Roberto F. Casal; Parvathy S. Pillai; Anshuj Deva; Bhavin Soni; Owais Sarwar; Aaron C. Milhorn; Aaron K. Jones; Gouthami Chintalapani; Gerhard Kleinszig; David E. Ost; Horiana B. Grosu; et al. (Annals of Biomedical Engineering, 2025)

Statistical Surgical Process Modeling: Analysis of Workflow and Performance of Emerging Technologies in Image-Guided Spine Surgery - Anshuj Deva; Tatiana A. Rypinski; Parvathy Sudhir Pillai; Bhavin Soni; Owais Sarwar; Aaron C. Milhorn; Aaron K. Jones; Claudio E. Tatsui; Laurence D. Rhines; Robert Y. North; Christopher Alvarez-Breckenridge; Justin E. Bird; et al. (Annals of Biomedical Engineering, 2025)

Deciphering the relevance of dead box RNA helicases in gliomagenesis and autophagy - Arpit Sharma; Naveen Soni; Megha Chaudhary; Jingyue Jia; Bhawana Bissa (Human Cell, 2025)

Soil organic carbon dynamics in dry tropics: impact of tree plantations on restoration of urban degraded lands - Rahul Kumar; Riya Gupta; Priyanka Soni; Fahami Zaya; Amrita Kumari; Nidhi Singh; Nandita Ghoshal (Environmental Sustainability, 2025)

Therapeutic Potential of Phytocompounds Gentisic Acid and Alpha Resorcylic Acid against Alzheimer’s Disease: A Network Pharmacology, In Silico, and In Vitro Approach - Urvashi Soni; Rohini Pujari (Cell Biochemistry and Biophysics, 2025)

Is lychee-associated encephalopathy in children a straightforward case of toxicity or a complex metabolic and environmental cascade? - Richa Soni; Santasabuj Das; Gopal Shankar Sahni; Dweipayan Goswami; Deepak Verma; Bikash Das; Palak Parmar (Toxicology Letters, 2025)

Plasmonic photothermal based quick sterilization of surgical tools and pathogen suspensions - Sarabjot Kaur; Parminder Kaur; Shobit Attery; Vrushali Raka; Rajneesh Dadwal; Hemraj Nandanwar; Sanjeev Soni (Journal of Photochemistry and Photobiology B: Biology, 2025)

Application of MALDI-TOF MS-based peptidome profiling for the identification of Bacillus cereus, Staphylococcus aureus, and Escherichia coli in single and mixed inoculum - Ying Feng; Aswathi Soni; Gale Brightwell; Marlon M. Reis; Juan Wang; Qingping Wu; Jinxuan Cao; Yu Ding (Food Chemistry, 2025)

Short-term exposure to particulate matter (PM10/2.5) from Varanasi, India led to asthma aggravation and early fibrotic changes in mice model: Insights into its regulation - Diksha Sharma; Payal Singh; Prashant Kumar Chauhan; Vandana Soni; Abhay Kumar Singh; Rashmi Singh (Atmospheric Environment, 2025)

Impact of soil moisture and rainfall variability on soybean crop yield during El Niño episodes in Maharashtra, India - Anil Kumar Soni; Jayant Nath Tripathi; M. Sateesh (Theoretical and Applied Climatology, 2025)

Cryopreservation of bael (Aegle marmelos L.Corr.) using encapsulated axillary buds - E. Deepa; Deepa S. Nair; Swapna Alex; K. B. Soni; M. M. Viji; B. Parvathi (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Role of Fibroblast Growth Factors in Neurological Disorders: Insight into Therapeutic Approaches and Molecular Mechanisms - Shubham Upadhayay; Divya Soni; Maanvi Dhureja; Pooja Temgire; Vishal Kumar; Richmond Arthur; Puneet Kumar (Molecular Neurobiology, 2025)

3D-printed sustainable biocomposites via valorization of biomass: focus on challenges and their future perspectives - Ashish Soni; Sonu Kumar Gupta; Dhinakaran Veeman; Jitendra Kumar Katiyar (Environmental Science and Pollution Research, 2025)
Ineffective management of plastic wastes and biomass is a global concern. The annual generation of plastic waste is around 380 million tonnes, with only 9% being recycled, and the production of biomass is 140 billion metric tonnes. The worry of the environment and demand for sustainability has triggered the configuration of biocomposites as an alternative to conventional materials. 3D printing is a promising technique for the manufacturing of polymer-based composites. The review has integrated 3D printing, utilization of biopolymers, and biomass. The work critically reviewed the various aspects of biocomposites. The characteristics of biocomposites, including processing, fabrication techniques, 3D printing parameters, environmental degradation, and applications, are discussed. The allied works on biocomposites are summarized. The challenges and opportunities of biocomposites are identified. In essence, the review encapsulates the transformative potential of 3D printing with biodegradable plastics and biomass for advancements of biocomposites and accentuates its potential in fostering sustainability. The review has revealed that 3D-printed biocomposites are potent for diverse engineering applications. The biocomposites are economical and eco-friendly and reduce energy consumption and emissions of greenhouse gases. The biomass-based 3D-printed biocomposites have shown comparable mechanical properties to traditional materials. The review revealed that different printing parameters substantially influence the strength, flexibility, crystallinity, and dimensional accuracy of printed parts. The optimization of 3D printing parameters is crucial for the improvement of performance. Biocomposites can overcome the challenges of the linear economy by transforming the wastes into valuable resources.

Synergic effect of biofillers reinforcements and polylactic acid on the mechanical performance of biocomposites for structural applications - Ashish Soni; Murugan Vellaisamy; Dhinakaran Veeman (Clean Technologies and Environmental Policy, 2025)

Comprehensive review on acid dye treatment and sustainability: engineering approaches, AI and ML integration - Kalpana Singh; Shashank Sharma; Shalini Pathak; Sankalp Raghuvanshi; Mohini Singh; Pankaj Mittal; Manglam Soni (Environmental Science and Pollution Research, 2025)

Psycho-socio-economic factors and cardiorenal multimorbidity in middle to older-aged adults: cross-sectional results from the Canadian Longitudinal Study on Aging - Setor K. Kunutsor; Reyhaneh Rikhtehgaran; Anita Soni (GeroScience, 2025)
Psycho-socio-economic factors (PSEFs) such as income, education, housing, and social support are known to influence health outcomes, yet their relationship with cardiorenal multimorbidity (CRM) remains poorly understood. This study aimed to estimate the prevalence of CRM and examine its associations with PSEFs in a large, nationally representative Canadian sample. We analyzed baseline data from 19,370 participants (mean age: 60 years; 49.8% men) in the Canadian Longitudinal Study on Aging, a prospective cohort of community-dwelling adults aged 45–85 years recruited between 2010 and 2015. CRM was defined as the co-existence of at least one cardiovascular disease and kidney disease. PSEFs assessed included household income, education, homeownership, marital status, employment status, and psychosocial variables. Survey-weighted multivariable logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for prevalent CRM. The overall prevalence of CRM was 0.83% (160 individuals), equivalent to 3.90 per 1000 individuals (95% CI 2.81–5.41). Prevalence increased with age and was higher among men than women (4.57 vs. 3.35 per 1000) and slightly higher in rural than urban areas (4.47 vs. 3.84 per 1000). Homeownership was associated with significantly lower odds of CRM (OR = 0.56; 95% CI 0.33–0.94). A household income of $50 K–99 K was associated with lower odds of CRM (OR = 0.63; 95% CI 0.39–1.00). No other PSEFs showed clear associations with prevalent CRM. CRM is relatively uncommon but shows variation by age, sex, and geography. Among the PSEFs assessed, homeownership and, to a lesser extent, moderate income were associated with reduced odds of prevalent CRM. These findings highlight the potential role of housing and economic stability in mitigating CRM risk. Longitudinal studies are needed to assess the impact of PSEFs on the development and progression of CRM over time.

Differential expression of GABARAPs in glioblastoma renders temozolomide sensitivity in a p53-dependent manner - Megha Chaudhary; Naveen Soni; Nargis Malik; Kunzang Chosdol; Bhawana Bissa (Tissue and Cell, 2025)

Functional assessment and comparison of different methods of genomic DNA extraction from fresh ejaculated and cryopreserved caprine sperms for enhanced quality and long-term DNA banking - Shiva Pratap Singh; Juhi Pathak; Manisha Pathak; Ravi Ranjan; Yogesh Kumar Soni; Manoj Kumar Singh (Small Ruminant Research, 2025)

Assessment of CO2 storage potential of a saline aquifer in the Gandhar Field, Cambay Basin, India - Vikram Vishal; David Lall; Yashvardhan Verma; Somali Roy; Upendra Soni; Bharath Shekar; Gaurav Mishra; Om Prakash Sinha; Kaustav Nag; T.N. Singh (Marine and Petroleum Geology, 2025)

Emergence of single atom catalyst and metallic organic frameworks (MOF) derived photocatalytic systems for CO2 conversion into C1 value added products - Anchal Panwar; Vatika Soni; Shabnam Sambyal; Pankaj Raizada; Pardeep Singh; Savas Kaya; Konstantin P. Katin; Vishal Chaudhary; Aftab Aslam Parwaz Khan; Chaudhery Mustansar Hussain; Sonu Sonu (Journal of Environmental Chemical Engineering, 2025)

The secrets of variegated leaves: Molecular to physiological and ecological insights - Anjali Bhardwaj; Dipti Agarwal; Upma Bhatt; Sunita Parihar; Vineet Soni (Flora, 2025)

Assessing the readiness to implement bioethanol-blended fuel in Indonesia - Soni Solistia Wirawan; Hari Setiapraja; Mokhtar; Agus Sugiyono; Ibrahim Ahmad Ibadurrohman; Ni Putu Dian Nitamiwati; Maharani Dewi Solikhah (Biomass and Bioenergy, 2025)

A survey: to identify plant leaf diseases by feature extraction methods and classification techniques - Karan Soni; Rakesh Chandra Gangwar (Planta, 2025)

Functional Pink Pigmented Facultative Methylotrophs from Capsicum frutescens Phyllosphere as Bioinoculants for Growth Promotion and Drought Stress Alleviation in Chilli - P. T. Jasna Sherin; S. Anu Rajan; K. N. Anith; T. Anuradha; K. B. Soni; V. I. Soumya; N. Chitra (Journal of Crop Health, 2025)

Adhesion extracellular matrix proteins improve in vitro cellular and functional properties of enriched caprine adult dermal fibroblast - Juhi Pathak; Shiva Pratap Singh; Manisha Pathak; Vishal Khandelwal; Yogesh Kumar Soni; Manoj Kumar Singh (In Vitro Cellular & Developmental Biology - Animal, 2025)

The critical role of temperature in determining optimal planting schedule for cotton: A review - Menard Soni; Aleksey Y. Sheshukov; Jonathan Aguilar (Agricultural and Forest Meteorology, 2025)

Digisonde based inter-analysis of ionospheric TEC during the major solar eclipse of 8 April 2024 over North/South American sites - Lakshmi; Vijay Kumar Soni; Adarsh Kumar (Advances in Space Research, 2025)

Combined challenges posed by climate change and pollution to river ecosystems: exploring connecting links, hydro-biological impacts and future research approaches - Ashutosh Tripathi-II; Sarojni Rai; Devendra Kumar Soni; Ashutosh Tripathi-I; Poonam Pandey (Environmental Sustainability, 2025)

Rutin Attenuates Virus Entry and Replication and Exerts Neuroprotection in Experimental Models of Japanese Encephalitis - Selamu Kebamo Abate; Rohit Soni; Prasanjit Jena; Arup Banerjee; Debapriya Garabadu (Journal of Neuroimmune Pharmacology, 2025)

Solid nano-structured In-Situ lipoidal dosage form (SNILD): development, optimization, functionality assessment, and In-Vivo data prediction - Mansi Dholakia; Hardik Rana; Dinal Patel; Bhanubhai Suhagia; Tejal Soni (Next Research, 2025)

Multi-source data fusion for soybean origin traceability: Stable isotopes, elemental composition, & volatile organic compounds - Khushboo Soni; Russell Frew; Biniam Kebede (Food Chemistry, 2025)

QbD-driven extraction and purification of piceatannol from passion fruit seeds and its cubosomes development, characterization, and neuronal cellular analysis - Navratan Soni; Sandeep Jat; Ankaj Kumar; Arvind Gulbake; Manini Bhatt; Bodhisatwa Das; Ramkishore Matsa; Pratik Vilas Gore; Dnyaneshwar Maykar; Pramod Kumar (Food Bioscience, 2025)

Characterization of metagenomic diversity of soil sediment from Tattapani hot spring located in Chhattisgarh (India) and application of thermophilic bacteria for agrowaste decomposition - Balram Sahu; Deeppal; Kishan Kumar Raj; Vinay Kumar; Tapas Chowdhury; Ravindra Soni (Ecological Genetics and Genomics, 2025)

Human TLS DNA polymerase: saviors or threats under replication stress? - Yogendra Singh Rajpurohit; Mitu Lal; Dhirendra Kumar Sharma; Ishu Soni (Molecular and Cellular Biochemistry, 2025)

Diagnostic yield of Xpert MTB/RIF, Xpert MTB/RIF Ultra, and Truenat MTB assays on non-pulmonary samples from suspected cases of extra-pulmonary tuberculosis (EPTB) - Anvita Gupta Malhotra; Leena Lokhande; Abhijit Pakhare; Payal Soni; Satya Prakash Vishwakarma; Anand Kumar Maurya; Jitendra Singh; Sarman Singh (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Phytochemical profiling, antioxidant potential and cytotoxic activity of Sargassum prismaticum extracts: implications for therapeutic applications - Sejal Pal; Anjali Soni; Nidhi Patel; Preeti Sharma; Nikhat J. Siddiqi; Sabiha Fatima; Bechan Sharma (Natural Product Research, 2025)

Computational studies of natural product compound (CP-225917) for lead identification - N. S. Hari; NS Hari Narayana Moorthy; Akhilesh Tiwari; Pranay Soni; E. Manivannan; C. Karthikeyan (In Silico Pharmacology, 2025)

An Updated Perspective on Skin Disease Therapy: From Conventional Methods to Nanocarrier Innovations - Riya Shivgotra; Bindu Soni; Parminder Kaur; Anshuka Sharma; Varun Singh; Nitin Partap; Hossamaldeen Bakrey; Subheet Kumar Jain (AAPS PharmSciTech, 2025)

Emerging bismuth stannate semiconductor and its photocatalytic applications in pollutant degradation via Z/S-scheme heterostructures - Tarannum; Vatika Soni; Monika Malhotra; Archana Singh; Vishal Chaudhary; Pardeep Singh; Tansir Aahmad; Savas Kaya; Chaudhery Mustansar Hussain; Pankaj Raizada (Environmental Research, 2025)

Lecanicillium saksenae (Kushwaha) Kurihara and Sukarno, a versatile endophytic entomopathogenic fungus for plant growth promotion in rice (Oryza sativa L.) - P. Shree Naveena; O. P. Reji Rani; P. R. Nithya; R. Beena; K. B. Soni; V. S. Adarsh (World Journal of Microbiology and Biotechnology, 2025)

Emerging therapeutic application of clemastine: a review of recent patents updates - Simran Soni; Ginpreet Kaur (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Rice transcriptomic analysis provides novel insights into T3SS-mediated modulation of plant defense responses by the most virulent Indian race 4 of Xanthomonas oryzae pv. oryzae - M. Amrutha Lakshmi; Aditya Kulshreshtha; Kalyan K. Mondal; N. S. Kalaivanan; Pratap J. Handique; Debashis Borbara; Yuvika Rajrana; Geeta Verma; Ankita Bhattacharya; Kishorekumar Reddy; Madhvi Soni; Thungri Ghoshal; et al. (Journal of Plant Diseases and Protection, 2025)

(CR)4-Targeted Liposomal Doxorubicin as Promising Therapeutic Approach for Breast Cancer Therapy - Sakshi Soni; Ekta Nehra; Puja Panwar Hazari; Anil K. Mishra; Shashank Singh; Sushil K. Kashaw; Vandana Soni (Journal of Pharmaceutical Innovation, 2025)

Revealing genetic diversity, population structure and stability in underutilized wonder legume winged bean (Psophocarpus tetragonolobus (L.) DC.) genotypes of North Eastern Himalayan region - Jeetendra Kumar Soni; Amit Kumar; Jayanta Bora; Simardeep Kaur; B. Lalramhlimi; Lungmuana Singson; S. Doley; V. K. Mishra (Genetic Resources and Crop Evolution, 2025)

Antigenic homology between mouse spermatozoa and Vibrio cholerae: in-silico, in-vitro, and in-vivo evidence for immune-mediated infertility - Thomson Soni; Ishwerpreet Kaur Jawanda; Sunidhi Bhatt; Subhankar Chatterjee; Seema Kumari; Vijay Prabha (Archives of Microbiology, 2025)

Molecular Dissection of Constans (CO) Homologs and Their Regulatory Role in Floral Induction of Mango (Mangifera indica L.) - M. Muthukumar; Anju Bajpai; Kasim Khan; Yashi Bajpai; Sandeep Kumar; Sumit Kumar Soni; Laxmi; V. K. Singh; T. Damodaran (Applied Fruit Science, 2025)

Physico-chemical Dynamics and Incidence of Jelly Seed Disorder in Mangifera indica L. cv. ‘Dashehari’ with Lengthening of Harvesting Time - Rubeena Abbas; Sumit K. Soni; Dinesh Kumar; Abha Singh; Israr Ahmad (Applied Fruit Science, 2025)

A review of biofuels and bioenergy production as a sustainable alternative: opportunities, challenges and future perspectives - Rajat Singh; Ashish Gaur; Priyanka Soni; Rajul Jain; Gaurav Pant; Deepak Kumar; Gaurav Kumar; SZM Shamshuddin; Nabisab Mujawar Mubarak; Mohammad Hadi Dehghani; Suhas; Khalid Ansari (Journal of Environmental Health Science and Engineering, 2025)

Black carbon characterization and its association with meteorological phenomena using network data - Vivek Kumar; Panuganti C. S. Devara; Vijay K. Soni (Environmental Monitoring and Assessment, 2025)

Corrigendum to “Black carbon pollution over India simulated with recent emission inventories and WRF-CHEM model” [Atmospheric Research, 315 (2025) 107931]. - Rahul Sheoran; Sanhita Ghosh; U.C. Dumka; Shubha Verma; D.G. Kaskaoutis; R.E.P. Sotiropoulou; S.D. Attri; V.K. Soni; Suresh Tiwari; Siddharth Singh; Rahesh K. Tiwari (Atmospheric Research, 2025)

Interference for MIPS1 mRNA results in biofortified lablab (Lablab purpureus L.) lines having reduced phytic acid levels - Feba Jacob; Deepu Mathew; K.B. Soni; Swapna Alex; Seeja Thomachan Panjikkaran (Biocatalysis and Agricultural Biotechnology, 2025)

Using mid-infrared spectroscopy to estimate soil microbial properties at the continental scale - Soni Ghimire; Yakun Zhang; Jingyi Huang; Erica L.-W. Majumder; Alfred E. Hartemink; Emily B. Graham; Odeta Qafoku; Joseph Andrews; Zachary B. Freedman (Applied Soil Ecology, 2025)

An Overview of the Design and Realized Performance of Ocean Colour Monitor (OCM-3) Payload On-Board the Oceansat-3 (EOS-06) Mission - Vishnukumar D. Patel; Manoj Kumar; Pradeep Soni; Rahul Dev; Dheeraj Adlakha; Moumita Dutta; Dhrupesh S. Shah; Manoj P. Detroja; Harish Seth; Ashok Kumar; Jimit Gadhia; P. Nandha Kumar; et al. (Journal of the Indian Society of Remote Sensing, 2025)

Physiological responses and early detection of leaf spot disease caused by Alternaria alternata in Ficus religiosa - Upma Bhatt; Haridev Chaudhary; Vineet Soni (Journal of Plant Pathology, 2025)

Isolates of Enterococcus faecalis from freshwater fish being sold in the retail fish markets harbor significantly higher antimicrobial resistance compared to isolates from fish farms - Anil Kumar; Arti Dwivedi; Mayank Soni; Vikash Sahu; Mohd Imran; Chandra Bhushan Kumar; Gaurav Rathore; Uttam Kumar Sarkar (Biologia, 2025)

A comprehensive In-silico analysis of the known and novel synthesized 5-substituted barbituric acid derivatives acting as CNS depressants - Soni Rani; Manisha Behera; Soma Mondal Ghorai; Gagandeep Singh (In Silico Pharmacology, 2025)

Development of food carrying bio-plastic film from banana peels starch incorporated with sugarcane bagasse cellulose - Smita Parekh; Aman Visani; Anjali Soni (Vegetos, 2025)

Morphological and biochemical analysis along with gene expression dynamics in Lilium ‘Brunello’ under supplemented effect of blue and red light treatment in pin tray soil-less cultivation system - Mahinder Partap; H.N. Deekshith; Himanshi Gupta; Gulshan Birsanta; Payal Kapoor; Vikas Soni; Bhavya Bhargava (Journal of Photochemistry and Photobiology B: Biology, 2025)

Upflow anaerobic sludge blanket based full-scale wastewater treatment plant, its performance evaluation and role as a breeding ground of antibiotic resistance determinants - Kuldeep Soni; Ram Chandra (Journal of Environmental Chemical Engineering, 2025)

Development of novel CuMnSe2/ppy hybrid structure for enhancing OER electrocatalytic activity in basic environment - Amisha Soni; Sarvatej Kumar Maurya; Manisha Malviya; Dhanesh Tiwary (Journal of Environmental Chemical Engineering, 2025)

Influence of meteorological variability on aerosol size distribution during the winter fog campaign over Delhi: a case study - A.K. Srivastava; K. Ram; D.S. Bisht; M.P. Raju; V. Singh; V.K. Soni (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Insights into surface ozone variability in India (1980–2014) through CMIP6 model analysis - Arshitha Anand K A; Dilip Ganguly; Sushovan Ghosh; Vijay Kumar Soni; Sagnik Dey (Atmospheric Environment, 2025)

Frogs from the Darjeeling Hill Region, India: Elucidation of their morphology and habitat - Kumaresh Mandal; Shishir Tamang; Soni Subba; Divya Rai; Saptaparni De; Aditya Pradhan; Kaushik Deuti; Gyaneshwer Chaubey; Rakesh Tamang (Proceedings of the Zoological Society, 2025)

Air Quality Analysis in Desert Region in the Northern State of India: GIS Based Approach - Vignesh Mohan; Rajeev Kumar Mishra; Vijay Kumar Soni (Journal of the Indian Society of Remote Sensing, 2025)

Enzymatic degradation of PET by hydrolase from Brucella intermedia IITR130 and its genomic insights - Pallavi Srivastava; Saurabh Singh; Mohini Soni; J. Venkatesh Pratap; Srikrishna Subramanian; Natesan Manickam (Biodegradation, 2025)

Soil Attributes Modulate the Fungal Population and Diversity of Phytopathogens and Biocontrol Agents - Isha Verma; Sumit K. Soni; Rahul Kumar; Bhavya Priyadarshini Mishra; Udit Yadav; Anshu anshu; Touseef Fatima; Sanjeeva Nayaka; Mariya Naseem; Suchi Srivastava; Poonam C. Singh (Agricultural Research, 2025)

A longitudinal study comparing the impact of pesticide exposure on cognitive abilities of Latinx children from rural farmworker and urban non-farmworker families - Monica Soni; Haiying Chen; Milton J. Cepeda; Lesley Berenson; Sydney Smith; Kim A. Anderson; Sara A. Quandt; Thomas A. Arcury; Paul J. Laurienti; Jonathan H. Burdette (Neurotoxicology and Teratology, 2025)

Utilisation of pumpkin seed (Cucurbita maxima) as a meat matrix preservative: Influence on colour and lipid stabilities - Yogesh P. Gadekar; Gauri Jairath; Arvind Soni; R.S. Bhatt; B.S. Yashavanth; Eric N. Ponnampalam (Meat Science, 2025)

Potential and challenges of desalination technologies for arid and semiarid regions: A comprehensive review - Simran Soni; Manoj Kumar Jindal; Pradip Kumar Tewari; Vikky Anand (Desalination, 2025)

Temporal and Spatial Variations in Lightning Activity and Meteorological Parameters Across the Indian Himalayan Region and Indo-Gangetic Plains - Rolly Singh; Vikram Singh; Alok Sagar Gautam; Sanjeev Kumar; Karan Singh; Pushpendra Singh Soni; Alka Gautam; Sneha Gautam (Asia-Pacific Journal of Atmospheric Sciences, 2025)

Tumor heterogeneity in retinoblastoma: a literature review - Rani Pallavi; Bihari Lal Soni; Gaurab Kumar Jha; Shalini Sanyal; Azima Fatima; Swathi Kaliki (Cancer and Metastasis Reviews, 2025)

Exploring carbon neutrality in supply chains: A critical factor analysis using fuzzy delphi and fuzzy cognitive methods - Paras Garg; Gunjan Soni; Madhuri Jain; Sachin Kumar Mangla; Ved Prabha Toshniwal; Rakesh Jain (Journal of Cleaner Production, 2025)

Selective extraction of uranium from nitric acid leachate of Minjingu rock phosphate - Raghav S. Soni; Hitarth K. Thakkar; Nils H. Haneklaus; Dennis A. Mwalongo; Ashwin W. Patwardhan; Pushpito K. Ghosh (Hydrometallurgy, 2025)

Advances in photocatalytic hydrogen production with ZnO/ZnS-Based nanostructured materials - Parul Rana; Vatika Soni; Rohit Kumar; Sonu; Akshay Chawla; Aftab Aslam Parwaz Khan; Pardeep Singh; Sourbh Thakur; Pankaj Raizada; Khalid A. Alzahrani (Fuel, 2025)

Black carbon pollution over India simulated with recent emission inventories and WRF-CHEM model - Rahul Sheoran; Sanhita Ghosh; U.C. Dumka; D.G. Kaskaoutis; R.E.P. Sotiropoulou; S.D. Attri; V.K. Soni; Suresh Tiwari; Sidharth Singh; Rakesh K. Tiwari (Atmospheric Research, 2025)

Field validation of brown carbon absorption dependence on acidity and aerosol liquid water content - Prerna Thapliyal; Ashish Soni; Tarun Gupta (Atmospheric Research, 2025)

Nitrogen and Sulfur Co-doped Lantana Camara Derived Carbon Material for Detection of Hg2+ Ions in Contaminated Water - Abhishek Soni; Neeraj Gupta (Water Conservation Science and Engineering, 2025)

Correction: AM-UNet: Road Network Extraction from high-resolution Aerial Imagery Using Attention-Based Convolutional Neural Network - Yashwant Soni; Uma Meena; Vikash Kumar Mishra; Pramod Kumar Soni (Journal of the Indian Society of Remote Sensing, 2025)

Unveiling genetic diversity and population structure for nutraceutical and grain ionome profile in traditional rice cultivars - S. Anadhu; R. L. Visakh; R. P. Sah; K. B. Soni; Swapna Alex; R. V. Manju; R. Beena (Genetic Resources and Crop Evolution, 2025)

Quality by design driven development of lipid nanoparticles for cutaneous targeting: a preliminary approach - Viral Patel; Tejal Mehta; Jigna Shah; Kinal Soni (Drug Delivery and Translational Research, 2025)

Lithospheric plane strain deformation due to tensile faulting - Nirmal Soni; Sunita Rani; Neeru Bala (Earthquake Engineering and Engineering Vibration, 2025)

Response of Bioformulations and Inorganic Fertilizers for Productivity, Quality, and Soil Microbial Activity of Banana in the Subtropics - Dinesh Kumar; Govind Kumar; K. K. Srivastava; Vinod Kumar Singh; Sumit K. Soni (Applied Fruit Science, 2025)

Impact of Weather Changes on the Phenostages and Flowering Times of Mango (Mangifera indica L.) - Yashi Bajpai; Anju Bajpai; Sumit K. Soni; Laxmi Rastogi; Mala Trivedi (Applied Fruit Science, 2025)

A rapid estimation of intra-row weed density using an integrated CRM, BTSORT and HSV model across entire video stream of chilli crop canopies - Prakhar Patidar; Peeyush Soni (Crop Protection, 2025)

A high resolution multipollutant assessment of health damages due to the onroad sector in Boston, Massachusetts - Manish Soni; Saravanan Arunachalam; M.V.S. Ramarao; Christos I. Efstathiou; Christopher Rick; Laura Buckley; C. Dinesh; Mary Willis; Frederica Perera; Patrick Kinney; Jonathan I. Levy; Jonathan Buonocore (Science of The Total Environment, 2025)

Identifying the causal agent of floral malformation as Fusarium complex using metagenomic and metabolomic approaches - M. Muthukumar; Anju Bajpai; Sumit K. Soni; Sanjay Kumar Singh; Yashi Bajpai; Sandeep Kumar; Laxmi (Physiological and Molecular Plant Pathology, 2025)

Indexing economic performance of energy security towards alternative sustainable strategies and reforming policies: The evidence from Indian rural segment - Vivek Soni; Pooja Sharma; Aarti Singh; Ambika Prasad Dash; Prasanta Kumar Dey (Next Research, 2025)

Genome-wide identification, in-silico characterisation and expression analysis of multiprotein bridging factor 1 gene family members in rice - Alka Bishnoi; Hasthi Ram; Praveen Soni (Plant Physiology Reports, 2025)

Advancing polar prediction: Enhancing short-range forecasting accuracy with Polar WRF at Bharati and Maitri stations in Antarctica - Anikender Kumar; Vivek Kumar; Anand Kumar Das; Shivani Rawat; Chinmay Kumar Jena; Sanjay Bist; Vijay Kumar Soni; D S Pai (Journal of Earth System Science, 2025)

Loganic Acid Alleviates the Olfactory-Brain NLRP3 Inflammasome Activation and Rescues Dopaminergic Neurons in Experimental Models of Parkinson’s Disease - Samir Ranjan Panda; Pallabi Panja; Meenakshi Singh; Ujjawal Soni; Bishal Rajdev; Pankaj Garg; Sharad D. Pawar; Rabinarayan Acharya; Anagha Ranade; V. G.M Naidu (Journal of Neuroimmune Pharmacology, 2025)

Recent updates on full solar spectrum metal sulphides photocatalyst for hydrogen peroxide generation: Modification strategies and mechanistic insights - Vatika Soni; Monika Malhotra; Pardeep Singh; Aftab Aslam Parwaz Khan; Wafa A. Bawazir; Van-Huy Nguyen; Tansir Ahamad; Quyet Van Le; Pankaj Raizada; Khalid A. Alzahrani (Journal of Environmental Chemical Engineering, 2025)

High-throughput, rapid, and non-destructive detection of common foodborne pathogens via hyperspectral imaging coupled with deep neural networks and support vector machines - Ying Feng; Marlon M. Reis; Christine Tu; Aswathi Soni; Gale Brightwell; Moutong Chen; Jumei Zhang; Juan Wang; Qingping Wu; Yu Ding (Food Research International, 2025)

Postharvest integration of prickly pear betalain-enriched gummies with different sugar substitutes for decoding diabetes type-II and skin resilience - in vitro and in silico study - Deepak Mehta; Kritika Kuksal; Abhilasha Sharma; Neha Soni; Supriti Kumari; Shivraj Hariram Nile (Food Chemistry, 2025)

Integrated supply chain optimization model for sorghum-based bioethanol industry on a small scale: Case study in East Java Province, Indonesia - Soni Solistia Wirawan; Agus Sugiyono; Ni Putu Dian Nitamiwati; Palupi Tri Widiyanti; Romelan Romelan; Yayan Heryana; Ana Nurhasanah; Maharani Dewi Solikhah (Bioresource Technology Reports, 2025)

Identification of aerosol and meteorological parameters threshold for visibility conditions over Delhi city - Prachi Goyal; Chinmay Jena; Anikender Kumar; V.K. Soni; Mrutyunjay Mohapatra (Atmospheric Pollution Research, 2025)

Theranostic Near-Infrared Monoamine Oxidase Inhibitor (NMI) Protein Binding Interactions with MAOA and Albumin - Ronald W. Irwin; Unnati H. Shah; Shivani Soni; Heinz Josef Lenz; Jean C. Shih (Pharmaceutical Research, 2025)
Purpose The protein binding interactions of near-infrared monoamine oxidase inhibitor (NMI) are reported here. Methods NMI-bound proteins were examined by fluorescent SDS-PAGE and mass spectrometry using tumor tissues from brain and colon cancer mouse models. Results This study shows protein interactions with NMI, a chemical conjugate of MAOA inhibitor clorgyline and tumor-seeking dye, MHI-148. NMI fluorescence in MAOA knock-out (KO) mice was significantly lower compared to WT mice, including whole animal, organs, and tissue lysates which indicated that NMI binds to MAOA. Pure recombinant MAOA protein was detectable as a single fluorescent band that migrated at ~ 65kD. NMI inhibited MAOA activity (IC 50 1–5 µM). In a glioma mouse model, NMI targeted specifically to tumor with high contrast to adjacent normal brain, shown by a 65 kD protein band. Recent studies demonstrated heptamethine cyanine dyes (e.g., MHI-148) interact with serum albumin, contributing to tumor uptake and cancer cell internalization. Our study shows NMI binds to albumin but highly prefers MAOA, providing a plausible mechanism for systemic drug delivery via serum albumin to the tumor target and subsequent MAOA inhibition. Further studies in a colon cancer mouse model found the ~ 65 kD SDS-PAGE band, bound to NMI, contained both MAOA and albumin proteins by mass spectrometry. Conclusion NMI was shown to interact with MAOA and the blood carrier protein, albumin. This study provides insights for drug delivery and protein target specificity of NMI to image and treat cancer.

Unraveling the treasure trove of phytochemicals in mitigating the Salmonella enterica infection - Saurabh Soni; Lokesh Gambhir; Gaurav Sharma; Asha Sharma; Neha Kapoor (Folia Microbiologica, 2025)

Characterization, Bio-Prospection, and Comparative Metagenomics of Bacterial Communities Revealing the Predictive Functionalities in Wild and Cultured Samples of Industrially Important Red Seaweed Gracilaria dura - Doniya Elze Mathew; Aastha Soni; Asmita Dhimmar; Apexa Gajjar; Ashutosh Shankar Parab; Sumit Sudhir Phakatkar; Harshal Sahastrabudhe; Cathrine Sumathi Manohar; Pramod B. Shinde; Vaibhav A. Mantri (Current Microbiology, 2025)

Enhanced production of phenylpropanoid glycosides from in vitro cultures of Artanema sesamoides Benth - Elizabeth Jose; Soni K. B.; Ancy Joseph; Swapna Alex; Deepa S. Nair (In Vitro Cellular & Developmental Biology - Plant, 2025)

Sub‐centennial upper water column structure variability of the tropical Indian Ocean since the Last Glacial Maximum - Soni Rai; D. P. Singh; R. Saraswat; A. S. Maurya (Journal of Quaternary Science, 2025)
The upper water column (UWC) is involved in the worldwide distribution of heat and nutrients. However, global warming is expected to alter the UWC structure due to temperature‐ and precipitation‐induced stratification. This impact of global warming is comparatively more pronounced in the Indian Ocean. Therefore, to understand the fate of the UWC structure in the future, it is important to comprehend its past variability in the Indian Ocean. To achieve this, we have reconstructed sub‐centennial scale variations in the UWC structure of the tropical central Indian Ocean by using the isotopic composition (δ 18 O and δ 13 C) of surface‐dwelling planktic foraminifera Globigerinoides ruber and subsurface‐dwelling Neogloboquadrina dutertrei . The difference in the isotopic composition of the surface‐ and subsurface‐dwelling species (Δδ 18 O r‐d and Δδ 13 C r‐d ) was used to understand the UWC structure variability in the tropical central Indian Ocean. We report a deeper mixed layer and thermocline during the last glacial period, followed by a shoaling of the thermocline during the glacial–interglacial transition. The thermocline also deepened during intense boreal summer monsoon events such as in the Bølling–Allerød and early Holocene. Our findings suggest that the tropical Indian Ocean UWC is influenced primarily by the intensity of the monsoon winds. From the comparison of our record with those of the eastern and western Indian Ocean, it is evident that a similar climatic forcing governed the central and eastern regions during the last glacial–interglacial period.

Temporal Trends of Dry Spells in Indian Meteorological Subdivisions During Southwest Monsoon 1951–2023 - Anil Kumar Soni; Jayant Nath Tripathi (International Journal of Climatology, 2025)
Amidst the backdrop of climate change, the monsoon rainfall pattern is experiencing alterations over time. A precise evaluation of monsoon rainfall distribution throughout the season is crucial for effective water management in agriculture, conducting drought assessments, and evaluating associated risks. Our study focused on analysing dry and wet spells within the Indian meteorological subdivisions over the past 73 years (1951–2023). It examines the spatial distribution of southwest monsoon rainfall and dry days, revealing a correlation between limited rainfall and extended dry periods, especially noticeable in regions like Western Rajasthan and Jammu & Kashmir. Vulnerability to drought is evident in regions with moderate monsoon rainfall and a high frequency of dry days. The study reveals that 65% of meteorological subdivisions experience over 60 dry days during the monsoon season, underscoring the need for a detailed analysis of dry day patterns. July and August are vital for Indian agriculture, as crop growth relies on consistent monsoonal rainfall; extended dry spells during this period cause moisture stress, affecting key stages like flowering and grain filling. The study reveals an alarming trend, with 44% of meteorological subdivisions showing an increase in dry days during August, and 29% exhibiting a similar trend for the overall monsoon season. The study also investigated the relationship between dry days and ENSO events, finding that Central and Northwest India are predominantly affected by moderate to strong events, resulting in a high probability of increased dry days. This increase in dry spells, driven by shifts in monsoon variability and intensity, reduces water availability during the growing season and raises the risk of crop failure. These findings emphasise the importance of implementing effective mitigation strategies to address the challenges posed by prolonged dry spells and their detrimental impact on crop yields.

Ziziphus nummularia and Acacia nilotica leaves based polyphenols rich diet modulates fatty acid profile and keeping quality of lamb meat - G.N. Aderao; A. Sahoo; R.S. Bhatt; L.K. Soni; Y.P. Gadekar; P.K. Kumawat (Small Ruminant Research, 2025)

Alcan-based adsorption: Mitigating phosphate pollution in subsurface drainage water - Soni Kumari; Younsuk Dong (Journal of Water Process Engineering, 2025)

Innovative approaches to chemical recycling of polyethylene terephthalate waste: Investigating key components and their emerging applications - Neha Mittal; Rakesh Kumar Soni; Meenu Teotia (Journal of Environmental Management, 2025)

MOFs-based S-scheme heterojunction photocatalysts: Challenges and prospects to break the selectivity limitation forintensified C1 products in CO2 photoreduction - Monika Malhotra; Vatika Soni; Rohit Kumar; Tarannum; Pardeep Singh; Sourbh Thakur; Quyet Van Le; Lan Huong Nguyen; Van-Huy Nguyen; Pankaj Raizada (Chemical Engineering Journal, 2025)

AM-UNet: Road Network Extraction from high-resolution Aerial Imagery Using Attention-Based Convolutional Neural Network - Yashwant Soni; Uma Meena; Vikash Kumar Mishra; Pramod Kumar Soni (Journal of the Indian Society of Remote Sensing, 2025)

Micrococcus luteus, an emerging opportunistic pathogen in farmed Nile tilapia, Oreochromis niloticus in Andhra Pradesh, India - Kummari Suresh; Devika Pillai; Mayank Soni; Srinu Rathlavath; Daggula Narshivudu (Aquaculture International, 2025)

Native entomopathogenic nematodes (Steinernematidae and Heterorhabditidae) provide effective biocontrol against Oriental leafworm moth, Spodoptera litura (Fabricius) (Lepidoptera: Noctuidae) in cabbage - Aarthi Nekkanti; Jagadeesh Patil; Sonia Soni; Gotyal B S; Manjunatha T. Gowda; Jayalaxmi Ganguli; S.N. Sushil (Rhizosphere, 2024)

The enigma of mitochondrial epigenetic alterations in air pollution-induced neurodegenerative diseases - Sayanti Acharyya; Sruthy Hari Kumar; Apoorva Chouksey; Nikita Soni; Nazim Nazeer; Pradyumna Kumar Mishra (NeuroToxicology, 2024)

Base metals (Ni, Cu, Zn, Fe) oxide nanomaterials mediated photo/sono-catalytic removal of emerging pharmaceutical contaminants from wastewater - Savita Soni; Anjali Kumari; Sonika Kumari; Ajay Sharma; Vivek Sheel; Shashi Kant Bhatia; Anil Kumar Sharma (Journal of Environmental Chemical Engineering, 2024)

Vertical Profiles of Black Carbon and Associated Radiative Properties over India: Inter-comparison of Measured and Reanalysis Data - Ashish Soni; Pawan S. Soyam; Mahen Konwar; Neelam Malap; Pramod Safai; Thara Prabhakaran (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Additive manufacturing in the food industry: Innovations in customised fabrication and personalised nutrition - Madhvi Sharma; Pratibha Parihar; Alok Dhar Dubey; Shiv Shankar Shukla; Rahul Soni (Food and Humanity, 2024)

Concentration of particulate matter and atmospheric pollutants in the residential area of Kathmandu Valley: A case study of March–April 2021 forest fire events - Jasmita Khadgi; Karuna Kafle; Geeta Thapa; Soni Khaitu; Chandan Sarangi; David Cohen; Hemu Kafle (Environmental Pollution, 2024)

Phenology Model of Oil Palm Plantation Based on Biophysical Parameter on Sentinel-1A Using Multiple Linear Regression (MLR) - Rika Hernawati; Ketut Wikantika; Soni Darmawan; Agung Budi Harto; Josaphat Tetuko Sri Sumantyo; Sitarani Safitri (Journal of the Indian Society of Remote Sensing, 2024)

Nanotechnology in Agriculture: Enhancing Crop Productivity with Sustainable Nano-Fertilizers and Nano-Biofertilizers - Sanjeev Kumar Soni; Sakshi Dogra; Apurav Sharma; Bishakha Thakur; Jyoti Yadav; Aishwarya Kapil; Raman Soni (Journal of Soil Science and Plant Nutrition, 2024)

Metagenomic Analysis Reveals the Complex Microbial Landscape of Market Chicken Meat - Pranav Anjaria; Prakash Koringa; Prakrutik Bhavsar; Manasi Soni; Mansi Desai; Jitendrakumar Nayak; Somak Chowdhury; Kamlesh Jangid; M. N. Brahmbhatt (Indian Journal of Microbiology, 2024)

Stable isotopic, bulk, and molecular compositions of post-monsoon biomass-burning aerosols in Delhi suggest photochemical ageing during regional transport is more pronounced than local processing - Rishu Agarwal; Shankar Gopala Aggarwal; Bhagawati Kunwar; Dhananjay Kumar Deshmukh; Khem Singh; Daya Soni; Kimitaka Kawamura (Journal of Atmospheric Chemistry, 2024)

Variability among the populations (F2:3and BC1F2) developed for Fusarium wilt and Watermelon Bud Necrosis Virus (WBNV) combined resistance in watermelon - Shruti Soni; D.C. Manjunathagowda; P.K.S. Gurjar; D.C. Lakshmana Reddy (Vegetos, 2024)

Epidemiological investigation of equine rotavirus B outbreaks in horses in central Kentucky - Chithra C. Sreenivasan; Ahsan Naveed; Tirth Uprety; Shalini Soni; Olivia Jacob; Emma Adam; Dan Wang; Feng Li (Veterinary Microbiology, 2024)

A review on e-waste contamination, toxicity, and sustainable clean-up approaches for its management - Pankaj Kumar; Snigdha Singh; Amel Gacem; Krishna Kumar Yadav; Javed Khan Bhutto; Maha Awjan Alreshidi; Manoj Kumar; Anand Kumar; Virendra Kumar Yadav; Sunil Soni; Ramesh Kumar; Maytham T. Qasim; et al. (Toxicology, 2024)

Fluoride removal using a rotating anode electro-coagulation reactor: Parametric optimization using response surface methodology, isotherms and kinetic studies, economic analysis and sludge characterization - Ram Raj Meena; Raj Mohan Singh; Pramod Soni; Rishi Kumar; Sushil Kumar (Journal of Environmental Management, 2024)

Modeling the plasma composition of 67P/C-G at different heliocentric distances - Sana Ahmed; Vikas Soni (Icarus, 2024)

UVSSA facilitates transcription-coupled repair of DNA interstrand crosslinks - Rowyn C. Liebau; Crystal Waters; Arooba Ahmed; Rajesh K. Soni; Jean Gautier (DNA Repair, 2024)

Bioremediation of Arsenic and Cadmium by Metal-Resistant Bacteria in Spinach - Basant Ram; Hari Narayan; Dayashankar Baghel; Anup Kumar Singh; Tapas Chowdhury; K. Tedia; Deep Chandra Suyal; Ravindra Soni (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2024)

Phytoactive drugs used in the treatment of Alzheimer’s disease and dementia - Anshita Gupta Soni; Astha Verma; Renjil Joshi; Kamal Shah; Deependra Soni; Chanchal Deep Kaur; Swarnlata Saraf; Nagendra Singh Chauhan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Fe-doped nano-cobalt oxide green catalysts for sulfoxidation and photo degradation - Atul Soni; Minaxi S. Maru; Parth Patel; Jagriti Behal; Deepika Kaushal; Manish Kumar; Maheshwar S. Thakur; Sunil Kumar (Clean Technologies and Environmental Policy, 2024)

Greener and sustainable fabrication of DNA/RNA base-pair conjugates by [CuO[HN(C2H5)3[Al2Cl7] nanocatalyst: Emerging drug against prostate cancer - Parveen Kumar; Akta Soni; Vijesh Tomar; Tejveer Singh; Meena Nemiwal (Sustainable Chemistry and Pharmacy, 2024)

Empowering sustainability: Charting the seven years of progress in g-C₃N₄ based materials and their crucial role in building a greener future - Shivani Soni; Sunita Teli; Pankaj Teli; Shikha Agarwal (Sustainable Chemistry and Pharmacy, 2024)

Estimating black carbon levels using machine learning models in high-concentration regions - Pratima Gupta; Pau Ferrer-Cid; Jose M. Barcelo-Ordinas; Jorge Garcia-Vidal; Vijay Kumar Soni; Mira L. Pöhlker; Ajit Ahlawat; Mar Viana (Science of The Total Environment, 2024)

Air pollution-linked epigenetic modifications in placental DNA: Prognostic potential for identifying future foetal anomalies - Sruthy Hari Kumar; Sayanti Acharyya; Apoorva Chouksey; Nikita Soni; Nazim Nazeer; Pradyumna Kumar Mishra (Reproductive Toxicology, 2024)

A comprehensive review on microalgal chromium detoxification in tannery wastewater: Paving the way for biobased products - Pragati Verma; Vandana Sirotiya; Rishabh Rathore; Avishek Kumar; Anshuman Rai; Urvashi Soni; Mohammad Khalid; Krishna Kumar Yadav; Vandana Vinayak (Process Safety and Environmental Protection, 2024)

Unravelling the molecular dimensions of atmospheric Micro(nano)Plastics: Exploring potential impacts on human health and strategies for detection - Nazim Nazeer; Arpit Bhargava; Nikita Soni; Rajnarayan Tiwari; Pooja Ratre; Pradyumna Kumar Mishra (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Numerical modeling and failure analysis of caisson foundations subjected to the monotonic lateral loads - Bilal Ahmad Malik; Pranjal Mandhaniya; Anish Kumar Soni; Zhongkun Ouyang (Ocean Engineering, 2024)

Feature fusion-based food protein subcellular prediction for drug composition - Haewon Byeon; Mohammad Shabaz; Janjhyam Venkata Naga Ramesh; Ashit Kumar Dutta; Richa Vijay; Mukesh Soni; Jagdish Chandra Patni; Maher Ali Rusho; Pavitar Parkash Singh (Food Chemistry, 2024)

Recent advances in manipulating strategies of NH2-functionalized metallic organic frameworks-based heterojunction photocatalysts for the sustainable mitigation of various pollutants - Balvinder Kaur; Vatika Soni; Rohit Kumar; Pardeep Singh; Rangabhashiyam Selvasembian; Archana Singh; Sourbh Thakur; Aftab Aslam Parwaz Khan; Savas Kaya; Lan Huong Nguyen; Van-Huy Nguyen; Pankaj Raizada (Environmental Research, 2024)

Channel planform dynamics using earth observations across Rel river, western India: A synergetic approach - Keval H. Jodhani; Dhruvesh Patel; N. Madhavan; Utsav Soni; Haard Patel; Sudhir Kumar Singh (Spatial Information Research, 2024)

Design and Critical Characterization the Pharmaceutical Cocrystal of Azelnidipine With Coformers for Boosting Physicochemical Properties - Vishva Chauhan; Rajnikant Mardia; Mehul Patel; Bhanu Suhagia; Tejal Soni (Journal of Pharmaceutical Innovation, 2024)

Crosstalk between gut–brain axis: unveiling the mysteries of gut ROS in progression of Parkinson’s disease - Divya Soni; Shubham Upadhayay; Maanvi Dhureja; Richmond Arthur; Puneet Kumar (Inflammopharmacology, 2024)

Investigation of radioactivity and heavy metal levels in soil samples from neutral and vegetation land of Punjab, India - Sanjeet S. Kaintura; Swati Thakur; Sarabjot Kaur; Soni Devi; Katyayni Tiwari; Priyanka; Arzoo Sharma; Pushpendra P. Singh (Environmental Monitoring and Assessment, 2024)

Estimation of regression relation between velocity of shear wave and depth: A contribution towards mitigating seismic hazard in Bilaspur and Hamirpur districts of Himachal Pradesh - Jyoti Singh; Anand Joshi; Saurabh Sharma; Mohit Pandey; Sandeep Singh; Rajeev Soni; Satvinder Singh (Journal of Earth System Science, 2024)

Selection of sustainable construction material from recycled waste plastics by q-rung orthopair fuzzy SWARA-MABAC approach - Ashish Soni; Sayanta Chakraborty; Pankaj Kumar Das; Apu Kumar Saha (Chemosphere, 2024)

Comprehensive insights into the impact of oil pollution on the environment - Komal Sharma; Garishma Shah; Khushbu Singhal; Vineet Soni (Regional Studies in Marine Science, 2024)

Sulfide-enhanced carboxymethyl cellulose stabilised nano zero-valent iron for chromium(VI) mitigation in water: Evidence from batch and column studies - B. Prathima; Vikram Srinivasa Raghvan; Swati Soni; Sai Siva Gorthi; Sivakumar Babu G.L. (Journal of Water Process Engineering, 2024)

Design and multiphysical modeling of SMA-driven bi-stable structures with efficient energy consumption - Ali Saeedi; Hyunchul Kwon; Priyank Soni; Benjamin Dillenburger; Moslem Shahverdi (Engineering Structures, 2024)

Harnessing agricultural waste: A sustainable approach to lignocellulolytic enzymes production - Neha Rani; Bishakha Thakur; Riya Dutt; Aishwarya Kapil; Raman Soni; Sanjeev Kumar Soni (Bioresource Technology Reports, 2024)

Differences in oxidoreductase activity of cytochromes bd-I and bd-II oxidases from Mycobacterium smegmatis and Cryo-EM structure of cyt. bd-II - Mateusz Janczak; Terezia Kovalova; Ana Gamiz Hernandez; Dan Sjöstrand; Soni Sharma; Ville Kaila; Martin Högbom; Pia Ädelroth (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Silencing of Coat Protein Gene Using IhpRNA Develops Resistance to Banana Bract Mosaic Virus in Musa Acuminata (AAA) cv. Grand Naine - Pritam Ramesh Jadhav; Sachin Chandrakant Ekatpure; K. B. Soni; Alex Swapna; R. S. Lekshmi; Yogesh Sahebrao Wagh; R. V. Manju (Tropical Plant Biology, 2024)

Phytotelmata as Mosquito Breeding Sites in the Darjeeling Himalayas: A Proximate Assessment - Shishir Tamang; Soni Subba; Rakesh Tamang (Proceedings of the Zoological Society, 2024)

Assessment of thermal damage for plasmonic photothermal therapy of subsurface tumors - Amit Kumar Shaw; Divya Khurana; Sanjeev Soni (Physical and Engineering Sciences in Medicine, 2024)

An analytical comparison of two versions (US EPA and BIS) of pararosaniline method used for monitoring of ambient SO2 - Rishu Agarwal; Shankar G. Aggarwal; Daya Soni; Khem Singh (Air Quality, Atmosphere & Health, 2024)

Coexistence of multidrug resistance and ESBL encoding genes - blaTEM, blaSHV, and blaCTX-M; its amplification and dispersion in the environment via municipal wastewater treatment plant - Kuldeep Soni; Km Jyoti; Anil Kumar; Ram Chandra (Chemosphere, 2024)

Rare earth elements and uranium in Minjingu phosphate fertilizer products: Plant food for thought - Nils H. Haneklaus; Dennis A. Mwalongo; Jacob B. Lisuma; Aloyce I. Amasi; Jerome Mwimanzi; Tomislav Bituh; Jelena Ćirić; Jakub Nowak; Urszula Ryszko; Piotr Rusek; Ali Maged; Essaid Bilal; et al. (Resources, Conservation and Recycling, 2024)

The combined action of a novel bacterial consortium as biocatalyst in microbial fuel cell and eco-friendly magnetic nanoparticles for treating synthetic wastewater containing sodium benzoate - Vishwata Patel; Abhishek A. Gor; Chetna Chauhan; Harsha Soni; Manisha Shah; Anup V. Sanchela; Nasreen S. Munshi (Journal of Water Process Engineering, 2024)

HRU-based Downscaling of GRACE-TWS to Quantify the Hydrogeological Fluxes and Specific Yield in the Lower Middle Ganga Basin - Ranveer Kumar; Shishir Gaur; Pramod Soni; Puneet Maurya; Anurag Ohri (Journal of Hydrology, 2024)

GC-MS based identification of anti-microbial bioactive compounds, isolated from Bacillus halotolerans of marine sediment - Kanchan Soni; Ashima Bagaria (Journal of Experimental Marine Biology and Ecology, 2024)

Pharmaceutical industrial wastewater exhibiting the co-occurrence of biofilm-forming genes in the multidrug-resistant bacterial community poses a novel environmental threat - Km Jyoti; Kuldeep Soni; Ram Chandra (Aquatic Toxicology, 2024)

Correction to: Efficient Adsorption of Lead(II) Ions from Artificial Wastewater by Organically Tailored vs TEOS‑Doped Silica Aerogels: Synthesis, Characterization and Isotherm Studies - Faheem Akhter; Heera Lal Soni; Abdul Rauf Jamali; Fernanda Miranda Zoppas; Sobhy M. Ibrahim (Water, Air, & Soil Pollution, 2024)

Evaluation of atmospheric precipitable water vapour distribution and trend over India - Chander Singh Tomar; Rajeev Bhatla; Nand Lal Singh; Vivek Kumar; Pradeep Kumar Rai; Vijay Kumar Soni; Ram Kumar Giri (Theoretical and Applied Climatology, 2024)

Adaptive enhancement of spatial information in adverse weather - Mohammad Shabaz; Mukesh Soni (Spatial Information Research, 2024)

Powerline extraction from aerial and mobile LiDAR data using deep learning - Vaibhav Kumar; Aritra Nandy; Vishal Soni; Bharat Lohani (Earth Science Informatics, 2024)

Jelly Seed Disorder in Mango: A Comprehensive Review of Current Status and Future Directions - Sharad Kumar Dwivedi; Dushyant Mishra; Alok Kumar Gupta; Vishambhar Dayal; Dinesh Kumar; Sanjay Kumar Singh; P. L. Saroj; Sumit K. Soni (Applied Fruit Science, 2024)

A review of conventional and rapid analytical techniques coupled with multivariate analysis for origin traceability of soybean - Khushboo Soni; Russell Frew; Biniam Kebede (Critical Reviews in Food Science and Nutrition, 2024)

Retraction Note: Synergy of RHA and silica sand on physico-mechanical and tribological properties of waste plastic–reinforced thermoplastic composites as floor tiles - Ashish Soni; Pankaj Kumar Das; Mohammad Yusuf; Amjad Ali Pasha; Kashif Irshad; Mostefa Bourchak (Environmental Science and Pollution Research, 2024)

Geographical variability of ultrafine particle concentrations in urban and background regions in India - Vignesh Mohan; Vijay Kumar Soni; Rajeev Kumar Mishra (Urban Climate, 2024)

The potential new microbial hazard monitoring tool in food safety: Integration of metabolomics and artificial intelligence - Ying Feng; Aswathi Soni; Gale Brightwell; Marlon M Reis; Zhengzheng Wang; Juan Wang; Qingping Wu; Yu Ding (Trends in Food Science & Technology, 2024)

Source contribution of black carbon aerosol during 2020–2022 at an urban site in Indo-Gangetic Plain - Arpit Malik; Shankar G. Aggarwal; Yutaka Kondo; Baban Kumar; Prashant Patel; Puna Ram Sinha; Naga Oshima; Sho Ohata; Tatsuhiro Mori; Makoto Koike; Khem Singh; Daya Soni; et al. (Science of The Total Environment, 2024)

Comparative measurement of CO2, CH4 and CO at two traffic interjunctions having inflated vehicular flow in Delhi - Komal; Daya Soni; Khem Singh; Shankar G. Aggarwal (Journal of Environmental Sciences, 2024)

A current review on P2X7 receptor antagonist patents in the treatment of neuroinflammatory disorders: a patent review on antagonists - Simran Soni; Mihir S. Lukhey; Baban S. Thawkar; Meena Chintamaneni; Ginpreet Kaur; Hemant Joshi; Seema Ramniwas; Hardeep Singh Tuli (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

The evolving facets of vaginal microbiota transplantation: reinvigorating the unexplored frontier amid complex challenges - Ishwerpreet Kaur Jawanda; Thomson Soni; Seema Kumari; Vijay Prabha (Archives of Microbiology, 2024)

Fe-based MOFs as promising adsorbents and photocatalysts for re-use water contained arsenic: Strategies and challenges - Monika Malhotra; Balvinder Kaur; Vatika Soni; Shilpa Patial; Kusum Sharma; Rohit Kumar; Pardeep Singh; Sourbh Thakur; Phuong V. Pham; Tansir Ahamad; Quyet Van Le; Van-Huy Nguyen; et al. (Chemosphere, 2024)

An estimation of atmospheric attenuation on an earth-space radio link operating at Ka-band over Larsemann hills area of Antarctica - Sahal Mohammed M.N.; Chinmay Kumar Patra; Sudhakar Kandukuri; Vivek Kumar; Vijay Kumar Soni (Polar Science, 2024)

Assessment of functional efficacy of sheep plasma protein hydrolysates and their utilization in mutton sausage - Sarita Kumari; Anurag Pandey; Arvind Soni; Anurag Mahala; Arun Kumar; Kushankur Dey (Meat Science, 2024)

The contraction of freshwater lenses in barrier island: A combined geophysical and numerical analysis - Jeeban Panthi; Thomas B. Boving; Soni M. Pradhanang; Christopher J. Russoniello; Seogi Kang (Journal of Hydrology, 2024)

Synergistic CdS@CeO2 nanocomposites: Harnessing Z-scheme electron transfer for enhanced photocatalytic CO2 conversion and aqueous Cr(VI) reduction - Lisamoni Kalita; Aishwarya Soni; Sanmilan Jyoti Kalita; Purashri Basyach; Ankur Kanti Guha; Suman L. Jain; Lakshi Saikia (Journal of Environmental Chemical Engineering, 2024)

Recent advances in waste-derived carbon dots and their nanocomposites for environmental remediation and biological applications - Himanshi Soni; Monika Bhattu; Priya SD; Manvinder Kaur; Meenakshi Verma; Jagpreet Singh (Environmental Research, 2024)

Multi-response optimization in the ORC-VCR system using the EDAS Method - Deepak Tiwari; Vinayak Soni (Energy and Buildings, 2024)

Estimation of genetic diversity utilizing gene-targeted SCoT markers and morpho-chemotypic analyses in Senna alexandrina Mill. (Senna) - Ashish Kumar; Anil Kumar Gupta; Saba Siddiqui; Soni Gupta; R.K. Lal; Abhilasha Srivastava; Mohammed Haris Siddiqui (Ecological Genetics and Genomics, 2024)

Revealing the Potential Effects and Risk of Microplastics from Face Mask on Human Health and Environment: A interlink Review on COVID-19 and Particulate Matter (PM2.5) - Dipa K. Israni; Jhanvi Soni; Sudarshan Singh; Bhupendra G. Prajapati (Water, Air, & Soil Pollution, 2024)

Temporal dynamics of urban air pollutants and their correlation with associated meteorological parameters: an investigation in northern Indian cities - Pushpendra Singh Soni; Vikram Singh; Alok Sagar Gautam; Karan Singh; Manish Sharma; Rolly Singh; Alka Gautam; Surendra Pratap Singh; Sanjeev Kumar; Sneha Gautam (Environmental Monitoring and Assessment, 2024)

Assessment of groundwater level using satellite-based hydrological parameters in North-West India: A deep learning approach - Pranshu Pranjal; Dheeraj Kumar; Ashish Soni; R. S. Chatterjee (Earth Science Informatics, 2024)

A Review on Picrosides Targeting NFκB and its Proteins for Treatment of Breast Cancer - Deepika Soni; Zubina Anjum; Khalid Raza; Saurabh Verma (Cell Biochemistry and Biophysics, 2024)

Quasi-planar ICME sheath: A cause of the first two-step extreme geomagnetic storm of the 25th solar cycle observed on 23 April 2023 - Kalpesh Ghag; Anil Raghav; Ankush Bhaskar; Shirsh Lata Soni; Bhagyashri Sathe; Zubair Shaikh; Omkar Dhamane; Prathmesh Tari (Advances in Space Research, 2024)

Elucidation of miRNAs and Their Putative Target Genes Associated with Jelly Seed Disorder of Mango (Mangifera indica L.) - Israr Ahmad; Sumit K. Soni; S. Rajan (Applied Fruit Science, 2024)

Application of Paclobutrazol Altered the Soil Bacterial Diversity and Richness of Mango Orchards: A Metagenomic Study - V. K. Singh; Sumit K. Soni; Pradeep K. Shukla; Anju Bajpai; Laxmi (Applied Fruit Science, 2024)

Revitalization of Overcrowded and Unproductive Mango (Mangifera indica L. cv ‘Dashehari’) Orchard Through Better Light Interception via Canopy Management - K. K. Srivastava; Dinesh Kumar; S. K. Dwivedi; Sumit K. Soni; S. R. Singh; S. K. Shukla (Applied Fruit Science, 2024)

Propellant Free Pressurized Spray System of Etodolac to Manage Acute Pain Conditions: In Vitro and In Vivo Evaluation - Shagun Saini; Bindu Soni; Manjot Kaur; Shubham Thakur; Riya Shivgotra; Navid Reza Shahtaghi; Subheet Kumar Jain (AAPS PharmSciTech, 2024)

Nanowonders in agriculture: Unveiling the potential of nanoparticles to boost crop resilience to salinity stress - Sunil Soni; Ambuj Bhushan Jha; Rama Shanker Dubey; Pallavi Sharma (Science of The Total Environment, 2024)

Effect of supplementation of bioactive rich tree leaves on nutrient utilization, growth performance, methane emission and fatty acid profile in finisher lambs fed energy dense diet - R.S. Bhatt; Srobana Sarkar; Lalit Soni; Priya Sharma; A. Sahoo; A. Soni (Small Ruminant Research, 2024)

Environmental life cycle assessment of underground metro rail: A case study in Mumbai Metropolitan Region, India - Amar Mohan Shinde; Anil Kumar Dikshit; Arti Soni (Environmental Impact Assessment Review, 2024)

Mass and Light Absorption Properties of Atmospheric Carbonaceous Aerosols over the Outflow Regions of Indo-Gangetic Plain - Ashish Soni; Abhijit Chatterjee; Binoy K. Saikia; Tarun Gupta (Atmospheric Environment, 2024)

Insights into the role of SUMO in regulating drought stress responses in pigeonpea (Cajanus cajan) - Aastha Ranjan; Shiloo Raj; Kamlesh Kumar Soni; Vivek Verma (Plant Cell Reports, 2024)

Performance analysis of an advanced concentrated solar power system for environmental benefit: energy and exergy analysis - A. Patel; R. Malviya; A. Soni; P. Baredar (International Journal of Environmental Science and Technology, 2024)

Evaluation of Antifungal Activity of Endophytic Bacillus spp. and Identification of Secondary Metabolites Produced Against the Phytopathogenic Fungi - Janki K. Patel; Yukta Mistry; Riya Soni; Anamika Jha (Current Microbiology, 2024)

Characterization of CeBr3 and NaI (Tl) based detector modules with readout using an array of Silicon Photomultiplier for the future space exploration programs - Shiv Kumar Goyal; Amisha P. Naik; Piyush Sharma; Abhishek J. Verma; Nupoor A. Chotaliya; Mansi M. Soni (Advances in Space Research, 2024)

Quantitative analysis of tiliroside and other flavonoid glycosides in Hippophae salicifolia D. Don leaves by HPLC-PDA - Soni Ranjana; Amit Srivastava; Alok Goyal; Inder Pal Singh; Sanjay M. Jachak (Natural Product Research, 2024)

Effect of Biofabricated Silver nanoparticles on Growth parameters in Fenugreek (Trigonella foenum-graecum) - Garvita Singh; Anshul Sheokand; Ashi Gupta; Himani Gupta; Jay Kumar; Renu Soni; Varsha K. Singh; Rajeshwar P. Sinha (Vegetos, 2024)

Penicillin-binding proteins: the master builders and breakers of bacterial cell walls and its interaction with β-lactam antibiotics - Milan Dabhi; Rohit Patel; Vidhi Shah; Richa Soni; Meenu Saraf; Rakesh Rawal; Dweipayan Goswami (Journal of Proteins and Proteomics, 2024)

Role of periodic irradiation and incident beam radius for plasmonic photothermal therapy of subsurface tumors - Amit Kumar Shaw; Sanjeev Soni (Journal of Thermal Biology, 2024)

Modelling soil-rotor blade interaction of vertical axis rotary tiller using discrete element method (DEM) - Prakhar Patidar; Peeyush Soni; Achala Jain; Vijay Mahore (Journal of Terramechanics, 2024)

Influence of β-CD and Ag deposition over TiO2 towards photocatalytic oxidation of urea under solar irradiation - Palak Soni; Bonamali Pal; Raj Kumar Das (Journal of Environmental Chemical Engineering, 2024)

Evaluating the sensitivity of fine particulate matter (PM2.5) simulations to chemical mechanism in WRF-Chem over Delhi - Rajmal Jat; Chinmay Jena; Prafull P. Yadav; Gaurav Govardhan; Gayatry Kalita; Sreyashi Debnath; Preeti Gunwani; Prodip Acharja; PoojaV. Pawar; Pratul Sharma; Santosh H. Kulkarni; Akshay Kulkarni; et al. (Atmospheric Environment, 2024)

Analysing the impact of day-night road traffic variation on ultrafine particle number size distribution and concentration at an urban site in the megacity Delhi - Vignesh Mohan; Vijay Kumar Soni; Rajeev Kumar Mishra (Atmospheric Pollution Research, 2024)

Elucidation of novel SNPs affecting immune response to classical swine fever vaccination in pigs using immunogenomics approach - Satish Kumar; Bharat Bhushan; Amit Kumar; Manjit Panigrahi; Jaya Bharati; Soni Kumari; Kaisa Kaiho; Santanu Banik; A. Karthikeyan; Rajni Chaudhary; G. K. Gaur; Triveni Dutt (Veterinary Research Communications, 2024)

In Silico Evaluation of Promising Naturally Occurring Bioactive Ligands Against Molecular Targets of SARS-Cov-2 - Unnati Soni; Tripti Mishra; O. P. Gupta; Mahesh Pal; Shalini Gupta; Saurabh Pratap Singh; Amita Sangwan; Krishna Misra (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2024)

Immobilization of microbial multienzyme preparation on calcium alginate beads as well as lyophilization with mosambi peel matrix improved its shelf-life and stability - Balvindra Singh; Sumit K. Soni; Supriya Vaish; Priti Mathur; Neelima Garg (Folia Microbiologica, 2024)

Quantum dots: a next generation approach for pathogenic microbial biofilm inhibition; mechanistic insights, existing challenges, and future potential - Khyati Koul; Ishwerpreet Kaur Jawanda; Thomson Soni; Pranjali Singh; Divyani Sharma; Seema Kumari (Archives of Microbiology, 2024)

Assessment of terminal heat tolerance ability of wheat genotypes based on chemometric analysis and agro-physiological traits - S. K. Dwivedi; Sumit K. Soni; J. S. Mishra; T. K. Koley; Santosh Kumar (Acta Physiologiae Plantarum, 2024)

Potential health risks assessment associated with arsenic-contaminated groundwater in the eastern district of Uttar Pradesh, India: a case study - Devendra Kumar Soni; Pradeep Kumar Mishra; Poonam Pandey (Environmental Sustainability, 2024)

Designing future peanut: the power of genomics-assisted breeding - Ali Raza; Hua Chen; Chong Zhang; Yuhui Zhuang; Yasir Sharif; Tiecheng Cai; Qiang Yang; Pooja Soni; Manish K. Pandey; Rajeev K. Varshney; Weijian Zhuang (Theoretical and Applied Genetics, 2024)

Variations in GNSS-/GPS-Measured Ionospheric TEC and Solar Wind Plasma Parameters During the Total Solar Eclipse of 09 March 2016 - Lakshmi Dagar; Vijay Kumar Soni; Adarsh Kumar (Journal of the Indian Society of Remote Sensing, 2024)

“Long COVID” and Its Impact on The Environment: Emerging Concerns and Perspectives - Parul Rana; Shilpa Patial; Vatika Soni; Pardeep Singh; Atul Khosla; Sourbh Thakur; Chaudhery Mustansar Hussaisn; Patricia de Carvalho Nagliate; Lucas Meili; Rangabhashiyam Selvasembian; Pankaj Raizada (Environmental Management, 2024)

A systematic overview of metal nanoparticles as alternative disinfectants for emerging SARS-CoV-2 variants - Sanjeev Kumar Soni; Tripta Marya; Apurav Sharma; Bishakha Thakur; Raman Soni (Archives of Microbiology, 2024)

Mitigating cadmium accumulation and toxicity in plants: The promising role of nanoparticles - Sunil Soni; Ambuj Bhushan Jha; Rama Shanker Dubey; Pallavi Sharma (Science of The Total Environment, 2024)

Machine learning-based draft prediction for mouldboard ploughing in sandy clay loam soil - Vijay Mahore; Peeyush Soni; Arpita Paul; Prakhar Patidar; Rajendra Machavaram (Journal of Terramechanics, 2024)

Municipal wastewater treatment plant showing a potential reservoir for clinically relevant MDR bacterial strains co-occurrence of ESBL genes and integron-integrase genes - Kuldeep Soni; David Kothamasi; Ram Chandra (Journal of Environmental Management, 2024)

Unlocking Indonesia's sweet sorghum potential: A techno-economic analysis of small-scale integrated sorghum-based fuel grade bioethanol industry - Soni Solistia Wirawan; Maharani Dewi Solikhah; Palupi Tri Widiyanti; Ni Putu Dian Nitamiwati; Romelan Romelan; Yayan Heryana; Ana Nurhasanah; Agus Sugiyono (Bioresource Technology Reports, 2024)

Enzyme-powered waste valorization: Simultaneous hydrolysis and fermentation of kitchen waste for biofertilizer production - Sanjeev Kumar Soni; Sakshi Dogra; Apurav Sharma; Bishakha Thakur; Jyoti Yadav; Raman Soni (Bioresource Technology Reports, 2024)

Processes governing the surface ozone over a tropical hill station in the Western Ghats - Revathy S. Ajayakumar; Imran A. Girach; Meghna Soni; Narendra Ojha; S. Suresh Babu (Atmospheric Environment, 2024)

Estimation of regional-scale near real time reference evapotranspiration using remote sensing and weather data to improve agriculture advisory - Anil Kumar Soni; Jayant Nath Tripathi; Kripan Ghosh; Priyanka Singh; M. Sateesh; K. K. Singh (Earth Science Informatics, 2024)

Two decadal (2003–2022) based trend analysis of aerosol optical depth (AOD) and its impact on cloud properties over a highly polluted region of India - Lakshmi; Vijay Kumar Soni; Adarsh Kumar (Arabian Journal of Geosciences, 2024)

An effective strategy for unit commitment of microgrid power systems integrated with renewable energy sources including effects of battery degradation and uncertainties - Premkumar Manoharan; Kumar Chandrasekaran; Ramakrishnan Chandran; Sowmya Ravichandran; Soni Mohammad; Pradeep Jangir (Environmental Science and Pollution Research, 2024)

Smart carbon-based sensors for the detection of non-coding RNAs associated with exposure to micro(nano)plastics: an artificial intelligence perspective - Pooja Ratre; Nazim Nazeer; Nikita Soni; Prasan Kaur; Rajnarayan Tiwari; Pradyumna Kumar Mishra (Environmental Science and Pollution Research, 2024)

Efficient in vitro regeneration of Artemisia annua : effect of different combinations of plant growth regulators on various types of explants - Ranjana Soni; Arpita Singh; Vikrant Gupta (Plant Biosystems, 2024)

Visible-light-driven photodegradation of methylene blue and doxycycline hydrochloride by waste-based S-scheme heterojunction photocatalyst Bi5O7I/PCN/tea waste biochar - Vatika Soni; Sonu; Anita Sudhaik; Pardeep Singh; Sourbh Thakur; Tansir Ahamad; Van-Huy Nguyen; Lan-Anh Phan Thi; Huy Hoang Phan Quang; Vishal Chaudhary; Pankaj Raizada (Chemosphere, 2024)

Impact of spatial metabolomics on immune-microenvironment in oral cancer prognosis: a clinical report - Swarnendu Bag; Janina Oetjen; Soni Shaikh; Amrita Chaudhary; Pattatheyil Arun; Geetashree Mukherjee (Molecular and Cellular Biochemistry, 2024)

Pansharpening Using IHS Method on Multi-sensor Data and Multiple Feature Extraction Using Modified Otsu Thresholding - Vikash Kumar Mishra; Raghvendra Kumar; Utsav Nareti; Triloki Pant; Pramod Kumar Soni (Journal of the Indian Society of Remote Sensing, 2024)

Layered double hydroxides based composite materials and their applications in food packaging - Sonika Kumari; Savita Soni; Ajay Sharma; Satish Kumar; Varruchi Sharma; Vivek Sheel Jaswal; Shashi Kant Bhatia; Anil Kumar Sharma (Applied Clay Science, 2024)

Influence of fly ash on thermo-mechanical and mechanical behavior of injection molded polypropylene matrix composites - Rajhans Meena; Abdul Wahab Hashmi; Shadab Ahmad; Faiz Iqbal; Hargovind Soni; Anoj Meena; Abdullah A. Al-Kahtani; Bidhan Pandit; Hesam Kamyab; Himanshu Payal; Mohammad Yusuf (Chemosphere, 2023)

Evaluation of meteorological characteristics and the influence of the Southern Annular Mode at newly established Bharati Station, East Antarctica - Vivek Kumar; Sanjay Bist; Rahil Akram; Anikender Kumar; Vijay Kumar Soni; Sunny Chug (Polar Science, 2023)

A novel antibacterial mechanism of atmospheric cold plasma against Staphylococcus aureus through degradation of cellular staphyloxanthin - Yupan Zhu; Hangbo Xu; Dongjie Cui; Renwu Zhou; Yanping Wang; Aswathi Soni; Gale Brightwell; Jie Zhuang; Ruonan Ma; Zhen Jiao (Innovative Food Science & Emerging Technologies, 2023)

Chemoprofiling and antioxidant activity of edible curcuma species - Akanksha Jain; Parag Jain; Sonia Bajaj; Ashish Majumdar; Pranay Soni (Food and Humanity, 2023)

Layered double hydroxides and their tailored hybrids/composites: Progressive trends for delivery of natural/synthetic-drug/cosmetic biomolecules - Sonika Kumari; Varruchi Sharma; Savita Soni; Ajay Sharma; Abhinay Thakur; Satish Kumar; Kuldeep Dhama; Anil Kumar Sharma; Shashi Kant Bhatia (Environmental Research, 2023)

Light-absorbing properties of polar- and non-polar brown carbon fractions of aerosols in Delhi - Ashmeet Kaur Alang; Shankar G. Aggarwal; Khem Singh; Daya Soni; Prashant Hegde (Atmospheric Research, 2023)

Metabolomics-mediated elucidation of rice responses to salt stress - Nitasana Rajkumari; Soni Chowrasia; Jyoti Nishad; Showkat Ahmad Ganie; Tapan Kumar Mondal (Planta, 2023)

The interplay between cell wall integrity and cell cycle progression in plants - Nancy Soni; Laura Bacete (Plant Molecular Biology, 2023)
Plant cell walls are dynamic structures that play crucial roles in growth, development, and stress responses. Despite our growing understanding of cell wall biology, the connections between cell wall integrity (CWI) and cell cycle progression in plants remain poorly understood. This review aims to explore the intricate relationship between CWI and cell cycle progression in plants, drawing insights from studies in yeast and mammals. We provide an overview of the plant cell cycle, highlight the role of endoreplication in cell wall composition, and discuss recent findings on the molecular mechanisms linking CWI perception to cell wall biosynthesis and gene expression regulation. Furthermore, we address future perspectives and unanswered questions in the field, such as the identification of specific CWI sensing mechanisms and the role of CWI maintenance in the growth-defense trade-off. Elucidating these connections could have significant implications for crop improvement and sustainable agriculture.

Genomic profile of diabetic retinopathy in a north indian cohort - Ruhi Sikka; Priyanka Raina; Rhibhu Soni; Himanshu Gupta; A. J. S. Bhanwer (Molecular Biology Reports, 2023)

Comparative analysis of wind potential and characteristics using metaheuristic optimization algorithms at different places in India - H. Patidar; V. Shende; P. Baredar; A. Soni (International Journal of Environmental Science and Technology, 2023)

Cross-species transferability of IRAP retrotransposon markers and polymorphism in black pepper (Piper nigrum L.) - Manjushri Dinkar Dongare; Swapna Alex; K. B. Soni; K. P. Sindura; Deepa S. Nair; Roy Stephen; Elizabeth Jose (Genetic Resources and Crop Evolution, 2023)

Meta-analysis of transcriptomics studies identifies novel attributes and set of genes involved in iron homeostasis in rice - Pooja Kanwar Shekhawat; Shaswati Sardar; Banita Yadav; Prafull Salvi; Praveen Soni; Hasthi Ram (Functional & Integrative Genomics, 2023)

A review on the municipal solid waste management status, challenges and potential for the future Indian cities - Ashish Soni; Pankaj Kumar Das; Prabhat Kumar (Environment, Development and Sustainability, 2023)

Host response of elite maize inbreds and hybrids against maydis leaf blight under epiphytotic conditions - Ankush Kumar; Harbinder Singh; Prashant Chauhan; Namita Soni; Munish Leharwan; N. K. Yadav (Cereal Research Communications, 2023)

Bioinoculants: the agrarian avengers - Anushree Kamath; Arpit Shukla; Tayyaba Saiyed; Soham Bhatt; Hirva Rathod; Vidhi Makwana; Diya Soni; Shuvomoy Banerjee; Dhara Patel (Symbiosis, 2023)

Assessment of spatio-temporal variation in AOD over four coal mine sites of Assam through satellite observation - Anjali S Nair; Kirti Soni; Priyanka Singh; Kuldeep Meena; Rina Sharma (Journal of Environmental Studies and Sciences, 2023)

Hydrodynamic Simulation of Green Hydrogen Catamaran Operating in Lisbon, Portugal - Gaurav Soni; Rui Costa Neto; Lúcia Moreira (Journal of Marine Science and Engineering, 2023)
Similar to other industries, the maritime industry is also facing increasing restrictions on ships regarding pollution control. The research presented in this paper is aimed at studying the pros and cons of alternative fuels followed by a detailed analysis on hydrogen fuel cells (PEMFC) for a particular ship operating in Lisbon, Portugal. Dynamic forces acting on the ship have been studied for a year. Assessing various scenarios based on these results aids ship operators in making informed decisions regarding the future course of action for their existing vessels. These different cases are first: business as usual (diesel engine), second: replacing the diesel engine with a hydrogen hybrid system and, third: replacement of the ship with a new hydrogen hybrid ship. The study is based on the simulation of numerical equations and CFD simulation results. As the result, the second scenario is best suited in both aspects; namely, environmental and economic.

Lithospheric plane strain deformation caused by a vertical dip-slip fault - Nirmal Soni; Sunita Rani (Journal of Earth System Science, 2023)

A comprehensive review on electro-oxidation and its types for wastewater treatment - Greeshma Nair; Bhavna Soni; Manan Shah (Groundwater for Sustainable Development, 2023)

Effect of trifluoroacetic acid on the antigenicity of capsular polysaccharides obtained from various Streptococcus pneumoniae serotypes - Walmik Karbhari Gaikwad; Rajeev M. Dhere; Swapan K. Jana; Asha D. Mallya; Dipen J. Soni; Makrand Gholap; Neil Ravenscroft; Kisan M. Kodam (Carbohydrate Polymers, 2023)

Roflumilast ameliorates diabetic nephropathy in rats through down-regulation of JAK/STAT signaling pathway - Priyal Patel; Sandip Patel; Piyush Chudasama; Shailesh Soni; Manan Raval (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Increasing risk of cascading hazards in the central Himalayas - Sanjib Sharma; Rocky Talchabhadel; Santosh Nepal; Ganesh R. Ghimire; Biplob Rakhal; Jeeban Panthi; Basanta R. Adhikari; Soni M. Pradhanang; Shreedhar Maskey; Saurav Kumar (Natural Hazards, 2023)

Characteristics of atmospheric boundary layer structure using monostatic SODAR system over Mumbai region - Nishant Kumar; Anjali S Nair; Kirti Soni; A A Shingare; Vidyanand M Motghare; Karansingh A Rajput; V K Soni; Anikender Kumar; Arvind Kumar Jha (Journal of Earth System Science, 2023)

Selection of waste plastics for incorporation in agro-waste as sustainable building construction materials concerning circular economy: an integrated MCDM approach - Ashish Soni; Pankaj Kumar Das; Sanjay Kumar (Clean Technologies and Environmental Policy, 2023)

Cooperative interaction of Glomus intraradices with plant growth-promoting rhizobacteria promotes plant development and essential oil yield of Pogostemon cablin and reduces disease occurrence under organic field conditions - Rakshapal Singh; Sumit K. Soni; Anju Bajpai (Australasian Plant Pathology, 2023)

Enhanced photocatalytic and SERS performance of Ag nanoparticles functionalized MoS2 nanoflakes - Jaspal Singh; R.K. Soni; D. Duc Nguyen; Vijai Kumar Gupta; Phuong Nguyen-Tri (Chemosphere, 2023)

Limits of antibacterial activity of triangular silver nanoplates and photothermal enhancement thereof for Bacillus subtilis - Sarabjot Kaur; Rajneesh Dadwal; Hemraj Nandanwar; Sanjeev Soni (Journal of Photochemistry and Photobiology B: Biology, 2023)

Fabricating cattle dung-derived nitrogen-doped biochar supported oxygen-deficient ZnO and Cu2O-based novel step-scheme photocatalytic system for aqueous Doxycycline hydrochloride mitigation and Cr (VI) reduction - Vatika Soni; Sonu; Pardeep Singh; Sourbh Thakur; Pankaj Thakur; Tansir Ahamad; Van-Huy Nguyen; Quyet Van Le; Chaudhery Mustansar Hussain; Pankaj Raizada (Journal of Environmental Chemical Engineering, 2023)

Coix: an underutilized functional food crop of Mizoram - Jeetendra Kumar Soni; B. Lalramhlimi; Amit Kumar; Omprakash Navik; Lungmuana; Lalhruaitluangi Sailo; S. Doley (Genetic Resources and Crop Evolution, 2023)

Design and development of a PM10 multi-inlet cyclone and comparison with reference cyclones - Prashant Patel; Shankar G. Aggarwal; Thi-Cuc Le; Khem Singh; Daya Soni; Chuen-Jinn Tsai (Air Quality, Atmosphere & Health, 2023)

Insight into the environmental fate, hazard, detection, and sustainable degradation technologies of chlorpyrifos—an organophosphorus pesticide - Pankaj Kumar; Muhammad Arshad; Amel Gacem; Sunil Soni; Snigdha Singh; Manoj Kumar; Virendra Kumar Yadav; Mohd. Tariq; Ramesh Kumar; Deepankshi Shah; Shivraj Gangadhar Wanale; Mohammed Khaloofah Mola Al Mesfer; et al. (Environmental Science and Pollution Research, 2023)

Prognostic Potential of Thrombocyte Indices, Acute Phase Proteins, Electrolytes and Acid-Base Markers in Canine Parvovirus Infected Dogs With Systemic Inflammatory Response Syndrome - Babul Rudra Paul; Ujjwal Kumar De; Varun Kumar Sarkar; Jitendra Singh Gandhar; Manas Kumar Patra; Mithilesh Kumar Singh; Srishti Soni; Chethan Gollahalli Eregowda (Topics in Companion Animal Medicine, 2023)

Physical and chemical properties of PM1 in Delhi: A comparison between clean and polluted days - Arpit Malik; Shankar G. Aggarwal; Bhagawati Kunwar; Dhananjay Kumar Deshmukh; Kritika Shukla; Rishu Agarwal; Khem Singh; Daya Soni; Puna Ram Sinha; Sho Ohata; Tatsuhiro Mori; Makoto Koike; et al. (Science of The Total Environment, 2023)

Influence of green roof plant density and redirecting rainfall via runoff zones on rainfall retention and plant drought stress - Lubaina Soni; Christopher Szota; Tim D. Fletcher; Claire Farrell (Science of The Total Environment, 2023)

Toxicity of malachite green on plants and its phytoremediation: A review - Jyotshana Sharma; Shubhangani Sharma; Vineet Soni (Regional Studies in Marine Science, 2023)

Covalent organic frameworks (COFs) core@shell nanohybrids: Novel nanomaterial support towards environmental sustainability applications - Vatika Soni; Shilpa Patial; Abhinandan Kumar; Pardeep Singh; Vijaya Kumar; Tansir Ahamad; Quyet Van Le; Rafael Luque; Pankaj Raizada; Van-Huy Nguyen (Environmental Research, 2023)

Delineating bedrock topography with geophysical techniques: An implication for groundwater mapping - Jeeban Panthi; Carole D. Johnson; Soni M. Pradhanang; Brian Savage; Mamoon Y. Ismail; Thomas B. Boving (CATENA, 2023)

Utilization of biochar derived from chick pea straw to enhance the properties of black cotton soil - Khemlata Soni; Aryak Shori; Surendra Kalbande; Vipin Kumar Mishra (Bioresource Technology Reports, 2023)

Expression profiling of laccase and β-glucan synthase genes in Pleurotus ostreatus during different developmental stages - Nesma A. S.; Susha S. Thara; K. B. Soni; K. P. Sindura; Krishnapriya P. J. (Molecular Biology Reports, 2023)

Integrated Application of Trichoderma and Carbendazim Affects the Carbendazim Extractability and Microbial Functions in the Maize Rhizosphere - Soni Chauhan; Touseef Fatima; Amita Dubey; Puneet Singh Chauhan; Om Prakash; Poonam C. Singh (Journal of Soil Science and Plant Nutrition, 2023)

Mucoadhesive Films of Docetaxel with Ceramide as an Adjuvant Monitoring Polymer-Drug Partitioning for Optimal Drug Release - Poornima Agrawal; Vandana Soni (Journal of Pharmaceutical Innovation, 2023)

Utilization of Deep Convolutional Neural Networks for Accurate Chest X-Ray Diagnosis and Disease Detection - Mukesh Mann; Rakesh P. Badoni; Harsh Soni; Mohammed Al-Shehri; Aman Chandra Kaushik; Dong-Qing Wei (Interdisciplinary Sciences: Computational Life Sciences, 2023)

Carbendazim Modulates the Metabolically Active Bacterial Populations in Soil and Rhizosphere - Soni Chauhan; Udit Yadav; Nasreen Bano; Sanjeev Kumar; Touseef Fatima; Anshu; Amita Dubey; Poonam C. Singh (Current Microbiology, 2023)

Correction to: Characterization of Enterococcus durans M7-2 and Weissella confusa M13 as prospective probiotics - Riteshri Soni; Hareshkumar Keharia (Biologia, 2023)

Negotiating oil and gas resource ownership for equitable sharing: A problematization approach and evidence from India - Vivek Soni; Prasanta Kumar Dey; Sunil Sharma; Debadyuti Das (Resources Policy, 2023)

Precise utilization of fruit and vegetable waste as a substrate for the multienzyme production by Bacillus subtilis NG105 and Trichoderma asperelllum NG125 - Balvindra Singh; Sumit K. Soni; Neelima Garg; Priti Mathur (Biocatalysis and Agricultural Biotechnology, 2023)

Horticultural geographical indications of India: botanical aspect - Garvita Singh; Kirti Sharma; Sakshi Dawer; Shweta Rana; Renu Soni; Varsha K. Singh; Rajeshwar P. Sinha (Vegetos, 2023)

Horny gourd (Cucumis metuliferus L.): a hidden vegetable boon for human nutrition - Dalasanuru Chandregowda Manjunathagowda; Mottaiyan Pitchaimuthu; Virupakshi Hiremata; G. C. Sathisha; Shruti Soni; M. V. Dhananjaya; Dhoranalapalli Chinnappareddy Lakshmana Reddy (Genetic Resources and Crop Evolution, 2023)

COVID-19 and transportation of India: influence on infection risk and greenhouse gas emissions - Arti Roshan Soni; Kumar Amrit; Amar Mohan Shinde (Environment, Development and Sustainability, 2023)

Characterization of Enterococcus durans M7-2 and Weissella confusa M13 as prospective probiotics - Riteshri Soni; Hareshkumar Keharia (Biologia, 2023)

Application of q-rung orthopair fuzzy based SWARA-COPRAS model for municipal waste treatment technology selection - Ashish Soni; Pankaj Kumar Das; Sanjay Kumar (Environmental Science and Pollution Research, 2023)

Review of the adsorbents/catalysts for the removal of sulfur compounds from natural gas - Percival Soni Castro; Gerson Martinez Zuniga; William Holmes; Prashanth R. Buchireddy; Daniel D. Gang; Emmanuel Revellame; Mark Zappi; Rafael Hernandez (Gas Science and Engineering, 2023)

Rice lipases: a conundrum in rice bran stabilization: a review on their impact and biotechnological interventions - Sakshi Bansal; Sathish Sundararajan; Pooja Kanwar Shekhawat; Shivangi Singh; Praveen Soni; Manas K. Tripathy; Hasthi Ram (Physiology and Molecular Biology of Plants, 2023)

Ventilation Coefficient Characteristics over North Indian Cities During the Post-Monsoon Season - Priyanka Singh; Nishant Kumar; Anjali S Nair; Kirti Soni; Kuldeep Meena; Rina Sharma (Journal of the Indian Society of Remote Sensing, 2023)

An overview for biomedical waste management during pandemic like COVID-19 - V. S. Kanwar; A. Sharma; Rinku; M. Kanwar; A. L. Srivastav; D. K. Soni (International Journal of Environmental Science and Technology, 2023)

Control of the post-infarct immune microenvironment through biotherapeutic and biomaterial-based approaches - Shreya S. Soni; Arielle M. D’Elia; Christopher B. Rodell (Drug Delivery and Translational Research, 2023)
Ischemic heart failure (IHF) is a leading cause of morbidity and mortality worldwide, for which heart transplantation remains the only definitive treatment. IHF manifests from myocardial infarction (MI) that initiates tissue remodeling processes, mediated by mechanical changes in the tissue (loss of contractility, softening of the myocardium) that are interdependent with cellular mechanisms (cardiomyocyte death, inflammatory response). The early remodeling phase is characterized by robust inflammation that is necessary for tissue debridement and the initiation of repair processes. While later transition toward an immunoregenerative function is desirable, functional reorientation from an inflammatory to reparatory environment is often lacking, trapping the heart in a chronically inflamed state that perpetuates cardiomyocyte death, ventricular dilatation, excess fibrosis, and progressive IHF. Therapies can redirect the immune microenvironment, including biotherapeutic and biomaterial-based approaches. In this review, we outline these existing approaches, with a particular focus on the immunomodulatory effects of therapeutics (small molecule drugs, biomolecules, and cell or cell-derived products). Cardioprotective strategies, often focusing on immunosuppression, have shown promise in pre-clinical and clinical trials. However, immunoregenerative therapies are emerging that often benefit from exacerbating early inflammation. Biomaterials can be used to enhance these therapies as a result of their intrinsic immunomodulatory properties, parallel mechanisms of action (e.g., mechanical restraint), or by enabling cell or tissue-targeted delivery. We further discuss translatability and the continued progress of technologies and procedures that contribute to the bench-to-bedside development of these critically needed treatments. Graphical Abstract

Alleviation of chromium stress in plants using metal and metal oxide nanoparticles - Sunil Soni; Ambuj Bhushan Jha; Rama Shanker Dubey; Pallavi Sharma (Environmental Science and Pollution Research, 2023)

Effect of supplementation of roasted oilseeds and phytochemical-rich herbages on nutrient utilization, methane emission, and growth performance in finisher lambs - Randhir Singh Bhatt; Srobana Sarkar; Lalit Soni; Artabandhu Sahoo (Environmental Science and Pollution Research, 2023)

Groundwater analysis using Gravity Recovery, Climate Experiment and Google Earth Engine: Bundelkhand region, India - Vishal Kumar Singh; H.K. Pandey; Sudhir Kumar Singh; Pramod Soni (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Performance evaluation of a novel geothermal energy integrated single effect evaporator desalination with software simulation - Mitul Prajapati; Manan Shah; Bhavna Soni (Journal of Cleaner Production, 2023)

Pullout behaviour of polymeric strips embedded in mixed recycled aggregate (MRA) from construction & demolition (C&D) waste – Effect of type of fill and compaction - Apoorva Agarwal; G.V. Ramana; Manoj Datta; Narendra Kumar Soni; Rajiv Satyakam (Geotextiles and Geomembranes, 2023)

Industrial mint crop revolution, new opportunities, and novel cultivation ambitions: A review - Soni Gupta; A. Kumar; A.K. Gupta; A.C. Jnanesha; M. Talha; A. Srivastava; R.K. Lal (Ecological Genetics and Genomics, 2023)

Influence of energy sources and shade drying period on oil yield and chemical composition of the essential oil extracted from Palmarosa grass (Cymbopogon martinii) through hydro distillation method - Khemlata Soni; Surendra Kalbande (Bioresource Technology Reports, 2023)

Effect of different bagging materials on guava fruit physiology and its quality attributes - K. K. Srivastava; Sumit K. Soni; Dinesh Kumar; S. K. Dwivedi (Plant Physiology Reports, 2023)

Allantoin improves salinity tolerance in Arabidopsis and rice through synergid activation of abscisic acid and brassinosteroid biosynthesis - Soni Chowrasia; Jyoti Nishad; Rekha Mahato; Kanti Kiran; Nitasana Rajkumari; Alok Kumar Panda; Hukam C. Rawal; Mandira Barman; Tapan Kumar Mondal (Plant Molecular Biology, 2023)

Linear regression model for noise pollution over central Delhi to highlight the alarming threat for the environment - Adwaita Dwivedi; Nishant Kumar; Priyanka Singh; Parag Chourey; Rohan Kamra; Kirti Soni; Mahavir Singh (Modeling Earth Systems and Environment, 2023)

Biochemical responses in wheat due to Puccinia triticina infection - Rashmi D.; Shipra Sharma; Kavin K. Soni; S. I. Patel (Indian Phytopathology, 2023)

SVM-based classification of multi-temporal Sentinel-2 imagery of dense urban land cover of Delhi-NCR region - Yash Khurana; Pramod Kumar Soni; Devershi Pallavi Bhatt (Earth Science Informatics, 2023)

Water-soluble dicarboxylic acids, oxoacids and α-dicarbonyls in the tropical aerosols in coastal megacity Mumbai: molecular characteristics and formation processes - Ashmeet Kaur Alang; Shankar G. Aggarwal; Khem Singh; Daya Soni; Kimitaka Kawamura (Journal of Atmospheric Chemistry, 2023)

Reverse-gavage feeding as a novel administration to investigate the immunomodulatory effects of Radix Scutellaria water extract on Macrobrachium rosenbergii immunity - Soni Andriawan; Hung Tran Bao; Wahyu Purbiantoro; Ating Yuniarti; Hso Chi Chaung; Tsair-Bor Yen; Ta-Chih Cheng (Aquaculture International, 2023)

Synergy of silica sand and waste plastics as thermoplastic composites on abrasive wear characteristics under conditions of different loads and sliding speeds - Ashish Soni; Pankaj Kumar Das; Mohammad Yusuf; Syahrir Ridha; Hesam Kamyab; Mohammad Azad Alam; Faisal Masood; Shreeshivadasan Chelliapan; Mohd Ubaidullah; Bidhan Pandit; Chander Prakash (Chemosphere, 2023)

Effect of systemic inflammatory response syndrome on thrombocytogram, acute phase proteins, electrolytes, acid-base indices and cytokine expression in naturally canine parvovirus infected dogs - Babul R. Paul; Ujjwal K. De; Varun K. Sarkar; Jitendra S. Gandhar; Manas K. Patra; Ravi K. Agrawal; Mithilesh K. Singh; Srishti Soni; Chethan G. Eregowda (Veterinary Immunology and Immunopathology, 2023)

Characteristics of volatile organic compounds (VOCs) at an urban site of Delhi, India: Diurnal and seasonal variation, sources apportionment - T.K. Mandal; Pooja Yadav; Mukesh Kumar; Shyam Lal; Kirti Soni; Lokesh Yadav; Ummed Singh Saharan; S.K. Sharma (Urban Climate, 2023)

Sway of aerosol on Atmospheric Boundary Layer influencing air pollution of Delhi - Anjali S Nair; Priyanka Singh; Kirti Soni; Kuldeep Meena; Rina Sharma (Urban Climate, 2023)

An inclusive outlook on the fate and persistence of pesticides in the environment and integrated eco-technologies for their degradation - Yogesh S. Chaudhari; Pankaj Kumar; Sunil Soni; Amel Gacem; Vinay Kumar; Snigdha Singh; Virendra Kumar Yadav; Vinars Dawane; Satish Piplode; Byong-Hun Jeon; Hala A. Ibrahium; Rabab A. Hakami; et al. (Toxicology and Applied Pharmacology, 2023)

Aerosol Variability at Coastal Bhola Island (Bangladesh), an IGP Outflow Region - Anjali S Nair; Kirti Soni; Priyanka Singh; Kuldeep Meena; Rina Sharma (Journal of the Indian Society of Remote Sensing, 2023)

Carotenoid from marine Bacillus infantis: production, extraction, partial characterization, and its biological activity - Nidhi Soni; Pinakin Dhandhukia; Janki N. Thakker (Archives of Microbiology, 2023)

Cigarette: an unsung anthropogenic evil in the environment - Garishma Shah; Upma Bhatt; Vineet Soni (Environmental Science and Pollution Research, 2023)

Opposite trends in heat waves and cold waves over India - Aninda Bhattacharya; Abin Thomas; Vijay K Soni; P S Roy; Chandan Sarangi; Vijay P Kanawade (Journal of Earth System Science, 2023)

Use of Moringa oleifera leaves (sole or combined with concentrate) in rabbit feeding: Effects on performance, carcass characteristics and meat quality attributes - R.S. Bhatt; Srobana Sarkar; S.R. Sharma; Arvind Soni (Meat Science, 2023)

Herbicide resistant Phalaris minor in India—history of evolution, present status and its management - Jeetendra Kumar Soni; Amarjeet Nibhoria; S. S. Punia; Dharam Bir Yadav; V. K. Choudhary; B. Lalramhlimi; Omprakash Navik (Phytoparasitica, 2023)

Flower Regulation in Floriculture: An Agronomic Concept and Commercial Use - Anjali Chandel; Meenakshi Thakur; Gurpreet Singh; Ruchika Dogra; Ankush Bajad; Vikas Soni; Bhavya Bhargava (Journal of Plant Growth Regulation, 2023)

A clash of quorum sensing vs quorum sensing inhibitors: an overview and risk of resistance - Rohit Patel; Mansi Soni; Bilv Soyantar; Suruchi Shivangi; Swati Sutariya; Meenu Saraf; Dweipayan Goswami (Archives of Microbiology, 2023)

Development of a mathematical model to forecast black carbon concentration using ARIMA and soft computing - Jatinder Kaur; Sarbjit Singh; Kulwinder Singh Parmar; Kirti Soni (Arabian Journal of Geosciences, 2023)

Synergy of waste plastics and natural fibers as sustainable composites for structural applications concerning circular economy - Ashish Soni; Sameer Kumar; Biprajit Majumder; Hriddhi Dam; Vishal Dutta; Pankaj Kumar Das (Environmental Science and Pollution Research, 2023)

Forest vegetation response to anthropogenic pressures: a case study from Askot Wildlife Sanctuary, Western Himalaya - Soni Bisht; G. S. Rawat; Surendra Singh Bargali; Y. S. Rawat; Abhinav Mehta (Environment, Development and Sustainability, 2023)

Hexavalent chromium-reducing plant growth-promoting rhizobacteria are utilized to bio-fortify trivalent chromium in fenugreek by promoting plant development and decreasing the toxicity of hexavalent chromium in the soil - Sumit K. Soni; Govind Kumar; Anju Bajpai; Rakshapal Singh; Yashi Bajapi; Laxmi; Sudeep Tiwari (Journal of Trace Elements in Medicine and Biology, 2023)

CDAP: A portable CCD-based daytime airglow photometer for investigations of ionosphere-thermosphere phenomena - Duggirala Pallamraju; Pradip Suryawanshi; Shashank Urmalia; Sunil Kumar; Sovan Saha; Ravindra Pratap Singh; Pankaj K. Kushwaha; Mohit Soni (Journal of Atmospheric and Solar-Terrestrial Physics, 2023)

Efficient Adsorption of Lead(II) Ions from Artificial Wastewater by Organically Tailored vs TEOS-Doped Silica Aerogels: Synthesis, Characterization and Isotherm Studies - Faheem Akhter; Heera Lal Soni; Abdul Rauf Jamali; Fernanda Miranda Zoppas; Sobhy M. Ibrahim (Water, Air, & Soil Pollution, 2023)

Silicon Supplementation as a Promising Approach to Induce Thermotolerance in Plants: Current Understanding and Future Perspectives - Alka Bishnoi; Pooja Jangir; Pooja Kanwar Shekhawat; Hasthi Ram; Praveen Soni (Journal of Soil Science and Plant Nutrition, 2023)

Multi-objective dynamic economic emission dispatch integration with renewable energy sources and plug-in electrical vehicle using equilibrium optimizer - Jatin Soni; Kuntal Bhattacharjee (Environment, Development and Sustainability, 2023)

Temporal and Spatial Variations of Satellite-Based Aerosol Optical Depths, Angstrom Exponent, Single Scattering Albedo, and Ultraviolet-Aerosol Index over Five Polluted and Less-Polluted Cities of Northern India: Impact of Urbanization and Climate Change - Rolly Singh; Vikram Singh; Alok Sagar Gautam; Sneha Gautam; Manish Sharma; Pushpendra Singh Soni; Karan Singh; Alka Gautam (Aerosol Science and Engineering, 2023)

Molecular characterization of carbapenem resistant E. coli of fish origin reveals the dissemination of NDM-5 in freshwater aquaculture environment by the high risk clone ST167 and ST361 - Arti Dwivedi; Chandra Bhushan Kumar; Anil Kumar; Mayank Soni; Vikash Sahu; Abhishek Awasthi; Gaurav Rathore (Environmental Science and Pollution Research, 2023)

Detection of 2,4-dichlorophenoxyacetic acid in water sample by organosilane based silica nanocomposites - Gurjaspreet Singh; Sanjay Sharma; Akshpreet Singh; Mohit; Anita Devi; Sofia Gupta; Pooja Malik; Sumesh Khurana; Sajeev Soni (Science of The Total Environment, 2023)

Rational design, structure properties, and synthesis strategies of dual-pore covalent organic frameworks (COFs) for potent applications: A review - Shilpa Patial; Vatika Soni; Abhinandan Kumar; Pankaj Raizada; Tansir Ahamad; Xuan Minh Pham; Quyet Van Le; Van-Huy Nguyen; Sourbh Thakur; Pardeep Singh (Environmental Research, 2023)

Early-Life Intervention of Lactoferrin and Probiotic in Suckling Piglets: Effects on Immunoglobulins, Intestinal Integrity, and Neonatal Mortality - Varun Kumar Sarkar; Ujjwal Kumar De; Anju Kala; Ashok Kumar Verma; Anuj Chauhan; Babul Rudra Paul; Srishti Soni; Jitendra Singh Gandhar; Pallab Chaudhuri; Manas Kumar Patra; Chethan Gollahalli Eregowda; Gyanendra Kumar Gaur (Probiotics and Antimicrobial Proteins, 2023)

Comparing the efficacy of forage combinations with different hydrolysable and condensed tannin levels to improve production and lower methane emission in finisher lambs - R.S. Bhatt; Srobana Sarkar; Priya Sharma; Lalit Soni; A. Sahoo (Small Ruminant Research, 2023)

Exogenously applied plant growth regulator protects rice from heat-induced damage by modulating plant defense mechanism - G. Lakshmi; R. Beena; K. B. Soni; M. M. Viji; Uday Chand Jha (Journal of Crop Science and Biotechnology, 2023)

Rhodamine B induced alteration in antioxidant enzymes and photosynthetic performance of Eichhornia crassipes - Jyotshana Sharma; Hanwant Singh; Shubhangani Sharma; Deepak Kumar; Upma Bhatt; Vineet Soni (Plant Physiology Reports, 2022)

Correction: Chlorogenic Acid: a Polyphenol from Coffee Rendered Neuroprotection Against Rotenone-Induced Parkinson’s Disease by GLP-1 Secretion - Nishant Sharma; Ritu Soni; Monika Sharma; Sayan Chatterjee; Nidhi Parihar; Mohd Mukarram; Ruhi Kale; Adil Ali Sayyed; Santosh Kumar Behera; Amit Khairnar (Molecular Neurobiology, 2022)

Allantoin mediated regulation of miRNAs for short term salinity stress tolerance in Oryza sativa L. cv. IR-29 - Jyoti Nishad; Alok Kumar Panda; Soni Chowrasia; Chongtham Nirmala; Tapan Kumar Mondal (Journal of Plant Biochemistry and Biotechnology, 2022)

A Comprehensive Review on Assessment and Key Control Strategies for Impurities in Drug Development with a Special Emphasis on Post-marketing Surveillance - Nikita Tapkir; Fatema Soni; Amit Kumar Sahu; Tarang Jadav; Rakesh K. Tekade; Pinaki Sengupta (Journal of Pharmaceutical Innovation, 2022)

Comparative evaluation of optimal Weibull parameters for wind power predictions using numerical and metaheuristic optimization methods for different Indian terrains - Harsh Patidar; Vikas Shende; Prashant Baredar; Archana Soni (Environmental Science and Pollution Research, 2022)

Analysis of temperature distribution over pipe surfaces of air-based cavity linear receiver for cross-linear concentration solar power system - Akash Patel; Archana Soni; Prashant Baredar; Rajkumar Malviya (Environmental Science and Pollution Research, 2022)

Trends in diurnal variation of surface air temperatures over India during hot weather (April–June) season - P. Rohini; M. Rajeevan; V. K. Soni (Natural Hazards, 2022)

Chlorogenic Acid: a Polyphenol from Coffee Rendered Neuroprotection Against Rotenone-Induced Parkinson’s Disease by GLP-1 Secretion - Nishant Sharma; Ritu Soni; Monika Sharma; Sayan Chatterjee; Nidhi Parihar; Mohd Mukarram; Ruhi kale; Adil Ali Sayyed; Santosh Kumar Behera; Amit Khairnar (Molecular Neurobiology, 2022)

Enhanced atmospheric pollution due to the Uttarakhand fire event of April 2016 and its radiative impact - Divyaja Lawand; Sumita Kedia; Rohini Bhawar; P. R. C. Rahul; Vijay Soni; Sahidul Islam; Manoj Khare (Air Quality, Atmosphere & Health, 2022)

The evaluation of climate change impact on hydrologic processes of a mountain river basin - Tirtha Raj Adhikari; Rocky Talchabhadel; Suraj Shrestha; Sanjib Sharma; Dibit Aryal; Soni M. Pradhanang (Theoretical and Applied Climatology, 2022)

Immunotherapy: an alternative promising therapeutic approach against cancers - Sneh Lata Gupta; Srijani Basu; Vijay Soni; Rishi K. Jaiswal (Molecular Biology Reports, 2022)

Detection of a target protein (GroEl2) in Mycobacterium tuberculosis using a derivative of 1,2,4-triazolethiols - Sampa Sarkar; Sagar Swami; Sarvesh Kumar Soni; Jessica K. Holien; Arshad Khan; Arvind M. Korwar; Anjali P. Likhite; Ramesh A. Joshi; Rohini R. Joshi; Dhiman Sarkar (Molecular Diversity, 2022)

Critical parameters for design and development of multivalent nanoconstructs: recent trends - Avijit Kumar Bakshi; Tanweer Haider; Rahul Tiwari; Vandana Soni (Drug Delivery and Translational Research, 2022)

Management of chromium(VI)-contaminated soils through synergistic application of vermicompost, chromate reducing rhizobacteria and Arbuscular mycorrhizal fungi (AMF) reduced plant toxicity and improved yield attributes in Ocimum basilicum L. - Sumit K. Soni; Rakshapal Singh; Sudeep Tiwari (Archives of Microbiology, 2022)

Ada-GridRF: A Fast and Automated Adaptive Boost Based Grid Search Optimized Random Forest Ensemble model for Lung Cancer Detection - Ananya Bhattacharjee; R. Murugan; Badal Soni; Tripti Goel (Physical and Engineering Sciences in Medicine, 2022)

Opportunities and potential of green chemistry in nanotechnology - Ruma Arora Soni; Mohd. Aseel Rizwan; Surinder Singh (Nanotechnology for Environmental Engineering, 2022)

Assessment of variation in air quality over Delhi and neighbouring cities of Noida and Greater Noida - Deepak Sharma; V K Soni; Subhalaxmi Pradhan (Journal of Earth System Science, 2022)

A review on geothermal energy resources in India: past and the present - Mitul Prajapati; Manan Shah; Bhavna Soni (Environmental Science and Pollution Research, 2022)

Mechanisms and Pathways for Coordinated Control of Fine Particulate Matter and Ozone - Narendra Ojha; Meghna Soni; Manish Kumar; Sachin S. Gunthe; Ying Chen; Tabish U. Ansari (Current Pollution Reports, 2022)

Optimal vision-based guidance row locating for autonomous agricultural machines - Piyanun Ruangurai; Matthew N. Dailey; Mongkol Ekpanyapong; Peeyush Soni (Precision Agriculture, 2022)

Inhibition of Melanosis and Quality Changes on Indian White Prawn Treated with Lemon and Pomelo Peel Extracts Conjugated with Copper Sulfide Nanoparticles during Chilled Storage - Praveenkumar Pandiyan; Ajeet Soni; Preetham Elumalai (Journal of Aquatic Food Product Technology, 2022)

Optimal selection of representative climate models and statistical downscaling for climate change impact studies: a case study of Rhode Island, USA - Shiva Gopal Shrestha; Soni M. Pradhanang (Theoretical and Applied Climatology, 2022)

An overview on mechanism, cause, prevention and multi-nation policy level interventions of dietary iron deficiency - Abhishek Kulkarni; Monika Khade; Sharadha Arun; Pranesh Badami; G. Raja Krishna Kumar; Tomal Dattaroy; Badrish Soni; Santanu Dasgupta (Critical Reviews in Food Science and Nutrition, 2022)

Study of biochemical and biophysical adjustments during transition from desiccation-to-fully-hydrated states in Riccia gangetica and Semibarbula orientalis - Upma Bhatt; Vineet Soni (Vegetos, 2022)

Bio-enhancement of Soy Isoflavones (Genistein & Daidzein) Using Bacillus coagulans in Letrozole Induced Polycystic Ovarian Syndrome by Regulating Endocrine Hormones in Rats - Jeshica Bulsara; Arun Soni; Pragati Patil; Kripa Halpati; Sonal Desai; Sanjeev Acharya (Probiotics and Antimicrobial Proteins, 2022)

Neurological monitoring and sedation protocols in the Liver Intensive Care Unit - Rohit Mehtani; Shankey Garg; Kamal Kajal; Shiv Lal Soni; Madhumita Premkumar (Metabolic Brain Disease, 2022)

Comparative study of offshore wind energy potential assessment using different Weibull parameters estimation methods - Harsh Patidar; Vikas Shende; Prashant Baredar; Archana Soni (Environmental Science and Pollution Research, 2022)

Correction: COVID-19 and transportation of India: influence on infection risk and greenhouse gas emissions - Arti Roshan Soni; Kumar Amrit; Amar Mohan Shinde (Environment, Development and Sustainability, 2022)

Microbial production of multienzyme preparation from mosambi peel using Trichoderma asperellum - Balvindra Singh; Neelima Garg; Priti Mathur; Sumit K. Soni; Supriya Vaish; Sanjay Kumar (Archives of Microbiology, 2022)

Microbially-derived cocktail of carbohydrases as an anti-biofouling agents: a ‘green approach’ - Harmanpreet Kaur; Arashdeep Kaur; Sanjeev Kumar Soni; Praveen Rishi (Biofouling, 2022)

RETRACTED ARTICLE: Synergy of RHA and silica sand on physico-mechanical and tribological properties of waste plastic–reinforced thermoplastic composites as floor tiles - Ashish Soni; Pankaj Kumar Das; Mohammad Yusuf; Amjad Ali Pasha; Kashif Irshad; Mostefa Bourchak (Environmental Science and Pollution Research, 2022)

Synergistic action of Trichoderma koningiopsis and T. asperellum mitigates salt stress in paddy - Anshu Anshu; Pallavi Agarwal; Kumkum Mishra; Udit Yadav; Isha Verma; Soni Chauhan; Pankaj Kumar Srivastava; Poonam C. Singh (Physiology and Molecular Biology of Plants, 2022)

A techno-economic analysis of digital agriculture services: an ecological approach toward green growth - D. S. Gangwar; S. Tyagi; S. K. Soni (International Journal of Environmental Science and Technology, 2022)

In vitro models and ex vivo systems used in inflammatory bowel disease - Abhishek Joshi; Arun Soni; Sanjeev Acharya (In vitro models, 2022)

Seasonal dynamics of particulate matter pollution and its dispersion in the city of Delhi, India - Priyanka Sharma; Sunil Kumar Peshin; Vijay Kumar Soni; Siddhartha Singh; Gufran Beig; Chirashree Ghosh (Meteorology and Atmospheric Physics, 2022)

Advanced space rubidium atomic frequency standard for satellite navigation - Thejesh N. Bandi; N. M. Desai; J. Kaintura; D. Attri; M. A. Saiyed; R. Sharma-Kesarkar; P. Sinha; B. Ghoshal; S. Mandal; B. Ghosh; P. Jain; P. Priya; et al. (GPS Solutions, 2022)

Comparative Evaluation of Anti-Fibrotic Effect of Tissue Specific Mesenchymal Stem Cells Derived Extracellular Vesicles for the Amelioration of CCl4 Induced Chronic Liver Injury - Suchi Gupta; Pinky; Vishal; Harshita Sharma; Naina Soni; E Pranshu Rao; Manu Dalela; Alka Yadav; Nidhi Nautiyal; Anupam Kumar; Baibaswata Nayak; Arup Banerjee; et al. (Stem Cell Reviews and Reports, 2022)

Isolation and evaluation of fruit and seed mycoflora of bottle gourd (Lagenaria siceraria (Molina) Standl.) - Namita Soni; Kushal Raj (Indian Phytopathology, 2022)

Current advances in the synthetic strategies of 2-arylbenzothiazole - Ayushi Sethiya; Nusrat Sahiba; Pankaj Teli; Jay Soni; Shikha Agarwal (Molecular Diversity, 2022)

Kumquat essential oil decreases proliferation and activates JNK signaling and apoptosis in HT-1080 fibrosarcoma cells - Subah Soni; Mruga Y. Parekh; Jive A. Jacob; James P. Mack; Dorothy E. Lobo (Molecular and Cellular Biochemistry, 2022)

Application of cotton stalk biochar as a biosorbent for the removal of malachite green and its microwave-assisted regeneration - Arth Jayesh Shah; Bhavin Soni; Sanjib Kumar Karmee (Energy, Ecology and Environment, 2022)

Severe leaf-vein infestation upregulates antioxidant and photosynthetic activities in the lamina of Ficus religiosa - Upma Bhatt; Hanwant Singh; Deepak Kumar; Reto J. Strasser; Vineet Soni (Acta Physiologiae Plantarum, 2022)

In-Silico Design of a Novel Tridecapeptide Targeting Spike Protein of SARS-CoV-2 Variants of Concern - Sajjan Rajpoot; Kundan Solanki; Ashutosh Kumar; Kam Y. J. Zhang; Soni Savai Pullamsetti; Rajkumar Savai; Syed M. Faisal; Qiuwei Pan; Mirza S. Baig (International Journal of Peptide Research and Therapeutics, 2022)

Population structure analysis and marker trait association in selected set of Indian tomato (Solanum lycopersicum L.) varieties under high temperature condition - V. Amrutha; S. Shanija; R. Beena; N. Nithya; M. P. K. Jaslam; K. B. Soni; M. M. Viji (Genetic Resources and Crop Evolution, 2022)

Chemical composition and radiative forcing of atmospheric aerosols over the high-altitude Western Himalayas of India - Ashish Soni; Stefano Decesari; Harish Gadhavi; Marco Paglione; Douglas Orsini; Vijay Shridhar; Ujjwal Kumar; Francesca Volpi (Environmental Science and Pollution Research, 2022)

Biological control potential of an aphid parasitoid, Diaeretiella rapae (McIntosh) (Hymenoptera: Braconidae) against Brevicoryne brassicae (Linnaeus) (Hemiptera: Aphididae), a pest of oilseed brassicas in India - Saurbh Soni; Surjeet Kumar (International Journal of Tropical Insect Science, 2021)

Isolation and characterization of endophytic fungi having plant growth promotion traits that biosynthesizes bacosides and withanolides under in vitro conditions - Sumit K. Soni; Rakshapal Singh; Nem K. Ngpoore; Abhishek Niranjan; Purnima Singh; Aradhana Mishra; Sudeep Tiwari (Brazilian Journal of Microbiology, 2021)

Crop Health Assessment Using Sentinel-1 SAR Time Series Data in a Part of Central India - Sandeep Kumar Kaushik; Varun Narayan Mishra; Milap Punia; Pranaya Diwate; Thota Sivasankar; Anil Kumar Soni (Remote Sensing in Earth Systems Sciences, 2021)

Effective Treatment of Curry ( Murraya koenigii ) and Moringa ( Moringa oleifera ) Leaves Extracts on Melanosis of Pacific White Shrimp ( Litopenaeus vannamei ) during Chilled Storage - Ajeet Soni; Praveenkumar Pandiyan; Preetham Elumalai (Journal of Aquatic Food Product Technology, 2021)

Genome-wide identification and functional prediction of salt- stress related long non-coding RNAs (lncRNAs) in chickpea (Cicer arietinum L.) - Neeraj Kumar; Chellapilla Bharadwaj; Sarika Sahu; Aalok Shiv; Abhishek Kumar Shrivastava; Sneha Priya Pappula Reddy; Khela Ram Soren; Basavannagouda Siddannagouda Patil; Madan Pal; Anjali Soni; Manish Roorkiwal; Rajeev Kumar Varshney (Physiology and Molecular Biology of Plants, 2021)
LncRNAs (long noncoding RNAs) are 200 bp length crucial RNA molecules, lacking coding potential and having important roles in regulating gene expression, particularly in response to abiotic stresses. In this study, we identified salt stress-induced lncRNAs in chickpea roots and predicted their intricate regulatory roles. A total of 3452 novel lncRNAs were identified to be distributed across all 08 chickpea chromosomes. On comparing salt-tolerant (ICCV 10, JG 11) and salt-sensitive cultivars (DCP 92–3, Pusa 256), 4446 differentially expressed lncRNAs were detected under various salt treatments. We predicted 3373 lncRNAs to be regulating their target genes in cis regulating manner and 80 unique lncRNAs were observed as interacting with 136 different miRNAs, as eTMs (endogenous target mimic) targets of miRNAs and implicated them in the regulatory network of salt stress response. Functional analysis of these lncRNA revealed their association in targeting salt stress response-related genes like potassium transporter, transporter family genes, serine/threonine-protein kinase, aquaporins like TIP1-2, PIP2-5 and transcription factors like, AP2, NAC, bZIP, ERF, MYB and WRKY. Furthermore, about 614 lncRNA-SSRs (simple sequence repeats) were identified as a new generation of molecular markers with higher efficiency and specificity in chickpea. Overall, these findings will pave the understanding of comprehensive functional role of potential lncRNAs, which can help in providing insight into the molecular mechanism of salt tolerance in chickpea.

Flash flood risk assessment using geospatial technology in Shewa Robit town, Ethiopia - Awlachew Dejen; Sandeep Soni (Modeling Earth Systems and Environment, 2021)

Phytoremediation of cadmium-contaminated soil by Bidens pilosa L.: impact of pine needle biochar amendment - Sheetal Manori; Vijendra Shah; Vandana Soni; Kasturi Dutta; Achlesh Daverey (Environmental Science and Pollution Research, 2021)

Combined Analysis of Anti SARS-CoV-2 IgG and IgM Responses in COVID19 Patients in India - Mohana Kumari Chidananda; Deepy Zohmangaihi; Sant Ram; Shiv Lal Soni; Vikas Suri; Pankaj Malhotra; Ravjit Singh Jassal; Jyotdeep Kaur; Indu Verma; Sadhna Sharma (Indian Journal of Clinical Biochemistry, 2021)

Phytostimulation and biocontrol potential of Gram-positive endospore-forming Bacilli - Riteshri Soni; Hareshkumar Keharia (Planta, 2021)

Allantoin: Emerging Role in Plant Abiotic Stress Tolerance - Harmeet Kaur; Soni Chowrasia; Vikram Singh Gaur; Tapan Kumar Mondal (Plant Molecular Biology Reporter, 2021)

Engineering the AEG1 promoter from cotton to develop male sterile lines - Kamlesh Kumar Soni; Amita Kush Mehrotra; Pradeep Kumar Burma (Plant Cell Reports, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Integrated hydrochemical and ERT approach for seawater intrusion study in a coastal aquifer: a case study from Jafrabad Town, Gujarat State, India - Pandurang Balwant; V. Jyothi; Paras R. Pujari; A. Soni; C. Padmakar; R. Quamar; J. Ramesh; V. Gohel; A. Mishra (Environmental Monitoring and Assessment, 2021)

Establishment of a testis cell line from Clarias magur: a potential resource for in-vitro applications - Neha Singh; Pankaj Soni; Basdeo Kushwaha; Murali Sanjeev Kumar; J. K. Srivastava; Shreya Srivastava; Akhilesh Kumar Mishra; Ravindra Kumar (The Nucleus, 2021)

Green synthesis of xanthene and acridine-based heterocycles of pharmaceutical importance: a review - Anand S. Burange; Komal G. Gadam; Prajyot S. Tugaonkar; Seema D. Thakur; Ravish K. Soni; Rubej R. Khan; Mubashira S. Tai; Chinnakonda S. Gopinath (Environmental Chemistry Letters, 2021)

Effects of COVID-19 lockdown phases in India: an atmospheric perspective - Pramod Soni (Environment, Development and Sustainability, 2021)

Characterization of Arsenic-Resistant Klebsiella pneumoniae RnASA11 from Contaminated Soil and Water Samples and Its Bioremediation Potential - Prahalad Kumar; Biplab Dash; Deep Chandra Suyal; S. B. Gupta; Anup Kumar Singh; Tapas Chowdhury; Ravindra Soni (Current Microbiology, 2021)

Road Centerline Extraction From VHR Images Using SVM and Multi-Scale Maximum Response Filter - Pramod Kumar Soni; Navin Rajpal; Rajesh Mehta (Journal of the Indian Society of Remote Sensing, 2021)

Low oxygen tension potentiates proliferation and stemness but not multilineage differentiation of caprine male germline stem cells - Shiva Pratap Singh; Suresh Dinkar Kharche; Manisha Pathak; Ravi Ranjan; Yogesh Kumar Soni; Manoj Kumar Singh; Ramasamy Pourouchottamane; Manmohan Singh Chauhan (Molecular Biology Reports, 2021)

A Role for Extracellular Vesicles in SARS-CoV-2 Therapeutics and Prevention - Jatin Machhi; Farah Shahjin; Srijanee Das; Milankumar Patel; Mai Mohamed Abdelmoaty; Jacob D. Cohen; Preet Amol Singh; Ashish Baldi; Neha Bajwa; Raj Kumar; Lalit K. Vora; Tapan A. Patel; et al. (Journal of Neuroimmune Pharmacology, 2021)

Wastewater Treatment and Reuse: a Review of its Applications and Health Implications - Kavindra Kumar Kesari; Ramendra Soni; Qazi Mohammad Sajid Jamal; Pooja Tripathi; Jonathan A. Lal; Niraj Kumar Jha; Mohammed Haris Siddiqui; Pradeep Kumar; Vijay Tripathi; Janne Ruokolainen (Water, Air, & Soil Pollution, 2021)
Water scarcity is one of the major problems in the world and millions of people have no access to freshwater. Untreated wastewater is widely used for agriculture in many countries. This is one of the world-leading serious environmental and public health concerns. Instead of using untreated wastewater, treated wastewater has been found more applicable and ecofriendly option. Moreover, environmental toxicity due to solid waste exposures is also one of the leading health concerns. Therefore, intending to combat the problems associated with the use of untreated wastewater, we propose in this review a multidisciplinary approach to handle wastewater as a potential resource for use in agriculture. We propose a model showing the efficient methods for wastewater treatment and the utilization of solid wastes in fertilizers. The study also points out the associated health concern for farmers, who are working in wastewater-irrigated fields along with the harmful effects of untreated wastewater. The consumption of crop irrigated by wastewater has leading health implications also discussed in this review paper. This review further reveals that our current understanding of the wastewater treatment and use in agriculture with addressing advancements in treatment methods has great future possibilities.

Differential effects of extracellular matrix proteins on in vitro culture and growth characteristics of caprine male germ cells - Shiva Pratap Singh; Suresh Dinkar Kharche; Manisha Pathak; Ravi Ranjan; Yogesh Kumar Soni; Sonia Saraswat; Manoj Kumar Singh; Manmohan Singh Chauhan (In Vitro Cellular & Developmental Biology - Animal, 2021)

Arsenic efflux in Enterobacter cloacae RSN3 isolated from arsenic-rich soil - Biplab Dash; Narayan Sahu; Anup Kumar Singh; S.B Gupta; Ravindra Soni (Folia Microbiologica, 2021)

Indium sulfide-based photocatalysts for hydrogen production and water cleaning: a review - Vatika Soni; Pankaj Raizada; Abhinandan Kumar; Vasudha Hasija; Sonal Singal; Pardeep Singh; Ahmad Hosseini-Bandegharaei; Vijay Kumar Thakur; Van-Huy Nguyen (Environmental Chemistry Letters, 2021)

Cellular and physiological approaches to evaluate the chelating effect of Chlorella on metal ion stressed lymphocytes - Mahendra Yadav; Ravi Soni; Meenakshi Kanwar Chauhan; Nidhi Sandal (BioMetals, 2021)

Microbiome change of agricultural soil under organic farming practices - Deep Chandra Suyal; Ravindra Soni; Dhananjay Kumar Singh; Reeta Goel (Biologia, 2021)

Analysis of nonribosomal peptide synthetase genes in haemolymph microbes of marine crabs - Akhitha Mary Benny; Sumithra Thangalazhy Gopakumar; Reshma Kalarical Janardhanan; Anusree Velappan Nair; Neethu Bindu Raj; Amala Panaparambil Vakkachan; Ratheesh Kumar Raveendran; Soni Kallamparambil Balakrishnan; Sanil Nandiath Karayi (Archives of Microbiology, 2021)

Protective Role of Low Ethanol Administration Following Ischemic Stroke via Recovery of KCC2 and p75NTR Expression - Stanislav Khirug; Shetal Soni; Marta Saez Garcia; Marine Tessier; Liang Zhou; Natalia Kulesskaya; Heikki Rauvala; Dan Lindholm; Anastasia Ludwig; Florence Molinari; Claudio Rivera (Molecular Neurobiology, 2021)
A striking result from epidemiological studies show a correlation between low alcohol intake and lower incidence for ischemic stroke and severity of derived brain injury. Although reduced apoptosis and inflammation has been suggested to be involved, little is known about the mechanism mediating this effect in vivo. Increase in intracellular chloride concentration and derived depolarizing GABA A R-mediated transmission are common consequences following various brain injuries and are caused by the abnormal expression levels of the chloride cotransporters NKCC1 and KCC2. Downstream pro-apoptotic signaling through p75 NTR may link GABA A depolarization with post-injury neuronal apoptosis. Here, we show that changes in GABAergic signaling, Cl − homeostasis, and expression of chloride cotransporters in the post-traumatic mouse brain can be significantly reduced by administration of 3% ethanol to the drinking water. Ethanol-induced upregulation of KCC2 has a positive impact on neuronal survival, preserving a large part of the cortical peri-infarct zone, as well as preventing the massive post-ischemic upregulation of the pro-apoptotic protein p75 NTR . Importantly, intracortical multisite in vivo recordings showed that ethanol treatment could significantly ameliorate stroke-induced reduction in cortical activity. This surprising finding discloses a pathway triggered by low concentration of ethanol as a novel therapeutically relevant target.

A comprehensive study of different feature selection methods and machine-learning techniques for SODAR structure classification - Nishant Kumar; Kirti Soni; Ravinder Agarwal (Modeling Earth Systems and Environment, 2021)

Pharmacotherapeutics of SARS-CoV-2 Infections - Bhavesh D. Kevadiya; Jatin Machhi; Jonathan Herskovitz; Maxim D. Oleynikov; Wilson R. Blomberg; Neha Bajwa; Dhruvkumar Soni; Srijanee Das; Mahmudul Hasan; Milankumar Patel; Ahmed M. Senan; Santhi Gorantla; et al. (Journal of Neuroimmune Pharmacology, 2021)

Hydrogeochemical Assessment of Groundwater for Drinking and Agricultural Use: A Case Study of Rural Areas of Alwar, Rajasthan - Ankur Aggarwal; Jigyasa Soni; Khyati Sharma; Mohnish Sapra; Chitrakshi; Oznur Karaca; A. K. Haritash (Environmental Management, 2021)

Variability of durum wheat genotypes in terms of physio-biochemical traits against salinity stress - Shobha Soni; Ashwani Kumar; Nirmala Sehrawat; Naresh Kumar; Gurpreet Kaur; Arvind Kumar; Anita Mann (Cereal Research Communications, 2021)

A Comprehensive Review on 1st-Generation Biodiesel Feedstock Palm Oil: Production, Engine Performance, and Exhaust Emissions - Digambar Singh; Dilip Sharma; S. L. Soni; Chandrapal Singh Inda; Sumit Sharma; Pushpendra Kumar Sharma; Amit Jhalani (BioEnergy Research, 2021)

Molecular insights into the interplay between adiposity, breast cancer and bone metastasis - Sneha Soni; Meaghan Torvund; Chandi C. Mandal (Clinical & Experimental Metastasis, 2021)

Stem Cells Therapy as a Possible Therapeutic Option in Treating COVID-19 Patients - Diana Esquivel; Rangnath Mishra; Prabhat Soni; Rajasekar Seetharaman; Anjum Mahmood; Anand Srivastava (Stem Cell Reviews and Reports, 2021)

Empagliflozin suppresses inflammation and protects against acute septic renal injury - Zaid H. Maayah; Mourad Ferdaoussi; Shingo Takahara; Shubham Soni; Jason R. B. Dyck (Inflammopharmacology, 2021)

The caffeoyl-CoA O-methyltransferase gene SNP replacement in Russet Burbank potato variety enhances late blight resistance through cell wall reinforcement - Niranjan Hegde; Sripad Joshi; Nancy Soni; Ajjamada C. Kushalappa (Plant Cell Reports, 2021)

Molecular crowding accelerates aggregation of α-synuclein by altering its folding pathway - Soumojit Biswas; Antara Bhadra; Sunidhi Lakhera; Monika Soni; Venkataharsha Panuganti; Swati Jain; Ipsita Roy (European Biophysics Journal, 2021)

Impact of herbicide pretilachlor on reproductive physiology of walking catfish, Clarias batrachus (Linnaeus) - Rakesh Soni; Sushant Kumar Verma (Fish Physiology and Biochemistry, 2020)

Elucidation of genotype–environment interactions and genetic stability parameters for yield, quality and agromorphological traits in ashwagandha (Withania somnifera (L.) Dunal) - MITHLESH KUMAR; MANUBHAI PATEL; RAVINDRASINGH CHAUHAN; CHANDRESH TANK; SATYANARAYAN SOLANKI; PRAVINBHAI PATEL; HITENDRA BHADAURIA; RAMAN GAMI; KAREN PACHCHIGAR; NISHIT SONI; PRANAY PATEL; ANUJ SINGH; et al. (Journal of Genetics, 2020)

Assessment of frequency and severity of droughts in Maharashtra state of India - Kumar Amrit; Arti Roshan Soni; Sunayana; Surendra Kumar Mishra; Ritesh Vijay; Rakesh Kumar (Arabian Journal of Geosciences, 2020)

The biodiversity - N cycle relationship: a 15N tracer experiment with soil from plant mixtures of varying diversity to model N pool sizes and transformation rates - Soni Lama; Thomas Kuhn; Moritz F. Lehmann; Christoph Müller; Odette Gonzalez; Nico Eisenhauer; Markus Lange; Stefan Scheu; Yvonne Oelmann; Wolfgang Wilcke (Biology and Fertility of Soils, 2020)
We conducted a 15 N tracer experiment in laboratory microcosms with field-fresh soil samples from a biodiversity experiment to evaluate the relationship between grassland biodiversity and N cycling. To embrace the complexity of the N cycle, we determined N exchange between five soil N pools (labile and recalcitrant organic N, dissolved NH 4 + and NO 3 − in soil solution, and exchangeable NH 4 + ) and eight N transformations (gross N mineralization from labile and recalcitrant organic N, NH 4 + immobilization into labile and recalcitrant organic N, autotrophic nitrification, heterotrophic nitrification, NO 3 − immobilization, adsorption of NH 4 + ) expected in aerobic soils with the help of the N-cycle model Ntrace . We used grassland soil of the Jena Experiment, which includes plant mixtures with 1 to 60 species and 1 to 4 functional groups (legumes, grasses, tall herbs, small herbs). The 19 soil samples of one block of the Jena Experiment were labeled with either 15 NH 4 + or 15 NO 3 - or both. In the presence of legumes, gross N mineralization and autotrophic nitrification increased significantly because of higher soil N concentrations in legume-containing plots and high microbial activity. Similarly, the presence of grasses significantly increased the soil NH 4 + pool, gross N mineralization, and NH 4 + immobilization, likely because of enhanced microbial biomass and activity by providing large amounts of rhizodeposits through their dense root systems. In our experiment, previously reported plant species richness effects on the N cycle, observed in a larger-scale field experiment within the Jena Experiment, were not seen. However, specific plant functional groups had a significant positive impact on the N cycling in the incubated soil samples.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Plant diversity influenced gross nitrogen mineralization, microbial ammonium consumption and gross inorganic N immobilization in a grassland experiment - Soni Lama; Andre Velescu; Sophia Leimer; Alexandra Weigelt; Hongmei Chen; Nico Eisenhauer; Stefan Scheu; Yvonne Oelmann; Wolfgang Wilcke (Oecologia, 2020)
Gross rates of nitrogen (N) turnover inform about the total N release and consumption. We investigated how plant diversity affects gross N mineralization, microbial ammonium (NH 4 + ) consumption and gross inorganic N immobilization in grasslands via isotopic pool dilution. The field experiment included 74 plots with 1–16 plant species and 1–4 plant functional groups (legumes, grasses, tall herbs, small herbs). We determined soil pH, shoot height, root, shoot and microbial biomass, and C and N concentrations in soil, microbial biomass, roots and shoots. Structural equation modeling (SEM) showed that increasing plant species richness significantly decreased gross N mineralization and microbial NH 4 + consumption rates via increased root C:N ratios. Root C:N ratios increased because of the replacement of legumes (low C:N ratios) by small herbs (high C:N ratios) and an increasing shoot height, which was positively related with root C:N ratios, with increasing species richness. However, in our SEM remained an unexplained direct negative path from species richness to both N turnover rates. The presence of legumes increased gross N mineralization, microbial NH 4 + consumption and gross inorganic N immobilization rates likely because of improved N supply by N 2 fixation. The positive effect of small herbs on microbial NH 4 + consumption and gross inorganic N immobilization could be attributed to their increased rhizodeposition, stimulating microbial growth. Our results demonstrate that increasing root C:N ratios with increasing species richness slow down the N cycle but also that there must be additional, still unidentified processes behind the species richness effect potentially including changed microbial community composition.

Satish Chandra Maheshwari (1933–2019)—a brilliant, passionate and an outstanding shining light for all of plant biology - Ashwani Pareek; Vineet Soni; Sudhir K. Sopory; Jitendra P. Khurana; K. Sowjanya Sree; Akhilesh K. Tyagi; Sushila Narsimhan; Govindjee Govindjee (Physiology and Molecular Biology of Plants, 2020)

Correlation and time-series analysis of black carbon in the coal mine regions of India: a case study - Sidhu Jitendra Singh Makkhan; Kulwinder Singh Parmar; Sachin Kaushal; Kirti Soni (Modeling Earth Systems and Environment, 2020)

Assessment of Agricultural Drought in Upper Seonath Sub-Basin of Chhattisgarh (India) Using Remote Sensing and GIS-Based Indices - Himangshu Sarkar; Sandeep Soni; Ishtiyaq Ahmad; M. K. Verma (Journal of the Indian Society of Remote Sensing, 2020)

Estimation of Mine Water Quantity: Development of Guidelines for Indian Mines - A. K. Soni (Mine Water and the Environment, 2020)

Multilocus variable number tandem repeat analysis (MLVA)-typing of Brucella abortus isolates of India reveals limited genetic diversity - Maninder Singh; Mohd Ashraf Malik; Dhirender Kumar Singh; Soni Doimari; Bhavna; Rohini Sharma (Tropical Animal Health and Production, 2020)

First onsite net zero energy green building of India - K. M. Soni; P. Bhagat Singh (International Journal of Environmental Science and Technology, 2020)

Mercury, arsenic, lead and cadmium in waters of the Singrauli coal mining and power plants industrial zone, Central East India - Shefali Bhardwaj; Richa Soni; Sharad Kumar Gupta; Dericks P. Shukla (Environmental Monitoring and Assessment, 2020)

Production of bioethanol from biodegraded alkali pretreated rice straw - Rajendra Sonwani; S. B. Gupta; Ravindra Soni (Vegetos, 2020)

The Potato Tuber Moth, Phthorimaea operculella (Zeller), in India: Biology, Ecology, and Control - R. S. Chandel; Sumit Vashisth; Saurbh Soni; Rahul Kumar; Vinod Kumar (Potato Research, 2020)

The major lightning regions and associated casualties over India - Pramod Kumar Yadava; Manish Soni; Sunita Verma; Harshbardhan Kumar; Ajay Sharma; Swagata Payra (Natural Hazards, 2020)

Semiautomatic Road Extraction Framework Based on Shape Features and LS-SVM from High-Resolution Images - Pramod Kumar Soni; Navin Rajpal; Rajesh Mehta (Journal of the Indian Society of Remote Sensing, 2020)

Potential of low molecular weight natural polysaccharides for colon targeted formulation and its evaluation in human by Gamma Scintigraphy - S. P. Sawarkar; S. G. Deshpande; A. N. Bajaj; P. S. Soni; P. Pandit; V. S. Nikam (Journal of Pharmaceutical Investigation, 2020)

Improving nitrogen assessment with an RGB camera across uncertain natural light from above-canopy measurements - Bayu Taruna Widjaja Putra; Peeyush Soni (Precision Agriculture, 2020)

Electrochemical destruction of RB5 on Ti/PtOx–RuO2–SnO2–Sb2O5 electrodes: a comparison of two methods for electrode preparation - B. D. Soni; U. D. Patel; A. Agrawal; J. P. Ruparelia (International Journal of Environmental Science and Technology, 2020)

Brain Networks Communicate Through Theta Oscillations to Encode High Load in a Visuospatial Working Memory Task: An EEG Connectivity Study - Suriya Prakash Muthukrishnan; Sunaina Soni; Ratna Sharma (Brain Topography, 2020)

Sustainability assessment of crop production in accord with energy, environment and economic performances in Nepal - Anil Pokhrel; Peeyush Soni (Environmental Sustainability, 2019)

Influence of Process Parameters on Optimization of Biochar Fuel Characteristics Derived from Rice Husk: a Promising Alternative Solid Fuel - Krishna Yadav; Megha Tyagi; Soni Kumari; Sheeja Jagadevan (BioEnergy Research, 2019)

Development and validation of RP-HPLC method for the determination of stigmasterol in the botanical extract of Ficus deltoidea - Hayat Mohammad Mukhtar; Amandeep Singh; Varinder Soni; Atinderpal Singh; Hardeep Kaur (Natural Product Research, 2019)

Optimization of phosphate recovery as struvite from synthetic distillery wastewater using a chemical equilibrium model - Soni Kumari; Sanoj Jose; Sheeja Jagadevan (Environmental Science and Pollution Research, 2019)

Hydrologic and cost benefit analysis at local scale of streambed recharge structures in Rajasthan (India) and their value for securing irrigation water supplies - Y. Dashora; P. Dillon; B. Maheshwari; P. Soni; H. K. Mittal; R. Dashora; P. K. Singh; R. C. Purohit; P. Katara (Hydrogeology Journal, 2019)

Implication of data uncertainty in the detection of surface radiation trends and observational evidence of renewed solar dimming over India - Pramod Soni; Rajesh Srivastava; Shivam Tripathi (Theoretical and Applied Climatology, 2019)

A conceptual framework of agroecological resource management system for climate-smart agriculture - D. S. Gangwar; S. Tyagi; S. K. Soni (International Journal of Environmental Science and Technology, 2019)

The foraging behaviour of Aphelinus asychis Walker (Hymenoptera: Aphelinidae) and Aphidius ervi (Haliday) (Hymenoptera: Braconidae) on Myzus persicae (Sulzer) (Hemiptera: Aphididae) - Surjeet Kumar; Shruti Kashyap; Saurbh Soni (Phytoparasitica, 2019)

Improving strategies for sustainability of short-term agricultural utilization on degraded peatlands in Central Kalimantan - Arif Surahman; Peeyush Soni; Ganesh P. Shivakoti (Environment, Development and Sustainability, 2019)

Bayesian analysis of the impact of rainfall data product on simulated slope failure for North Carolina locations - Soni Yatheendradas; Dalia Kirschbaum; Grey Nearing; Jasper A. Vrugt; Rex L. Baum; Rick Wooten; Ning Lu; Jonathan W. Godt (Computational Geosciences, 2019)

Performance Evaluation of AquaCrop and DSSAT-CERES for Maize Under Different Irrigation and Manure Application Rates in the Himalayan Region of India - Mukand S. Babel; Proloy Deb; Peeyush Soni (Agricultural Research, 2019)

A new approach to generalizing riparian water and air quality function across regions - Yasaman T. Hassanzadeh; Philippe G. Vidon; Arthur J. Gold; Soni M. Pradhanang; Kelly Addy (Environmental Monitoring and Assessment, 2019)

Genotyping-by-sequencing based genetic mapping reveals large number of epistatic interactions for stem rot resistance in groundnut - Sneha M. Dodia; Binal Joshi; Sunil S. Gangurde; Polavakkalipalayam P. Thirumalaisamy; Gyan P. Mishra; Dayama Narandrakumar; Pooja Soni; Arulthambi L. Rathnakumar; Jentilal R. Dobaria; Chandramohan Sangh; Annapurna Chitikineni; Sumitra V. Chanda; et al. (Theoretical and Applied Genetics, 2019)

Long-term (2005–2012) measurements of near-surface air pollutants at an urban location in the Indo-Gangetic Basin - N Kishore; A K Srivastava; Hemwati Nandan; Chhavi P Pandey; S Agrawal; N Singh; V K Soni; D S Bisht; S Tiwari; Manoj K Srivastava (Journal of Earth System Science, 2019)

Stenotrophomonas: a versatile diazotrophic bacteria from the rhizospheric soils of Western Himalayas and development of its liquid biofertilizer formulation - Ajay Kumar; Ruchi Soni; Sarbjit Singh Kanwar; Sunil Pabbi (Vegetos, 2019)

Life cycle assessment research and application in Indonesia - Edi Iswanto Wiloso; Novizar Nazir; Jessica Hanafi; Kiman Siregar; Soni Sisbudi Harsono; Arief Ameir Rahman Setiawan; Muryanto; Muhammad Romli; Nuki Agya Utama; Bayuni Shantiko; Joni Jupesta; Tri Hendro Atmoko Utomo; et al. (The International Journal of Life Cycle Assessment, 2019)

RGD Peptide as a Targeting Moiety for Theranostic Purpose: An Update Study - Saket Asati; Vikas Pandey; Vandana Soni (International Journal of Peptide Research and Therapeutics, 2019)

A durability study of a compression ignition engine operating with Thumba (Citrullus colocyntis) vegetable oil - Narayan Lal Jain; Shyam Lal Soni; M. P. Poonia; Dilip Sharma; Anmesh K Srivastava; Hardik Jain (Environmental Science and Pollution Research, 2019)

A comprehensive review on water-emulsified diesel fuel: chemistry, engine performance and exhaust emissions - Amit Jhalani; Dilip Sharma; Shyam Lal Soni; Pushpendra Kumar Sharma; Sumit Sharma (Environmental Science and Pollution Research, 2019)

Aerosol and pollutant characteristics in Delhi during a winter research campaign - Umesh C. Dumka; Suresh Tiwari; Dimitris G. Kaskaoutis; Vijay K. Soni; Promod D. Safai; Shiv D. Attri (Environmental Science and Pollution Research, 2019)

Biophysical Characterization of SG2NA Variants and their Interaction with DJ-1 and Calmodulin in vitro - Sangeeta Soni; Buddhi Prakash Jain; Richa Gupta; Sudhaker Dharavath; Karunakar Kar; Sneha Sudha Komath; Shyamal K Goswami (Cell Biochemistry and Biophysics, 2018)

Calcium alginate encapsulated synthetic seed production in Plumbago rosea L. for germplasm exchange and distribution - Anand Vishnu Prakash; Deepa S. Nair; Swapna Alex; K. B. Soni; M. M. Viji; B. R. Reghunath (Physiology and Molecular Biology of Plants, 2018)

Aerosol columnar characteristics and their heterogeneous nature over Varanasi, in the central Ganges valley - Shani Tiwari; Dimitris Kaskaoutis; Vijay Kumar Soni; Shiv Dev Attri; Abhay Kumar Singh (Environmental Science and Pollution Research, 2018)

Genetic analysis of persistency in HF crossbred cattle at an organized farm of northern India - Nisha Sharma; Raman Narang; Neeraj Kashyap; Soni Kumari; Simarjeet Kaur; Poonam Ratwan (Tropical Animal Health and Production, 2018)

Epidemio-Clinico-Microbiological Study of Mycotic Keratitis in North-West Region of Rajasthan - Abhishek Binnani; Priyanka Soni Gupta; Ankur Gupta (Mycopathologia, 2018)

Assessment of total columnar ozone climatological trends over the Indian sub-continent - Mahesh Pathakoti; Lakshmi Kanchana Asuri; Mahalakshmi Dangeti Venkata; Sujatha Peethani; Sreenivas Gaddamidi; Vijay Kumar Soni; Sunil Kumar Peshin (International Journal of Remote Sensing, 2018)

Managing aquifer recharge and sustaining groundwater use: developing a capacity building program for creating local groundwater champions - Y. Jadeja; B. Maheshwari; R. Packham; Hakimuddin Bohra; R. Purohit; B. Thaker; P. Dillon; S. Oza; S. Dave; P. Soni; Y. Dashora; R. Dashora; et al. (Sustainable Water Resources Management, 2018)

A simple method using farmers’ measurements applied to estimate check dam recharge in Rajasthan, India - Y. Dashora; P. Dillon; B. Maheshwari; P. Soni; R. Dashora; S. Davande; R. C. Purohit; H. K. Mittal (Sustainable Water Resources Management, 2018)

A Case Study: Heavy Rainfall Event Comparison Between Daily Satellite Rainfall Estimation Products with IMD Gridded Rainfall Over Peninsular India During 2015 Winter Monsoon - Anil Kumar Singh; Virendra Singh; K. K. Singh; Jayant Nath Tripathi; Amit Kumar; Anil Kumar Soni; M. Sateesh; Chinmay Khadke (Journal of the Indian Society of Remote Sensing, 2018)

Osteogenic Nanofibrous Coated Titanium Implant Results in Enhanced Osseointegration: In Vivo Preliminary Study in a Rabbit Model - Siddhartha Das; Sandeep Gurav; Vivek Soni; Arvind Ingle; Bhabani S. Mohanty; Pradip Chaudhari; Kiran Bendale; Kanchan Dholam; Jayesh R. Bellare (Tissue Engineering and Regenerative Medicine, 2018)

Radiative effects of black carbon aerosols on Indian monsoon: a study using WRF-Chem model - Pramod Soni; Sachchida Nand Tripathi; Rajesh Srivastava (Theoretical and Applied Climatology, 2018)

Enhanced broadband greenness in assessing Chlorophyll a and b, Carotenoid, and Nitrogen in Robusta coffee plantations using a digital camera - Bayu Taruna Widjaja Putra; Peeyush Soni (Precision Agriculture, 2018)

Effect of injection pressure on performance, emission, and combustion characteristics of diesel–acetylene-fuelled single cylinder stationary CI engine - Anmesh Kumar Srivastava; Shyam Lal Soni; Dilip Sharma; Narayan Lal Jain (Environmental Science and Pollution Research, 2018)

Biotechnological potential of microbial inulinases: Recent perspective - Hemant Kumar Rawat; Hemant Soni; Helen Treichel; Naveen Kango (Critical Reviews in Food Science and Nutrition, 2017)

Effect of Protected Fat as Ca-Soap and Formaldehyde-Treated Full-Fat Soybean in the Finisher Diet of Lambs on Growth Performance, Carcass Traits and Fatty Acid Profile - Randhir Singh Bhatt; A. Sahoo; Lalit Kumar Soni; Y. P. Gadekar (Agricultural Research, 2017)

The pattern of secondary cancers in patients with Kaposi sarcoma in the United States - Vivek Kumar; Mohit Garg; Neha Chaudhary; Parita Soni; Charalampos S. Floudas; Chiemeziem Nwanyanwu; Abhinav Chandra (Cancer Causes & Control, 2017)

Modeling of air pollution in residential and industrial sites by integrating statistical and Daubechies wavelet (level 5) analysis - Kirti Soni; Kulwinder Singh Parmar; Sanjeev Agrawal (Modeling Earth Systems and Environment, 2017)

Experimental investigation of performance and emissions of a VCR diesel engine fuelled with n-butanol diesel blends under varying engine parameters - Ashish Nayyar; Dilip Sharma; Shyam Lal Soni; Alok Mathur (Environmental Science and Pollution Research, 2017)

Modeling of air pollutants using least square support vector regression, multivariate adaptive regression spline, and M5 model tree models - Ozgur Kisi; Kulwinder Singh Parmar; Kirti Soni; Vahdettin Demir (Air Quality, Atmosphere & Health, 2017)

Effect of Honey on Quality Characteristics of Mutton Spread - Suman Talukder; Sanjod Kumar Mendiratta; Tarun Pal Singh; Ashish Kumar; Rajiv Ranjan Kumar; Arvind Soni (Agricultural Research, 2017)

Active oxygen species metabolism in neem (Azadirachta indica) seeds exposed to natural ageing and controlled deterioration - Alok Kumar Sahu; Balram Sahu; Avinash Soni; Subhash Chandra Naithani (Acta Physiologiae Plantarum, 2017)

Oxidative Stress and Genotoxicity of Zinc Oxide Nanoparticles to Pseudomonas Species, Human Promyelocytic Leukemic (HL-60), and Blood Cells - Deepika Soni; Deepa Gandhi; Prashant Tarale; Amit Bafana; R.A. Pandey; Saravanadevi Sivanesan (Biological Trace Element Research, 2017)

Effect of compression ratio on performance, emission and combustion characteristics of diesel–acetylene-fuelled single-cylinder stationary CI engine - Anmesh Kumar Srivastava; Shyam Lal Soni; Dilip Sharma; Deepesh Sonar; Narayan Lal Jain (Clean Technologies and Environmental Policy, 2017)

SGNH hydrolase-type esterase domain containing Cbes-AcXE2: a novel and thermostable acetyl xylan esterase from Caldicellulosiruptor bescii - Surabhi Soni; Sneha S. Sathe; Annamma A. Odaneth; Arvind M. Lali; Sanjeev K. Chandrayan (Extremophiles, 2017)

SODAR pattern classification and its dependence on meteorological parameters over a semiarid region of India - Nishant Kumar; Kirti Soni; Naveen Garg; Ravinder Agarwal; D. Saha; Mahavir Singh; Gurbir Singh (International Journal of Remote Sensing, 2017)

In Vitro Selection of Cell Lines in Punica granatum L. (Daru) Against Bacterial Blight - Garima Kumari; Kamlesh Kanwar; Madhvi Soni; Deepika Sharma (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2017)

Size distribution and roundness of clasts within pseudotachylytes of the Gangavalli Shear Zone, Salem, Tamil Nadu: An insight into its origin and tectonic significance - Bhuban Mohan Behera; V Thirukumaran; Aishwaraya Soni; Prasanta Kumar Mishra; Tapas Kumar Biswal (Journal of Earth System Science, 2017)

Comparative Study of Two ELISA Kits for Estimation of Antibodies to Hepatitis B Virus in Human Normal Immunoglobulin and Specific Immunoglobulin Intended for Intravenous or Intramuscular Use - J. P. Prasad; Y. Madhu; Arushi Mandhan; Payal Garg; Anu Prakash; Varsha Singh; Daud Ali; Prdeep Kumar; Surinder Singh; G. R. Soni; Varun Singh (Indian Journal of Clinical Biochemistry, 2017)

Experimental investigation of impact of diesel particulate filter on smoke and NOx emissions of a Euro-I compression ignition engine with active and off-board regeneration - Pradeep Kumar Gupta; Dilip Sharma; Shyam Lal Soni; Rahul Goyal; Dheeraj Kishor Johar (Clean Technologies and Environmental Policy, 2017)

Investigation of dominant modes of monsoon ISO in the northwest and eastern Himalayan region - Sandipan Mukherjee; Srabanti Ballav; Sandeep Soni; Kireet Kumar; Utpal Kumar De (Theoretical and Applied Climatology, 2016)

Morphological and molecular characterization of powdery mildew on sunflower (Helianthus annuus L.), alternate hosts and weeds commonly found in and around sunflower fields in India - Sujatha Mulpuri; Prashant Kumar Soni; Suresh Kumar Gonela (Phytoparasitica, 2016)

Modeling landslide susceptibility over large regions with fuzzy overlay - Dalia Kirschbaum; Thomas Stanley; Soni Yatheendradas (Landslides, 2016)

Anthocyanins Based Indicator Sensor for Intelligent Packaging Application - Vivek Shukla; Gurunathan Kandeepan; Mangalathu Rajan Vishnuraj; Arvind Soni (Agricultural Research, 2016)

Variability in optical properties of atmospheric aerosols and their frequency distribution over a mega city “New Delhi,” India - S. Tiwari; Suresh Tiwari; P. K. Hopke; S. D. Attri; V. K. Soni; Abhay Kumar Singh (Environmental Science and Pollution Research, 2016)

Endocannabinoid CB1 receptor-mediated rises in Ca2+ and depolarization-induced suppression of inhibition within the laterodorsal tegmental nucleus - Neeraj Soni; Kristi A. Kohlmeier (Brain Structure and Function, 2016)

Hyperhomocysteinemia Alters Sinoatrial and Atrioventricular Nodal Function: Role of Magnesium in Attenuating These Effects - Chirag V. Soni; Suresh C. Tyagi; Nathan D. Todnem; Srikanth Givvimani; Sathnur B. Pushpakumar; Juan Villafane; Claudio Maldonado (Cell Biochemistry and Biophysics, 2016)

Drought risk assessment in central Nepal: temporal and spatial analysis - Piyush Dahal; Nicky Shree Shrestha; Madan Lall Shrestha; Nir Y. Krakauer; Jeeban Panthi; Soni M. Pradhanang; Ajay Jha; Tarendra Lakhankar (Natural Hazards, 2016)

Development and Optimization of Gastro-Retentive Controlled-Release Tablet of Calcium-Disodium Edentate and its In Vivo Gamma Scintigraphic Evaluation - Neeraj Kumar; Sandeep Soni; Thakuri Singh; Amit Kumar; Farhan Jalees Ahmad; Aseem Bhatnagar; Gaurav Mittal (AAPS PharmSciTech, 2015)

A three-point time series study of antibiotic usage on an intensive care unit, following an antibiotic stewardship programme, after an outbreak of multi-resistant Acinetobacter baumannii - S. Singh; Y. Z. Zhang; S. Chalkley; K. Ananthan; E. Demertzi; M. Beach; M. Cohen; V. Grover; C. Chung; J. Tatlock; N. Soni; B. Azadian (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Biochemical and Molecular Alterations Following Arsenic-Induced Oxidative Stress and Mitochondrial Dysfunction in Rat Brain - Chandra Prakash; Manisha Soni; Vijay Kumar (Biological Trace Element Research, 2015)

Seepage Modeling for a Large Open Pit Coal Mine in India - A. K. Soni; Bhavika Manwatkar (Geotechnical and Geological Engineering, 2015)

Performance and emission characteristics of a diesel engine with varying injection pressure and fuelled with raw mahua oil (preheated and blends) and mahua oil methyl ester - Deepesh Sonar; S. L. Soni; Dilip Sharma; Anmesh Srivastava; Rahul Goyal (Clean Technologies and Environmental Policy, 2015)

Fast-Dissolving Films of Sumatriptan Succinate: Factorial Design to Optimize In Vitro Dispersion Time - Govind Soni; Khushwant S. Yadav (Journal of Pharmaceutical Innovation, 2015)

Structural monitoring for the rail industry using conventional survey, laser scanning and photogrammetry - Anita Soni; Stuart Robson; Barry Gleeson (Applied Geomatics, 2015)

Time series model prediction and trend variability of aerosol optical depth over coal mines in India - Kirti Soni; Kulwinder Singh Parmar; Sangeeta Kapoor (Environmental Science and Pollution Research, 2015)

Apoptosis imaging studies in various animal models using radio-iodinated peptide - Wonjung Kwak; Yeong Su Ha; Nisarg Soni; Woonghee Lee; Se-Il Park; Heesu Ahn; Gwang Il An; In-San Kim; Byung-Heon Lee; Jeongsoo Yoo (Apoptosis, 2015)

Phylogenetic analysis of the Listeria monocytogenes based on sequencing of 16S rRNA and hlyA genes - Dharmendra Kumar Soni; Suresh Kumar Dubey (Molecular Biology Reports, 2014)

Flyrock in bench blasting: a comprehensive review - A. K. Raina; V. M. S. R. Murthy; A. K. Soni (Bulletin of Engineering Geology and the Environment, 2014)

Radiation and energy balance dynamics over young chir pine (Pinus roxburghii) system in Doon of western Himalayas - Nilendu Singh; Bimal K Bhattacharya; M K Nanda; Prafulla Soni; Jai Singh Parihar (Journal of Earth System Science, 2014)

Synthesis of new naphthoisoxazole amide derivatives and study of their biological evaluations - Shubhangi S. Soman; Jigar N. Soni; Timir B. Patel (Medicinal Chemistry Research, 2014)

Isolation and Characterization of a Nitrile-Hydrolysing Bacterium Isoptericola variabilis RGT01 - Gurdeep Kaur; Pankaj Soni; Rupinder Tewari; Rohit Sharma (Indian Journal of Microbiology, 2014)

Lime and Sulphide-Free Dehairing of Animal Skin Using Collagenase-Free Alkaline Protease from Vibrio metschnikovii NG155 - Nancy George; Sonica Sondhi; Sanjeev Kumar Soni; Naveen Gupta (Indian Journal of Microbiology, 2014)

Pretreatment of Cr(VI)-Amended Soil With Chromate-Reducing Rhizobacteria Decreases Plant Toxicity and Increases the Yield of Pisum sativum - Sumit K. Soni; Rakshapal Singh; Mangal Singh; Ashutosh Awasthi; Kundan Wasnik; Alok Kalra (Archives of Environmental Contamination and Toxicology, 2014)

Artificial Bee Colony-based satellite image contrast and brightness enhancement technique using DWT-SVD - Ashish Kumar Bhandari; Vivek Soni; Anil Kumar; Girish Kumar Singh (International Journal of Remote Sensing, 2014)

Structural characterization and mutational assessment of podocin — A novel drug target to nephrotic syndrome — An in silico approach - Asra Tabassum; Tadigadapa Rajeshwari; Nidhi Soni; D. S. B. Raju; Mukesh Yadav; Anuraj Nayarisseri; Parveen Jahan (Interdisciplinary Sciences: Computational Life Sciences, 2014)

A Cr(VI)-reducing Microbacterium sp. strain SUCR140 enhances growth and yield of Zea mays in Cr(VI) amended soil through reduced chromium toxicity and improves colonization of arbuscular mycorrhizal fungi - Sumit K. Soni; Rakshapal Singh; Ashutosh Awasthi; Alok Kalra (Environmental Science and Pollution Research, 2014)

Ground penetrating radar (GPR) study to detect seepage pathways in the Ajanta Caves in India - Paras R. Pujari; Abhay Soni; C. Padmakar; Piyush Mahore; Ramya Sanam; P. Labhasetwar (Bulletin of Engineering Geology and the Environment, 2014)

Long-term Aerosol Characteristics over Eastern, Southeastern, and South Coalfield Regions in India - Kirti Soni; Sangeeta Kapoor; Kulwinder Singh Parmar (Water, Air, & Soil Pollution, 2014)

Rapid in vitro propagation, conservation and analysis of genetic stability of Viola pilosa - Madhvi Soni; Rajinder Kaur (Physiology and Molecular Biology of Plants, 2014)

Aerosol particle behavior during Dust Storm and Diwali over an urban location in north western India - Divya Prakash; Swagata Payra; Sunita Verma; Manish Soni (Natural Hazards, 2013)

Genotoxicity evaluation of asymmetric lipid polymer hybrid nanoparticles of doxycycline hydrochloride following intravenous administration - Maheshkumar P. Soni; Madhuvanti V. Mahajan; Rohit V. Dhumal; Sharad Bhagat; Dinesh Tiwari; Rajiv V. Gaikwad; Abdul Samad; Padma V. Devarajan; Geeta R. Vanage (Drug Delivery and Translational Research, 2013)

Generation of superior germplasm of Jatropha curcas through ex vitro grafting - Sarina Panghal; V. S. Beniwal; Shashi Shanker Soni (Agroforestry Systems, 2013)

Dust events and their influence on aerosol optical properties over Jaipur in Northwestern India - Sunita Verma; Swagata Payra; Ritesh Gautam; Divya Prakash; Manish Soni; Brent Holben; Shaun Bell (Environmental Monitoring and Assessment, 2013)

A suite of new genes defining salinity stress tolerance in seedlings of contrasting rice genotypes - Neelam Soda; Hemant R. Kushwaha; Praveen Soni; Sneh L. Singla-Pareek; Ashwani Pareek (Functional & Integrative Genomics, 2013)

Synthesis of novel 4,6-diaryl-2-aminopyrimidines as potential antiplasmodial agents - Rajani Giridhar; Riyaj S. Tamboli; Dhaval G. Prajapati; Sanket Soni; Sarita Gupta; M. R. Yadav (Medicinal Chemistry Research, 2013)

Diversity of Halophilic Archaea at Salt Pans Around Bhavnagar Coast, Gujarat - Bharti P. Dave; Apexa Soni (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2013)

A novel thermotolerant Pediococcus acidilactici B-25 strain for color, COD, and BOD reduction of distillery effluent for end use applications - Soni Tiwari; Priyanka Rai; Santosh Kumar Yadav; Rajeeva Gaur (Environmental Science and Pollution Research, 2013)

In vitro Cr(VI) reduction by cell-free extracts of chromate-reducing bacteria isolated from tannery effluent irrigated soil - Sumit K. Soni; Rakshapal Singh; Ashutosh Awasthi; Mangal Singh; Alok Kalra (Environmental Science and Pollution Research, 2013)

An Insight Into the Production, Characterization, and Mechanisms of Action of Low-Cost Adsorbents for Removal of Organics From Aqueous Solution - S. Kushwaha; H. Soni; V. Ageetha; P. Padmaja (Critical Reviews in Environmental Science and Technology, 2013)

Synergy between Glomus fasciculatum and a beneficial Pseudomonas in reducing root diseases and improving yield and forskolin content in Coleus forskohlii Briq. under organic field conditions - Rakshapal Singh; Sumit K. Soni; Alok Kalra (Mycorrhiza, 2013)

Application of low altitude remote sensing (LARS) platform for monitoring crop growth and weed infestation in a soybean plantation - Grianggai Samseemoung; Peeyush Soni; Hemantha P. W. Jayasuriya; Vilas M. Salokhe (Precision Agriculture, 2012)

Anti-microbial benzimidazole derivatives: synthesis and in vitro biological evaluation - Love Kumar Soni; Tamanna Narsinghani; Anand Sethi (Medicinal Chemistry Research, 2012)

Characterization of Soy Polysaccharide and Its In Vitro and In Vivo Evaluation for Application in Colon Drug Delivery - B. M. Ursekar; P. S. Soni; Abhijit A. Date; M. S. Nagarsenker (AAPS PharmSciTech, 2012)

Evaluation of vermicompost doses for management of root-rot disease complex in Coleus forskohlii under organic field conditions - R. Singh; S. K. Soni; A. Awasthi; A. Kalra (Australasian Plant Pathology, 2012)

Nymphasterol, a new steroid from Nymphaea stellata - Amita Verma; Bahar Ahmed; Rucha Upadhyay; Neetu Soni (Medicinal Chemistry Research, 2012)

Immunopathology and Th1/Th2 immune response of Campylobacter jejuni-induced paralysis resembling Guillain–Barré syndrome in chicken - Kishan K. Nyati; Kashi N. Prasad; Nagendra K. Kharwar; Priyanka Soni; Nuzhat Husain; Vinita Agrawal; Arun K. Jain (Medical Microbiology and Immunology, 2012)

Evaluation of long‐term changes of solar radiation in India - V. K. Soni; G. Pandithurai; D. S. Pai (International Journal of Climatology, 2012)
Temporal and spatial variability in annually averaged global irradiance, diffuse irradiance, and bright sunshine duration over twelve stations of solar radiation network of India Meteorological Department (IMD) were evaluated for the period 1971–2005. Annually averaged all‐sky global irradiance decreased between 0.1% (0.3 Wm −2 ) and 3.6% (9.0 Wm −2 ) per decade at the stations. The decrease in sunshine duration was concomitant with the decrease in global solar irradiance. The long‐term trends in diffuse irradiance differed markedly between the twelve stations. Significant increasing trend in diffuse irradiance were found at the four stations under all‐sky conditions, while seven stations showed increasing trend under clear sky conditions. The two most probable causes of long‐term trends in radiation are changes in aerosol loading and cloud cover. Trend analyses of Angstrom's turbidity coefficient measured at three stations of IMD during the last three decades indicate that total column aerosol has increased significantly. Trend analysis of bright sunshine duration suggests long‐term decrease at all the stations. Reduction in bright sunshine hours varied from 0.0 to 0.5 h per decade. There is a strong northwest‐northeast gradient in sunshine duration which contributes to the spatial trends in global and diffuse solar irradiance. This paper examines the trends of global irradiance, diffuse irradiance and sunshine duration over India in all‐sky conditions as well as cloud‐free skies so the effect of cloud cover can be examined. Copyright © 2011 Royal Meteorological Society

Spatial assessment of climate change effects on crop suitability for major plantation crops in Sri Lanka - P. M. S. Jayathilaka; Peeyush Soni; Sylvain R. Perret; H. P. W. Jayasuriya; Vilas M. Salokhe (Regional Environmental Change, 2012)

Synthesis, anticonvulsant and neurotoxic activity of some new 2,5-disubstituted-1,3,4-oxadiazoles - Neha Jain; Sushil K. Kashaw; R. K. Agrawal; Anjali Gupta; Abhishek Soni (Medicinal Chemistry Research, 2011)

Immunosuppressive activity of hexane and ethanolic extracts of Pterospermum acerifolium seeds in BALB/c mice - Manisha Pathak; Nasreen Bano; Preety Dixit; Vishal Kumar Soni; Padam Kumar; Rakesh Maurya; Shailja Misra-Bhattacharya (Medicinal Chemistry Research, 2011)

Design and synthesis of some novel 3-[5-(4-substituted) phenyl-1,3,4-oxadiazole-2yl]-2-phenylquinazoline-4(3H)-ones as possible anticonvulsant agent - Anjali Gupta; Sushil K. Kashaw; Neha Jain; Harish Rajak; Abhishek Soni; J. P. Stables (Medicinal Chemistry Research, 2011)

Variation in aerosol black carbon concentration and its emission estimates at the mega-city Delhi - Tarannum Bano; Sachchidanand Singh; N. C. Gupta; Kirti Soni; R. S. Tanwar; S. Nath; B. C. Arya; B. S. Gera (International Journal of Remote Sensing, 2011)

Purification and characterization of two distinct acidic phytases with broad pH stability from Aspergillus niger NCIM 563 - S. K. Soni; A. Magdum; J. M. Khire (World Journal of Microbiology and Biotechnology, 2010)

Analysis of physicochemical properties for drugs from nature - B. R. Prashantha Kumar; Mukesh Soni; U. Bharvi Bhikhalal; Ismayil R. Kakkot; Meghana Jagadeesh; Praveen Bommu; M. J. Nanjan (Medicinal Chemistry Research, 2010)

To Study the Effect of Diet Supplementation with Coconut Oil, Mustard Oil and Sunflower Oil on Blood Lipids in Rabbit - N. D. Soni; Urmila Choudhary; Praveen Sharma; Amitabh Dube (Indian Journal of Clinical Biochemistry, 2010)

m-Calpain-mediated cleavage of Na+/Ca2+ exchanger-1 in caveolae vesicles isolated from pulmonary artery smooth muscle - Soni Shaikh; Krishna Samanta; Pulak Kar; Soumitra Roy; Tapati Chakraborti; Sajal Chakraborti (Molecular and Cellular Biochemistry, 2010)

Salmonella brain abscess in a patient on chronic azathioprine therapy for myasthenia gravis: report of an unusual case and review of literature in the postantibiotic era - Chetan R Soni; Gyanendra Kumar; Pradeep C Bollu; Pradeep Sahota; N. Scott Litofsky (Journal of NeuroVirology, 2010)

Nanoparticle-mediated targeting of phosphatidylinositol-3-kinase signaling inhibits angiogenesis - Rania Harfouche; Sudipta Basu; Shivani Soni; Dirk M. Hentschel; Raghunath A. Mashelkar; Shiladitya Sengupta (Angiogenesis, 2009)

Development of Budesonide Microparticles Using Spray-Drying Technology for Pulmonary Administration: Design, Characterization, In Vitro Evaluation, and In Vivo Efficacy Study - Sonali R. Naikwade; Amrita N. Bajaj; Prashant Gurav; Madhumanjiri M. Gatne; Pritam Singh Soni (AAPS PharmSciTech, 2009)

Purification and characterization of an endoglucanase from Aspergillus terreus highly active against barley β-glucan and xyloglucan - Asiya Nazir; Rohit Soni; H. S. Saini; R. K. Manhas; B. S. Chadha (World Journal of Microbiology and Biotechnology, 2009)

Sea water intrusion studies near Kovaya limestone mine, Saurashtra coast, India - Paras R. Pujari; Abhay K. Soni (Environmental Monitoring and Assessment, 2009)

Exploration of Csp Genes from Temperate and Glacier Soils of the Indian Himalayas and In Silico Analysis of Encoding Proteins - Prema K. Latha; Ravindra Soni; Mahejibin Khan; Soma S. Marla; Reeta Goel (Current Microbiology, 2009)

Biodegradation of high explosive production effluent containing RDX and HMX by denitrifying bacteria - Rita Singh; Pramod Soni; Pawan Kumar; Sumita Purohit; Antaryami Singh (World Journal of Microbiology and Biotechnology, 2009)

Estimation of forest biophysical variables from Indian Earth Observation Satellite Cartosat‐1 stereo data - M. M. Kimothi; S. Mohan; R. B. Singh; P. Soni; H. B. Vashistha; Ajai (International Journal of Remote Sensing, 2009)

Immunomodulator Effect of Picroliv and its Potential in Treatment Against Resistant Plasmodium yoelii (MDR) Infection in Mice - Varun Dwivedi; Arif Khan; Azevedo Vasco; Nishat Fatima; Vishal Kumar Soni; Anil Dangi; Shailja Misra-Bhattacharya; Mohammad Owais (Pharmaceutical Research, 2008)

Cloning, characterization and expression of the chitinase gene of Enterobacter sp. NRG4 - M. Salam; N. Dahiya; R. Sharma; S. K. Soni; G. S. Hoondal; R. Tewari (Indian Journal of Microbiology, 2008)

On the marine atmospheric boundary layer characteristics over Bay of Bengal and Arabian Sea during the Integrated Campaign for Aerosols, gases and Radiation Budget (ICARB) - Denny P. Alappattu; D. Bala Subrahamanyam; P. K. Kunhikrishnan; K. M. Somayaji; G. S. Bhat; R. Venkatesan; C. B. S. Dutt; A. Bagavath Singh; V. K. Soni; A. S. Tripathi (Journal of Earth System Science, 2008)

QSAR study of 5-arylidene-2,4-thiazolidinediones as aldose reductase inhibitors - Love Kumar Soni; Arun Kumar Gupta; S. G. Kaskhedikar (Medicinal Chemistry Research, 2008)

Zeta Potential of Selected Bacteria in Drinking Water When Dead, Starved, or Exposed to Minimal and Rich Culture Media - Kamlesh A. Soni; Ashwin K. Balasubramanian; Ali Beskok; Suresh D. Pillai (Current Microbiology, 2008)

Production and partial characterization of two types of phytase from Aspergillus niger NCIM 563 under submerged fermentation conditions - Sarvesh Kumar Soni; Jayant Malhar Khire (World Journal of Microbiology and Biotechnology, 2007)

Impact of Distillery Soil Leachate on Haematology of Swiss Albino Mice (Mus musculus) - Subhasini Sharma; Arti Sharma; Pawan Kumar Singh; Pratima Soni; Shweta Sharma; Pradeep Sharma; K. P. Sharma (Bulletin of Environmental Contamination and Toxicology, 2007)

Obesity and risk of non-Hodgkin lymphoma (United States) - Brian C.-H. Chiu; Lori Soni; Susan M. Gapstur; Angela J. Fought; Andrew M. Evens; Dennis D. Weisenburger (Cancer Causes & Control, 2007)

Shallow cover over coal mining: a case study of subsidence at Kamptee Colliery, Nagpur, India - A. K. Soni; K. K. K Singh; A. Prakash; K. B. Singh; A. K. Chakraboraty (Bulletin of Engineering Geology and the Environment, 2007)

Low incidence of bovine leukocyte adhesion deficiency (BLAD) carriers in Indian cattle and buffalo breeds - Rajesh K. Patel; Krishna M. Singh; Kalpesh J. Soni; Jenabhai B. Chauhan; Krothapalli R. S. Sambasiva Rao (Journal of Applied Genetics, 2007)

Evaluation of Hydrogeological Parameters Associated with Limestone Mining: A Case Study from Chandrapur, India - A. K. Soni (Mine Water and the Environment, 2007)

The Effect of Film Thickness on Thermal Aerosol Generation - Dan J. Myers; Ryan D. Timmons; Amy T. Lu; Ron L. Hale; Dennis W. Solas; Pravin Soni; Josh D. Rabinowitz (Pharmaceutical Research, 2007)

Lack of carriers of citrullinaemia and DUMPS in Indian Holstein cattle - Rajesh K. Patel; Krishna M. Singh; Kalpesh J. Soni; Jenabhai B. Chauhan; Krothapalli R. S. Sambasiva Rao (Journal of Applied Genetics, 2006)

Cross-linked guar gum microspheres: A viable approach for improved delivery of anticancer drugs for the treatment of colorectal cancer - Mohini Chaurasia; Manish K. Chourasia; Nitin K. Jain; Aviral Jain; Vandana Soni; Yashwant Gupta; Sanjay K. Jain (AAPS PharmSciTech, 2006)

Organochlorine Pesticide Residues in Milk and Blood of Women from Anupgarh, Rajasthan, India - Ashok Kumar; Anju Baroth; Inderpal Soni; Pradeep Bhatnagar; P. J. John (Environmental Monitoring and Assessment, 2006)

IL-10 promoter single nucleotide polymorphisms are significantly associated with resistance to leprosy - Dheeraj Malhotra; Katayoon Darvishi; Soni Sood; Swarkar Sharma; Chander Grover; Vineet Relhan; B. S. N. Reddy; R. N. K. Bamezai (Human Genetics, 2005)

Design and development of multivesicular liposomal depot delivery system for controlled systemic delivery of acyclovir sodium - Sanjay K. Jain; Rajesh K. Jain; Manish K. Chourasia; Akhilesh K. Jain; Kishore B. Chalasani; Vandana Soni; Aviral Jain (AAPS PharmSciTech, 2005)

Molecular mechanism of action of major Helicobacter pylori virulence factors - Suman Kumar Dhar; Rajesh K. Soni; Bimal K. Das; Gauranga Mukhopadhyay (Molecular and Cellular Biochemistry, 2003)

Cognitive effects of olanzapine and clozapine treatment in chronic schizophrenia - Tonmoy Sharma; Catherine Hughes; William Soni; Veena Kumari (Psychopharmacology, 2003)

Land damage assessment - a case study - A. K. Soni; V. J. Loveson (Journal of the Indian Society of Remote Sensing, 2003)

Poly(D,L-Lactide-Co-Glycolide) microspheres containing 5-fluorouracil: Optimization of process parameters - Rajesh H. Parikh; Jolly R. Parikh; Rajesh R. Dubey; Heena N. Soni; Kishor N. Kapadia (AAPS PharmSciTech, 2003)

Life cycle assessment study at Tata Steel, Jamshedpur, India - Soni, R. Sripiya; P. V. T Rao; O. N. Mohanty (The International Journal of Life Cycle Assessment, 2002)

Degumming of buel (Grewia optiva) bast fibres by pectinolytic enzyme from Bacillus sp. DT7 - Des R. Kashayp; Pawan K. Vohra; Sanjeev K. Soni; Rupinder Tewari (Biotechnology Letters, 2001)

Comparative Study of Agar Diffusion Test and the NCCLS Macrobroth Method for In Vitro Susceptibility Testing of Candida spp. - Luciana Maria Faiad Soni; Marcelo Nascimento Burattini; Antonio Carlos Campos Pignatari; Olga Fischman Gompertz; Arnaldo Lopes Colombo (Mycopathologia, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Production of extracellular alkaline lipase by a new thermophilicBacillus sp - P. Sidhu; R. Sharma; S. K. Soni; J. K. Gupta (Folia Microbiologica, 1998)

Effect of N-Nitrosodiethylamine on Lipid Peroxidation and Antioxidant Enzymes in Rat Liver Mitochondria: Protective Role of Antioxidants - A. K. Bansal; D. Bhatnagar; G. L. Soni (Bulletin of Environmental Contamination and Toxicology, 1997)